Nitrogen-doped porous carbon from sucrose-polyaniline precursor co-processing: high CO2 adsorption performance and cyclic stability - Li Zhao; Run Zhang; Yong-sheng Ma; Zhong-hao Wu; Qi Niu; Xin-hua Yuan; Xin-yue Zhou; Kai Li; Qiang Lu (Biomass and Bioenergy, 2027)

Annual straw return mode enhances soil quality, apparent stable organic carbon saturation capacity, and seedcotton yield stability in East China - Qiang Li; Ying Zhang; Junjie Ma; Hongbin Wang; Xin Wang; Luyao Liu; Wenqing Zhao; Wei Hu; Zhiguo Zhou; Haishui Yang; Yali Meng (European Journal of Agronomy, 2027)

Coupling modeling, design optimization, and experimental research of agrivoltaic systems based on soybean cultivation - Qiang Yu; Gaocheng Zhang; Xiaoyu Xu; Wenyao Zhao; Haoyan Li; Jian Zhao (Computers and Electronics in Agriculture, 2026)

Low-temperature pyrolysis enhanced dissociation and waste oil assisted green flotation for the recovery of electrode materials from spent LiCoO2 batteries - Xin-long Li; Xiang-nan Zhu; Guang-liang Wei; Chun-liu Hu; Xiao-tian Zhao; Jing-tao Chen; Wen-hao Gao; Chun-chen Nie; Yong-qiang Zhao; Gu-yue Li (Minerals Engineering, 2026)

Introgression shapes the genomic conflict landscape of Malus, providing evidence for a reticulate backbone in a woody crop lineage - Xiao-Ya Li; Zhao-Qian Niu; Ya-Wen Zheng; Jue-Lin Huang; Dai-Kun Ma; Jia-Xin Huang; Qiang Hao; Ti-Cao Zhang; Si-Yu Xie; Chao Xu; Bin-Bin Liu (Molecular Phylogenetics and Evolution, 2026)

Irrigation partitioning triggers multi-hazard cascades mediated by rising groundwater in Heifangtai loess terrace, NW China - Kuanyao Zhao; Qiang Xu; Wanlin Chen; Dalei Peng; Yongsong Li; Haoche Shui; Zhaozhao Liu; Beibei Zhou; Jiayu Qiu; Hongxuan Jiang (CATENA, 2026)

Astragaloside IV pretreatment enhances the therapeutic efficacy of bone marrow mesenchymal stem cells in murine fulminant hepatic failure - Ting-Ting Zhao; Wen-Qiang He; Rui-Zhi Shi; Bing-Yu Du; Mei-Mei Lan; Dan Zhou; Xiao-Qin Gao; Min Li; Jun-Feng Li; Li-Ting Zhang (Molecular Biology Reports, 2026)

Bushen Yijing formula exerts chondroprotective effects in knee osteoarthritis via the ERα/PI3K/AKT signaling pathway: Insights from network pharmacology and experimental validation - Yu-Qing Zhai; Jian-Wei Lu; Qiang Yan; Jia-Wei Du; Yang-Shuo Ge; Min-Jun Zhao; Jian-Li Yin; Chun-Meng Huang; Ting-Ting Meng; Xin-Hui Huang; Liao-Lin Chen; Jia-Hui Luo; et al. (Tissue and Cell, 2026)

Continuous versus discontinuous biodegradable film mulching in maize: A five-year field study on soil carbon sequestration, productivity, and microplastic legacy - Kai Wang; Xiao Li; Shiyan Sun; Gary Y. Gan; Ying Zhao; Qiang Li; Jiangxin Gu; Rui Jiang (Field Crops Research, 2026)

Rhizobia block Cd absorption in peanut via rhizosphere microbiome assembly and N-regulated host defense - Xinyi Li; Jie Zhou; Xiang Liu; Luyao Liu; Qiang Chen; Quanju Xiang; Yunfu Gu; Ke Zhao; Likou Zou; Qiangfeng Wang; Haiying Yu; Xiumei Yu (Environmental Pollution, 2026)

Hybrid nonlinear energy sink for vibration suppression of truss-hinged deployable arms considering locking-device nonlinearity - Tao Peng; Rongqiang Liu; Runchao Zhao; Chuang Shi; Biao Li; Hongwei Guo; Qiang Cong (Engineering Structures, 2026)

A bioinspired nanovesicle integrates multistep brain delivery and ROS-triggered release for ischemic stroke therapy - Yu Huang; Xuehao Yu; Qianqian Zhao; Jiahua Wang; Jinlong Zhang; Yuanyuan Guo; Qiang Zhang; Tingting Yao; Yuehua Li (Chemical Engineering Journal, 2026)

Mechanism of Kushen Tongguan Pill on benign prostatic hyperplasia: roles of TLR4/NF-κB pathway and macrophage M1 polarization - Shaofeng Chen; Jie Wang; Yuhong Feng; Chunxu Li; Fu Wang; Lin Miao; Yaojun Li; Yangyang Lei; Qiang Geng; Zhong Li; Feng Zhao; Yuan Sun; et al. (Journal of Molecular Histology, 2026)

Compressive bearing capacity field test of a vertical-inclined combined core high-pressure jet grouting pile group foundation - Meilin Li; Gang Zheng; Qiang Lou; Yu Zhao; Haizuo Zhou; Weiguo Jiao; Hong Wang; Fei Gan (Transportation Geotechnics, 2026)

Supplementation with C-type natriuretic peptide during pre-in vitro maturation regulates key aspects of cumulus cell physiology in cattle - Leyu Zhao; Qiang Zhang; Jing Li; Xiaoyu Zhang; Shuai Gao; Zhenwei Jia (Theriogenology, 2026)

Model-based inference of monsoonal moisture from stalagmite and tree-ring δ18O - Qiang Li; Yifan Wu; Jiachuan Wang; Yu Liu; Yanjun Cai; Haiwei Zhang; Liangcheng Tan; Jingyao Zhao; Changfeng Sun; Huiming Song; Yang Xu; Yueer Li; et al. (Quaternary Science Reviews, 2026)

The GmCYCLOPS paralogs regulate soybean nodulation and exhibit signatures during domestication - Yuanting Lei; Zhi Liu; Qiang Chen; Xintong Wu; Ming Li; Fulong Liu; Yuzhen Liu; Zhitong Yin; Siyuan Zhao; Pengshuo Shen; Yuan Zhao; Sobhi F. Lamlom; et al. (Plant Science, 2026)

Defect engineering of La-Co bimetallic sites in fly ash-based zeolite: A sustainable paradigm for high-efficiency lithium capture - Tao Yang; Puyan Zhao; Zhengyuan Du; Li Wang; Chenlong Duan; Yan Sun; Yanbiao Xu; Qiang Zhang; Jinpeng Qiao (Journal of Environmental Chemical Engineering, 2026)

Multimodal machine learning reveals strain-specific flavor and kinetic dynamics in chinese spicy cabbage fermentation - Weiye Cheng; Qingyang Zhang; Xingye Sun; Xuan Wang; Yun Cen; Qiang Zhao; Hansheng Gong; Kanghee Ko; Wenli Liu; Xiaoping Liu; Huamin Li (Food Research International, 2026)

Rhamnolipids: from biosynthesis to applications - Ai-Ping Pang; Zhiqing Zhang; Guo-Zhao Li; Yun Wang; Kun Yang; Junping Zhou; Lianggang Huang; Li-Qun Jin; Zhi-Qiang Liu; Yu-Guo Zheng (Food Chemistry, 2026)

Green manuring promotes grain yield and nitrogen use efficiency of spring wheat under chemical nitrogen reduction by enhancing plant nitrogen uptake and soil nitrogen supply - Yanwei Guo; Wen Yin; Hailong Qiu; Pan Li; Jingui Wei; Diankai Zhang; Lianhao Zhao; Pingxing Wan; Zhilong Fan; Falong Hu; Yunyou Nan; Qiang Chai; et al. (Field Crops Research, 2026)

Enhancing photosynthetic traits and source-sink relationships through organic fertilizer substitution to improve maize radiation use efficiency and yield stability under reduced irrigation - Feier Wang; Pan Li; Hailong Qiu; Xinyuan Ma; Jing Zhu; Lianhao Zhao; Pingxing Wan; Zhilong Fan; Falong Hu; Qiang Chai; Heyu Chen; Mohamed Abdalla; et al. (Field Crops Research, 2026)

Prenatal exposure to organophosphate esters and infantile neurobehavior: Integrating the gut microbiome and metabolome - Yuhan Zhou; Liyi Zhang; Qiang Li; Hang Wang; Huijing Shi; Yingya Zhao; Xirong Xiao; Yunhui Zhang (Environmental Research, 2026)

Hierarchical core–shell nanoplatforms based on sacrificial template-directed ZnO2@ZIF-8 for spatiotemporally controlled and self-augmented chemodynamic–photothermal antibacterial therapy - Yi-Fei Hui; Duan-Ping Hu; Yi Zhao; Shulin Li; Zhi-Feng Cai; Lin-Yi Li; Yuming Xie; Yong-Nian Zeng; Zu-Jin Lin; Fa-Qiang Tang (Chemical Engineering Journal, 2026)

Femtosecond laser customized fabrication of ultrabroadband microwave absorbers with hierarchical metastructures regulation - Qiang Li; Jinhao Liu; Jianlong Xie; Chunyang Zhao (Chemical Engineering Journal, 2026)

Engineering inverse CeO2/Cu interfaces for efficient hydrogen production from methanol steam reforming - Shengchao Chen; Jiayi Zhang; Ruihan Wang; Jiawei Guo; Jinhai Yang; Yan Song; Linda Zhang; Xin Huang; Tengfei Gao; Qiang Wang; Hao Li; Ning Zhao (Chemical Engineering Journal, 2026)

Structure and protection of Cichorium glandulosum polysaccharides against sarcopenic obesity through activating mitophagy via butyrate-GPR43-AMPK pathway - Chong Ma; Ruoyu Geng; Qiang Hou; Yao Zhao; Yanzhe Yue; Taotao Xue; Limei Wen; Tian Li; Jianhua Yang; Junping Hu (Carbohydrate Polymers, 2026)

Tip funnel-shaped nanochannels sensor for high-flux chloride transport inspired by CLC - Cuiguang Ma; Haifan Zhang; Govindasami Periyasami; Qiang He; Yuechao Liu; Zhihang Zhao; Shuhui Hu; Ehsan Bahojb Noruzi; Jia Li; Liuwei Jiang; Haibing Li (Analytica Chimica Acta, 2026)

Granzyme A participates in intestinal inflammation induced by PFOA through affecting PAR1/β-catenin/TBX3/IL24 pathway - Ya-nan Li; Xuemei Wang; Lei Zhang; Peng-pu Wang; Jian-qiang Zhang; Xin Fang; Yu-yao Cheng; Xing-yu Zhao; Feng-hong Wang (Chemico-Biological Interactions, 2026)

Mechanisms of growth regulation and environmental effects of ambient nutrients on Vallisneria natans in eutrophic lakes - Weijie Li; Bingbing Liang; Ling Li; Yutai Dai; Jiping Chen; Mengdi Zhao; Hong Shen; Qiang Gao; Xi Yang; Dongqin Wang; Xuwei Deng (Water Research, 2026)

Earthquake-induced displacement model for earth slopes incorporating soil softening effect based on material point method - Yu-Han Zhao; Qiang Wu; Zhi-Yong Fu; Dian-Qing Li; Wenqi Du (Soil Dynamics and Earthquake Engineering, 2026)

From thermal runaway propagation to inhalation risk: Influence of state of charge on heat transfer and particle emissions in lithium-ion batteries - Yijia He; Qiang Dong; Zhan Wang; Huifeng Li; Chenwei Shang; Long Ma; Ming Fu; Jinlong Zhao; Xiaole Zhang (Process Safety and Environmental Protection, 2026)

Heterologous expression of Arabidopsis RLP30 enhances fungal resistance in poplar - Lijuan Zhao; Qiang Cheng; Xiaodie Huo; Conghui Li; Bingqing Li; Xueqin Meng; Qi Li; Rui Sun; ZeYao Li; Haitao Liu (Physiological and Molecular Plant Pathology, 2026)

Infrared radiation modulates hexanal formation during rice grain storage via lipid-metabolic, enzymatic, and structural regulation - Tingting Tao; Miaomiao Ying; Lisong Huang; Qi Yao; Xihua Ding; Xiaoqing Li; Qiang Liu; Siqi Zhao; Xinbo Zhuang; Liping Guo; Chao Ding (Journal of Cereal Science, 2026)

Microbial and environmental determinants of 1-propanol biosynthesis in Jiang-flavor Baijiu fermentation - Wei-Tao Zhai; Han Zhao; Li-Juan Chai; Wei Zhang; Xiao-Juan Zhang; Zhen-Ming Lu; Chuan-Qiang Gao; Guan-Ru Si; Wen-Qing Zhang; Song-Tao Wang; Cai-Hong Shen; Zheng-Hong Xu (Food Microbiology, 2026)

Relative-effect metrics do not reflect societal burden under population ageing: Evidence from cold spell–related dementia mortality in China - Rui Zhang; Songwang Wang; Yujie Meng; Huan Zheng; Zixiong Zhao; Qing Guo; Shuo Zhan; Qiang Chen; Chaonan Wang; Jia Zhao; Ainan Jia; Xuejie Du; et al. (Environmental Impact Assessment Review, 2026)

CXCR2-engineered biomimetic prodrug nanoplatform restores STING signaling and enhances anti-glioma immunity - Qiuchen Bi; Huamiao Zhang; Zhangqiang Ma; Zhao Wang; Heping Zhu; Kamran Ali; Xiaoli Sun; Xiaoling Zhu; Huiqian Wang; Qianhui Zhao; Xin Wang; Jiaqi Cao; et al. (Chemical Engineering Journal, 2026)

Stress-homogenization tailoring via 2D-seed-mediated template growth for high-efficiency perovskite solar cells - Chenyun Wang; Chuanzhen Shang; Bin Zhou; Duo Qu; Shasha Wang; Wei Jia; Linwei Li; Qiang Guo; Ruilin Han; Wenying Zhao; Fan Xu; Jihuai Wu; et al. (Chemical Engineering Journal, 2026)

Fluorene-containing poly(aryl ketone) membranes with high-density sulfonation and improved stability for proton exchange membrane fuel cells - Qiang Ren; Wenying Li; Liyuan Chen; Ziyu Lin; Hongyu Pan; Zhiwei Zhao; Guannan Chen; Jinhui Pang; Zhewen Liu; Zhenhua Jiang (Chemical Engineering Journal, 2026)

Activating lattice oxygen in Ni-doped SnO2 to break surface confinement for high-performance hydrogen sensing - Meili Wu; Yanbai Shen; Sikai Zhao; Ang Li; Jinzhou Bai; Qiang Zhao; Wenbao Liu; Zhenyu Yuan; Fanli Meng (Chemical Engineering Journal, 2026)

Engineering centimeter-thick free-standing carbon electrodes through synergistic integration of multiscale cellular wood channels and penetrative binary molten salt - Weimin Chen; Yanzhuo Zhou; Pu Yang; Zhao Li; Daotong Zhang; Ziyi Xu; Qiang Yang; Chaozheng Liu; Kai Yang; Feng Jiang; Xiaoyan Zhou (Chemical Engineering Journal, 2026)

An enhanced and humidity-adaptive chitosan foam triboelectric nanogenerator: Multi-component synergistic design for energy harvesting and sensing applications - Jie Tao; Qiangli Zhao; Jiahao Kang; Min Mao; Qiang Mu; Tao Jiang; Lanjin Wang; Panxu Wang; Xiao Han; Xinhai He; Jianwei Li (Carbohydrate Polymers, 2026)

Research on Multi-Scale Feature Extraction and Mineral Content Inversion in Elemental Logging Based on an Integrated RF-CNN-XGBoost Model - You-hai Sun; Zhong-jian Li; Yong-qiang Zhao; Ze-bin Gong; Yang Zhang; Shou-qing Zhang; Dan Yu (Applied Geophysics, 2026)

Influence of Interbedded Soft and Hard Rock on Rock Burst and Microseismic Activities in Deeps: Case Studies - Yue-Mao Zhao; Zheng-Chen Ge; Peng-Xiang Li; Kai Liu; Ben-Guo He; Xing-Dong Zhao; Guo-Qiang Zhu (Rock Mechanics and Rock Engineering, 2026)

Land-Use Type Dominates Over Rhizosphere Effects on phoC- and phoD-Harboring Bacterial Communities in Acidic Soils - Xiaoli Li; Xun Xiao; Long Guo; Xiao Ying Dong; Ren Fang Shen; Xue Qiang Zhao (Journal of Soil Science and Plant Nutrition, 2026)

Pore size-matched adsorption of organic pollutants and its pilot application in advanced wastewater treatment - Baogui Wang; Yingxu Liu; Bowen Hou; Qiang Li; Di Mao; Xiangnan Li; Shanshan Feng; Yunfei Tan; Dongsong Zhao; Hongwei Yu; Zhenao Gu; Chengzhi Hu (Water Research, 2026)

Annexin A2 orchestrates CSFV entry route selection via the annexin A2/S100A10 heterotetrameric complex - Tao Wang; Liangcai Da; Junfang Zhao; Hong Yuan; Ying Sun; Liang Zhang; Jiaoyang Li; Kun Li; Jing Zhang; Pu Sun; Zhixun Zhao; Qiang Zhang; et al. (Veterinary Microbiology, 2026)

Mannan-based oral nanovaccine rebalances intestinal immunity against food allergy - Yu Miao; Qiang Zhang; Pengxing Li; Hanlin Zhang; Mengyan Wang; Linfu Chen; Zheyu Kang; Zhuyu Hou; Haibin Zhao; Xinying Lv; Yang Yang; Qian Chen (Science Bulletin, 2026)

AGR2-high cells drive a FOXM1-mediated pro-malignancy program in non-functional pancreatic neuroendocrine tumors (NF-PanNETs) and informatively predict patient outcomes - Junya Peng; Rui Jiang; Jiajuan Tu; Wanli Liu; Lu Ping; Ruikang Dun; Wenyu Zhang; Hao Chen; Yihong Shi; Xu Pan; Panpan Jia; Mengjie Li; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Epsilon-supervised contrastive learning with boundary-gradient sampling open-set fault diagnosis for industrial processes - Qiang Zhao; Mingyu Li; Guangyang Deng; Yinghua Han (Process Safety and Environmental Protection, 2026)

Plasma-engineered MIL-88A/GO-NH2 composites for flow-through solid-phase extraction of trace psychoactive substances - Qiang Wang; Xiaojuan Cao; Gen Li; Yinghao Zhao; Dongmei Li; Yabing Shan; Xianbin Zeng; Boyang Cao; Dongjing Liu; Fei Chen; Jiamei Lei (Journal of Environmental Chemical Engineering, 2026)

Comparing the impacts of conventional and emerging roasting processes on duck myofibrillar protein structure, volatile profiles, and polycyclic aromatic hydrocarbon formation - Jiawei Zhao; Xinze Li; Jiamin Shen; Changyu Zhou; Yangying Sun; Hongbing Yan; Jinxuan Cao; Daodong Pan; Kai Zhang; Qiang Xia (Food Research International, 2026)

Prenatal exposure to per- and polyfluoroalkyl substances, placental DNA methylation, and small vulnerable newborns: Insights from the Shanghai maternal-child pairs cohort - Yue Zhao; Liyi Zhang; Weizhao Cao; Pengpeng Wang; Yuyan Gui; Yuhan Zhou; Qiang Li; Yaqi Xu; Feng Wang; Jieming Wang; Yashuo Xie; Huijing Shi; et al. (Environmental Research, 2026)

Hierarchical metal–oxide composite architectures for enhanced coupled radiative and convective heat dissipation - Qiang Zhao; Jie Cheng; Haosong Li; Huiting Sun; Jiafu Wang; Jingze Li; Jihua Zhang (Chemical Engineering Journal, 2026)

Nanoscale competing polar orders enabling superior energy storage in lead-free relaxors - Haoyu Tang; Wenwei Ge; Wenting Tang; Qiang Zhou; Liang Li; Changyi Liu; Hongwei Zhao; Haiwu Zhang; Haosu Luo (Chemical Engineering Journal, 2026)

Halloysite surface-induced spin-state regulation and hydroxyl-assisted adsorption: A dual enhancement mechanism for PMS activation - Haiyi Lv; Sikai Zhao; Yan Li; Qiang Zhao; Xiaoyu Jiang; Hongshan Bi; Zhou Lin; Yanbai Shen (Chemical Engineering Journal, 2026)

Mechanism of magnetite coupled microbial enhancement in mariculture wastewater treatment: Dual edged role of magnetite - Kejin Zong; Ting Zhang; Yuan Li; Mingde Ji; Jiaxing Lu; Ying Guo; Congcong Zhao; Jianshu Lv; Qiang Kong; Qian Wang; Jian Zhang (Bioresource Technology, 2026)

One-step fabrication of porous carbon via molten salt-assisted pyrolysis and evaluation of its CO2 adsorption performance - Li Zhao; Run Zhang; Ting Huang; Ding-wang Qiao; Qi Niu; Ze-jun Luo; Kai Li; Qiang Lu (Biomass and Bioenergy, 2026)

TianGong database—an open-source, ILCD entry-level life cycle unit process database of china - Ming Xu; Weiqiang Chen; Yutao Wang; Lei Shi; Zhi Cao; Huimin Chang; Chang Chen; Xiangbin Ding; Jianwei Du; Huabo Duan; Kai Fang; Cuiyang Feng; et al. (Journal of Industrial Ecology, 2026)

Substrate type and structural complexity drive macrobenthic diversity of coral reefs in the South China Sea - Peng-Jin Zhu; Li-Sha Hu; Zhan-Wei Zhao; Hong-Qiang Yang; Min Hui; Ze-Lin Chen; Yun-Wei Dong (Coral Reefs, 2026)

Enhanced landslide detection via multi-module deep learning: a morphology-dependent performance analysis approach - Zhengwu Yuan; Sen Kang; Pinglang Kou; Qiang Xu; Xiaobo Luo; Qinchuan Gu; Xinchan Li; Zhao Jin; Chuanhao Pu (Bulletin of Engineering Geology and the Environment, 2026)

Comparative effects of digestion residue-derived and corn straw biochar on free-living diazotrophs in nitrogen-deficient calcareous purple soil - Junwen Zhao; Yuting Chen; Haiyan Zhang; Yulan Chen; Bing Li; Muhammad Bilal Khan; Yingjie Wu; Xiaoyan Tang; Huanxiu Li; Rong Huang; Qiang Xu; Qiquan Li; et al. (Biology and Fertility of Soils, 2026)

First-principles calculation of the thermally activated chemical reaction process in kaolinite - Qing Wang; Tiyuan Shan; Xinyi Ma; Limei Wu; Tianru Li; Mingyu Zhao; Qiang Zhang (Applied Clay Science, 2026)

Long-term intercropping increases soil microbial community stability via network simplification and stochastic assembly - Pingxing Wan; Wen Yin; Pan Li; Yakov Kuzyakov; Saeed Karbin; Lianhao Zhao; Cai Zhao; Aizhong Yu; Zhilong Fan; Falong Hu; Hong Fan; Qiang Chai (Agriculture, Ecosystems & Environment, 2026)

Identification of KL29 type acinetobacter baumannii phage of obolenskvirus subfamily and tail-associated depolymerase activity - Jinpan Wei; Tao Yu; Qiang Wang; Can Wang; Xuefeng Li; Guoping Lu; Lijuan Li; Aihui Xu; Lei Zhao (Archives of Virology, 2026)

Interaction Between Carbon and Nitrogen Cycling in the Vanadium Titanium Magnetite Tailings Soil During Pongamia pinnata Remediation - Xiang Liu; Lan Zeng; Xinyi Li; Qiyi Li; Qilu He; Yueyi Li; Yunfu Gu; Quanju Xiang; Ke Zhao; Likou Zou; Menggen Ma; Qiang Chen; et al. (Journal of Soil Science and Plant Nutrition, 2026)

Numerical investigation on liquefaction-induced deformation behavior of sandy foundations under railway embankments - Jinqiao Zhao; Xuanming Ding; Siau Chen Chian; Weiting Deng; Shengnan Li; Qiang Ou (Transportation Geotechnics, 2026)

The role of ecosystem conservation and restoration in achieving the SDGs - Yizhong Huan; Guangjin Zhou; Alice C. Hughes; Xiaoyun Li; Peng Hou; Marco Lambertini; Tao Liang; Wenwu Zhao; Binoy Sarkar; Alexandre Betinardi Strapasson; Yiming Su; Xiaoman Liu; et al. (Science Bulletin, 2026)

Graph representation learning with causal–confounding feature separation for fault diagnosis in industrial processes - Qiang Zhao; Haowei Li; Haiyang Du; Yinghua Han (Process Safety and Environmental Protection, 2026)

Resveratrol-derived N-doped carbon dots enabling dual-mode sensing and active preservation in biodegradable seafood packaging - Zhenqiao Ma; Peini Li; Yiqing Deng; Xiandi Yang; Kaixuan Guo; Yaling Liu; Qiang Zhao (Innovative Food Science & Emerging Technologies, 2026)

Synergistic sulfur-chlorine dual sites drive wide-temperature mercury purification in smelting flue gas - Su Wang; Dilong Qiang; Haiting Yan; Zhou Zhou; Mindong Chen; Zhen Li; Songjian Zhao (Fuel, 2026)

Water-saving and economic benefits of a soil moisture threshold-based irrigation strategy for cotton in Xinjiang under climate change - Bin Chen; Linjia Yao; Yadong Liu; Mohamed Amine Benaly; Changqing Yan; Genghong Wu; Ronghao Guan; Yi Li; Dongyan Zhang; Jie Bai; Qiuxiang Tang; Jianqiang He; et al. (European Journal of Agronomy, 2026)

Effects of heat input on heat-affected zone of simultaneously welded cruciform fillet joints in Q550D and Q690D steels - Yize Gao; Xiao-Ling Zhao; Yan-Bo Wang; Rui Yan; Zhe Sun; Guo-Qiang Li (Engineering Structures, 2026)

Hydroxyapatite nanoparticles improve vitrified bovine MII oocyte developmental competence by reducing ultrastructural damage and modulating gene expression - Xiao-Xia Li; Yi-Hang Wang; Jun Wang; Shi-Yu Zhang; Jia-Hao Zhang; Shi-Han Zhao; Qi Yan; Ping-Hua Cao; Zi-Qiang Zhang; Chen Zhou; Zhen Zhang; Qiao-Ting Shi; et al. (Animal Reproduction Science, 2026)

Mitochondria-targeted redox-logic carbon dots for in vivo realtime visualization of peroxynitrite during wound-healing - Jing-Yu Hu; Xin Gen; Yuan-Qiang Sun; Zhao-Hui Li (Analytica Chimica Acta, 2026)

Temporal and spatial evolution of deep rock mass damage and failure based on acoustic emission and discrete element method - An-Ying Yuan; Yi-Hao Sun; Yong-Qiang Zhao; Hao Huang; Tang Li (Applied Geophysics, 2026)

Antibiotic transport and release effects in paddy soil-water system under water level regulation modes - Jian Zhang; Qinglin Li; Renjie Hou; Zhaoqiang Zhou; Qiang Fu; Tianxiao Li; Anshuang Su; Hai Xu; Miao Wang; Wei Huang; Shan Zhao (Water Research, 2026)

Orchestrated multicopper heterostructural motifs in MOF enable tandem CO2 valorization via photothermal-photocatalytic C–N coupling - Jian-Qiang Zhao; Hui-Li Zheng; Yu-Jia Cheng; Cheng-Xia Chen; Xiong-Feng Ma; Zheng Yin; Jia-Wei Li; Dong-Dong Ma; Hua Lin; Xin-Tao Wu; Cheng-Yong Su; Qi-Long Zhu (Science Bulletin, 2026)

Global material flow analysis of scandium from 2000 to 2024: Insights into supply, stocks, and circularity gaps - Qiang-Feng Li; Yi-Ding Wu; Lu Wang; Dan Lai; Qi-Ming Guo; Zong-Bin Shi; Shen Zhao; Qian-Qian Wang; Wei-Qiang Chen (Resources, Conservation and Recycling, 2026)

Seep-related carbonates on continental shelves: Distinctive processes and morphologies revealed by the Qiongdongnan Shelf, South China Sea - Hongli Wang; Qiang Zhao; Fangqi Wang; Qingfeng Hua; Qiuhong Xie; Yangting Liu; Chenguang Liu; Yanliang Pei; Xishuang Li; Yikai Feng; Fei Cao (Marine Geology, 2026)

PfAgo-guided SERS signal conversion for amplification-free and semi-quantitative detection of Salmonella typhimurium in food and physiological samples - Ruibo Zhao; Jingjing Bai; Qiang Zhang; Jiayi Wei; Fei Deng; Myunghee Kim; Xingjie Li; Shuli Man; Weipan Peng; Long Ma (Journal of Hazardous Materials, 2026)

SiO2@CLDH as a modifier for synergistic solidification of chlorides and heavy metals in municipal solid waste incineration fly ash - Li Tianru; Li Mingfei; Wang Lele; Zhang Qiang; Ding Zhaoyang; Wang Xuesong; Wang Qing; Zhao Mingyu (Journal of Environmental Chemical Engineering, 2026)

Continuous plastic film mulching reduces global warming potential (GWP) in greenhouse soil biosolarization by regulating microbial carbon and nitrogen metabolism - Qianru Liu; Qiang Zuo; Yuteng Qi; Yufan Yang; Guochun Ding; Mao Li; Guicheng Han; Yinzhi Chu; Bingxue Wang; Yuhao Sun; Xiao Zhao; Lianfeng Du; et al. (Journal of Cleaner Production, 2026)

3-Mercaptopropyltrimethoxysilane combined with manganese sulfate reduces Cd accumulation in wheat on weakly alkaline soils via plant-soil-microorganism regulation - Li Zhang; Nan Zhao; Ajit K Sarmah; Lijie Zhao; Qiang Zeng; Yuepeng La; Dasong Lin; Ruigang Wang (Journal of Environmental Sciences, 2026)

Apparent resistivity evaluation method of slurry diffusion-solidification and grouting effect of water-bearing fractured rock mass - Hao Xu; Zhen-zhong Xing; Sheng-quan He; Lian-zhi Yang; Yi Zhu; Da-zhao Song; Yu Zhang; Jin-tao Dang; Qiang Liu; Li-ming Qiu; Ping Wang (Journal of Applied Geophysics, 2026)

A study of complete brewing process of Jiang-flavor Baijiu and brewing functions of thermotolerant actinomycetes - Qingqing Li; Chuanyu Du; Baoxia Mei; Qiang Yang; Shenxi Chen; Rongsheng Fan; Nan Peng; Shumiao Zhao (Food Chemistry, 2026)

Chronic ammonia-N exposure impairs the intestinal health of the Siberian sturgeon (Acipenser baerii Brandt): through the pathways of oxidative stress, tight junction proteins, inflammatory factors, and intestinal microbiota - Huimin Sun; Qiang Hu; Yujie Huang; Siqi Zhao; Guangwei Cao; Zhizhen Zhang; Fei Wang; Defang Chen; Zhiqiong Li; Xin Zhang (Fish & Shellfish Immunology, 2026)

Elevated CO2 accelerates mineral-protected organic carbon loss in the upland rhizosphere after paddy drainage - Xun Yan; Zhifan Li; Bo Kang; Tao Li; Linkang Chen; Junwen Zhao; Bing Li; Youlin Luo; Yingjie Wu; Rong Huang; Xiaoyan Tang; Qiang Xu; et al. (CATENA, 2026)

Intercomparison of AI forecasts and numerical weather predictions for the July 2021 extreme precipitation event in Henan, China - Qiang Li; Tongtiegang Zhao (Stochastic Environmental Research and Risk Assessment, 2026)

Study on a Thermo-Hydro-Mechanical-Damage Coupling Model and Numerical Simulation of Coal Body Considering Liquid Nitrogen Seepage - Changbao Jiang; Hao Li; Chonghong Zhao; Yunbo Li; Jian Hou; Yi Li; Qiang Li; Wei Li (Rock Mechanics and Rock Engineering, 2026)

Promoter-driven enhancement of PHBV synthesis in recombinant Escherichia coli using glucose and propionate as carbon sources - Zhao-song Huang; Cheng-jiao Yu; Zi-miao Yan; Chang-feng Miao; Ling-yi Hou; Peng-fei Gu; Xiang-yu Fan; Qiang Li (Archives of Microbiology, 2026)

Probiotics in the alleviation of food allergies in infants and young children: research progress - Zihan Wen; Zhenzhen Zhang; Xiaojing Li; Zhenxing Qiang; Hui Wang; Qiuying Wang; Junying Zhao; Wenxiao Feng; Jingjing Peng; Ling Guo; Lijun Chen (Critical Reviews in Food Science and Nutrition, 2026)

Slope aspect modulates fertilization impacts on PLFA-based soil microbial community structure but not on diversity in a degraded alpine grassland under restoration - Qiang Zhang; Yunfei Xing; Xiaoli Wang; Jianjun Shi; Chunhui Zhang; Huakun Zhou; Honglin Li; Xinquan Zhao; Yushou Ma (Plant and Soil, 2026)

Phylogeny of the Chinese Mydaeinae (Diptera, Muscoidea, Muscidae) based on morphological characters - Kailin Wang; Qiang Zhang; Lulu Tian; Yameng Wang; Yuli Zhang; Shengjuan Zhao; Wenliang Li (Zoologischer Anzeiger, 2026)

Plastisphere denitrification dynamics shaped by soil acidification: Microbial Community and activity responses - Yu-Chen Li; Sha Zhao; Hu Li; Pei-Yuan Xu; Hong-Xia Cui; Jian-Qiang Su (Journal of Hazardous Materials, 2026)

Phage-based suppression of plasmid-mediated antibiotic resistance: A promising approach for antimicrobial stewardship - Yan-Zi Wang; Hu Li; Bei-Ning Xue; Xiao-Xu Zhao; Yu Rao; Sha Zhao; Kiandro J. Fortuna; Mao Ye; Jian-Qiang Su (Journal of Hazardous Materials, 2026)

Bioremediation of high concentrations of mercury and nickel in activated sludge by black soldier fly larvae: Accumulation, transformation, and sustainability assessment - Bo Deng; Chong-Yang Ren; Zi-He Ren; Zhi-Jian Zhang; Qiang Li; Qiao-Xia Yuan; He-Ping Zhao (Journal of Hazardous Materials, 2026)

Genetic diversity analysis of three geographical populations of Triplophysa yarkandensis macroptera in arid northwestern China - Ya Liu; Hangyu Lin; Hongyu Ke; Han Zhao; Zhongmeng Zhao; Shengqi Su; Qiang Li (Journal of Arid Environments, 2026)

Decoding the molecular mechanisms of metaplast transformation in coal pyrolysis - Zhao Lei; Chuandong Zheng; Qin Pei; Qiang Ling; Xiangchun Liu; Xiaodong Li; Ping Cui (Fuel, 2026)

Numerical simulation of fracture propagation and interwell frac-hit mechanism in deep shale gas infill wells - Yufeng Wang; Qiang Wang; Jinzhou Zhao; Yongquan Hu; Jianglong Wang; Juhui Zhu; Rong Wang; Xiaowei Li; Yu Yang (Engineering Geology, 2026)

Thermoelectric interface material screening strategy toward full-SnTe couple - Yaning Wang; Yi Yuan; Yonghui Ma; Zhe Wang; Kai Zhao; Junliang Chen; Guojian Li; Tie Liu; Qiang Wang (Chemical Engineering Journal, 2026)

From spent lithium-ion batteries to high-grade “urban mines”: A review of green recovery technologies for strategic metal resources of electrode material - Xiao-tian Zhao; Xiang-nan Zhu; Xin-long Li; Guang-liang Wei; Jing-tao Chen; Chun-liu Hu; Chun-chen Nie; Gu-yue Li; Yong-qiang Zhao (Chemical Engineering Journal, 2026)

Synergistic photobiocatalytic antifouling strategy based on a Bi5O7I/CeO2 heterojunction for sustainable marine coating - Bingqing Jia; Ting Xu; Qian Zhang; Xudong Geng; Jiachen Xu; Yuezheng Li; Yuanyuan Qu; Xiangdong Liu; Mingwen Zhao; Weifeng Li; Yong-Qiang Li (Chemical Engineering Journal, 2026)

An interface engineering strategy for SiC nanoelectrodes to investigate the mechanism of glutathione-mediated alleviation of hepatotoxicity - Qiang Zhou; Jian Wang; Yangmingxu Meng; Yi Li; Xianglong Zhao; Zexuan Meng; Jiuxi Sui; Lu Yang; Jiajia Chen; Xuanbing Wang; Ji Gong; Guangqiang Pan; et al. (Chemical Engineering Journal, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Geochemistry of tourmaline in granitic rocks from the Zharigana and Caolong areas, Northern Tibet: Implications for the identification of lithium-mineralizing plutons - Ling Ma; Jin-Sheng Zhou; Qiang Wang; Lin Ma; Jin-Heng Liu; Wu-Fu Li; Bing-Zhang Wang; Chun-Tao Wang; Jian-Dong Liu; Xin-Yuan Zhang; Mao-Rui Liu; Zhi-Wei Yu; et al. (Lithos, 2026)

Zinc-iron layered double hydroxide enhances cadmium tolerance in tobacco via cell wall immobilization and regulation of phenylpropanoid and nitrogen metabolism - Xiaoyan Sui; Zhenyu Zhao; Qiang Ma; Zhongqing Liu; Sheng Zhang; Jianbing Ding; Zhengyu Deng; Pengfei Yi; Weijie Yan; Xiaoxuan Yi; Haocun Tang; Zhenhua Wang; et al. (Journal of Environmental Management, 2026)

Pollution characteristics of Litopenaeus vannamei greenhouse effluents and purification performance of a combined flocculation–ecological floating bed system - Shanyuan Xue; Guo Li; Ensheng Zhu; Weizhen Zhang; Jiao Ran; Zhe Li; Yu Zhao; Jingru Hu; Jing Dong; Yingxue Yi; Dan Zhou; Qiang He; et al. (Journal of Environmental Chemical Engineering, 2026)

Effects of coal tar pitch properties and processing parameters on the strength of formed coke prepared from coke breeze: an analysis using interpretive structural modeling and ridge regression - Yinrui Dong; Yongbin Yang; Lin Wang; Chen Zhao; Yan Zhang; Qiang Zhong; Qian Li; Tao Jiang (Fuel, 2026)

Umifenovir protects Procambarus clarkii against white spot syndrome virus by suppressing viral replication and modulating innate immunity - Cheng Chen; Bo-Han Li; Chao-Yu Wang; Er-Long Wang; Tian-Qiang Liu; Zhe Zhao (Fish & Shellfish Immunology, 2026)

Orbital hybridization engineering via P-refilling: Enhancing structural robustness and oxygen vacancy stability in V6O13 cathode for durable aqueous zinc-ion batteries - Can Huang; Tiezhong Liu; Pengjin Li; Jialin Wang; Tingting Liu; Shuang Hou; Tianwen Huang; Qiang Deng; Lingzhi Zhao (Chemical Engineering Journal, 2026)

Integrated dynamic control and enzyme co-localization strategies enable high-efficiency stilbenoid biosynthesis - Guofu Zhao; Pengpai Li; Xinyao Ding; Jiugong Lv; Ying Yang; Lin Liu; Lihan Zi; Qiang Zhang; Liya Liang; Rongming Liu (Bioresource Technology, 2026)

Metabolomic and physiological responses of mulberry plants to exogenous molybdenum enhance amino acid and sugar metabolism - Zipei Cui; Michael Ackah; Frank Kwarteng Amoako; Jianbin Li; Aaron Tettey Asare; Changyu Qiu; Qiang Lin; Owuraku Amponsah Abu; Isaac K. A. Galyuon; Xueying Jin; Mengdi Zhao; Weiguo Zhao (Plant and Soil, 2026)

Non-covalent proteasome inhibitor PI1840 suppresses osteoclastogenesis and prevents LPS-induced osteolysis in mice - Yehua Xia; Fuli Zhao; Cheng Dang; Jiayi Bai; Yueqiang Li; Jiaxue Yang; Qiuyi You; Qiang Tang; Wenwen Dou; Mei Liu (Inflammopharmacology, 2026)

Integrated assessment of Nitenpyram-induced physiological and microbial alterations in Chinese longsnout catfish - Yang Liu; Han Zhao; Chengyan Mou; Zhongmeng Zhao; Lu Zhang; Huadong Li; Qiang Li; Jian Zhou (Ecotoxicology, 2026)

HUTG: a next-generation IGS real‑time combined GIM via two‑step global and regional correction with robust weighting from HENU and UPC‑IonSAT - Kualong Xu; Qi Liu; Manuel Hernández-Pajares; Enric Monte-Moreno; Heng Yang; Germán Olivares-Pulido; David Roma-Dollase; Alberto García-Rigo; Ningbo Wang; Zishen Li; Ang Liu; Clément Ubelmann; et al. (GPS Solutions, 2026)

General Biogeographic Rules and Lineage‐Specific History Shape the Assembly of Asian Tropical Megadiversity - Hao Wu; Bing‐Yue Zhu; Jing Yang; Qiang Zhang; Zhen‐Ping Shi; Yan‐Jing Shi; Xiao‐Chen Zhao; Pei‐Yi Yang; Ke‐Xin Fan; Guang‐Shun Li; Si‐Qi Hu; Yee Wen Low; et al. (Journal of Biogeography, 2026)
Aim Tropical Asia's extraordinary plant diversity is thought to be intrinsically linked to its dynamic geological history. However, quantifying the precise evolutionary processes that assembled this diversity across the archipelago remains challenging. A recently proposed biogeographic framework classifies the functional roles of different regions as “radiators,” “incubators,” “corridors” or “accumulators,” offering a useful framework to analyse this complexity. Here, we aim to provide a critical, independent test of this framework using the megadiverse tree genus Syzygium as a model system. Syzygium originated on the Sahul Shelf, contrasting with the Indochinese origin of rattan palms used in the original framework validation. Location Tropical Asia, Pacific Islands and Africa. Methods We analysed the complete chloroplast genome of 200 species of the genus Syzygium and performed phylogenetic analysis to estimate divergence times, ancestral region reconstruction, and estimated diversification and extinction rates. We then analysed the relationship between regional area and the dispersal of species and examined speciation and dispersal patterns in relation to the geographical environment. Results Our comprehensive chloroplast phylogenomic analysis indicates rapid diversification of Syzygium commencing ~12 million years ago, coinciding with shelf collision. Biogeographic reconstructions indicate that while the framework's general principles hold – continental shelf act as “radiators” and isolated islands as “incubators” – the specific geographic roles vary depend on lineage history . Main Conclusions Our study validates the radiator‐incubator model as a general feature of tropical Asian evolution but refines it by demonstrating that historical contingency is key to understanding the assembly of Earth's richest biota. Tropical Asian plant diversity reflects a unique geological history of continental shelf collision and dynamic island geography, offering insights into biodiversity evolution in other geologically active regions worldwide, highlighting the importance of maintaining large, connected natural areas and dispersal corridors for preserving the evolutionary processes that generate Earth's botanical richness.

Enhanced pathogenicity of Vibrio cholerae S15G02 ΔluxS mutant in Procypris rabaudi: AI-2 quorum sensing disruption triggers hypervirulence - Tianzhi Jin; Yanhan Yang; Kaixuan Liu; Haixin Yi; Junrong Qin; Qiang Zhao; Shilin Li; Shixia Huang; Zhijian Wang; Fang Li (Aquaculture, 2026)

In situ biofilm development on microplastics and its impact on PFAS adsorption in aquatic environment - Guoqing Hou; Rui Zhang; Tianhui Zhao; Mengyuan Fang; Lin Niu; Qitao Lei; Qiang Li; Nuo Chen; Zhi Tang; Xiaoli Zhao; Fengchang Wu (Water Research, 2026)

Priorities for enhancing resilience of SDG causal network from a human-nature perspective - Yiming Su; Guangjin Zhou; Mingyuan Wang; Xiaoyun Li; Tao Liang; Lingqing Wang; Jian Hu; Jixi Gao; Wenwu Zhao; Siyuan Tao; Peter E. Holm; Jörg Rinklebe; et al. (Resources, Conservation and Recycling, 2026)

Research progress and prospects on refractory materials prepared from high-carbon ferrochrome slag: A review - Zhiqiang Yang; Zhiyun Ji; Xiaohui Fan; Min Gan; Qiang Li; Yuanjie Zhao; Xiaoxian Huang; Zengqing Sun; Xuling Chen; Zhenxiang Feng (Process Safety and Environmental Protection, 2026)

A CPTu-based method for evaluating consolidation characteristics of under-consolidated soils - Yu-cheng Li; Pin-Qiang Mo; Guojun Cai; Zhao Lu; Yan Zhuang; Hai-Sui Yu (Ocean Engineering, 2026)

Magnetic chronology of the late Miocene Wulangou red clay sequences in the northern Otindag Sandy Land - Hongyu Qi; Yali Zhou; Jiangli Pang; Xiaoke Qiang; Jiale Wang; Baofeng Ma; Tong Feng; Xichen Li; Yiting Zhao; Yingying Cui; Liping Jiang; Siying Yue (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Breakthroughs in new pollutant research: Analytical methods, environmental processes, toxicological mechanisms, and control strategies - Lu Jiang; Yali Shi; Lu Bai; Qiang Zhao; Hanyong Peng; Xiaoxi Yang; Yanna Liu; Guangbo Qu; Qunfang Zhou; Yumiao Sun; Jianjie Fu; Jiyan Liu; et al. (Journal of Environmental Sciences, 2026)

Enhancing electrochemical CO2 reduction with monoamino-functionalized cobalt tetraphenylporphyrin catalysts - Li-Yuan Zhao; Hui Wang; Hao Tan; Jie Chao; Zhi-Hang Lin; Ge-Chuan-Qi Pan; Xiao-Ji Wang; Qiang Sun (Fuel, 2026)

Divergent effects of β-glucan addition in baked vs steamed bread: Deciphering hydration of BG and its interaction with starch-protein networks - Zhihui Zhang; Zhifen Pan; Yutong Li; Tianyi Zhao; Qiang Zhou; Haoquan Bian; Jiaxin Chen; Yuhong Zhang; Xingquan Zeng; Zhongyi Li; Tao Wang; Yonghong Zhou; et al. (Food Hydrocolloids, 2026)

Optimized organic-inorganic fertilization enhances soil carbon sequestration and wheat productivity: Evidence from hierarchical carbon pool analysis - Qiang Liu; Shenglong Zhao; Yifei Li (Field Crops Research, 2026)

A coupled thermo-hydro-mechanical damage (THMD) model based on finite element method-discrete fracture model (FEM-DFM) for simulating supercritical CO2 (ScCO2) fracturing - Kang Yang; Yunpei Liang; Quangui Li; Qiang Chen; Zhengduo Zhao; Xiaolong Yang; Yuxuan Li (Computers and Geotechnics, 2026)

Mechanically interlocked graphene architectures for enhanced thermal conductivity and reduced thermal contact resistance - Qiang Zhao; Jie Cheng; Lijia Chen; Qindong Zhang; Xianzhen Cai; Jingze Li; Xinhui Xia; Yongqi Zhang (Chemical Engineering Journal, 2026)

Sulfonic acid electrolyte additives realizing high-energy-density magnesium-air batteries by pH-controlled interphase engineering and in situ protective layer construction - Wang Qiang; Sha Jianchun; Li Xue; Chen Weilong; Wang Kehao; Zhang Yusong; Yang Yiqiang; Qiao Mingliang; Tian Jie; Liu Wenhong; Zhao Zhong; Zhang Zhiqiang (Chemical Engineering Journal, 2026)

Stepwise biofabrication of CuMnS from electroplating wastewater: bimetal-sulfur synergy for enhanced peroxymonosulfate activation - Xian-Zhong Fu; Yong-Qiang Ma; Xiao-Jing Zhao; Wen-Hui Xu; Chen-Xuan Li; Chun-Yan Guo; Xue-Yuan Wang; Fei-Yang Wang; You-De Zhang; Kang-Ping Cui (Bioresource Technology, 2026)

Nr4a2, A Key Factor Controlling the Development and Functional Maintenance of Forebrain Car3 Neurons - Yun-Chao Tao; Li Zhao; Qiong Zhang; Xi-Yue Liu; Wei-Tang Liu; Ze-Xuan Li; Ling Hu; Lei Zhang; Jia-Yin Chen; Yu-Qiang Ding; Ning-Ning Song (Neuroscience Bulletin, 2026)
Nr4a2 ( Nurr1 ) is well known to be vital for midbrain dopaminergic neurons. Recent single-cell RNA analyses reveal that Nr4a2 is expressed in lateral cerebral regions, within neurons named L4/L5/L6 IT Car3 . These neurons have attracted intense attention for the molecular mechanisms underlying their development and functions. We classified Car3 neurons into neocortical (Ncx- Car3 ), claustral (CLA- Car3 ), and dorsal endopiriform nucleus (dEn- Car3 ) subpopulations, focusing on the characterization of Ncx- Car3 neurons. These neurons exhibit distinct birthdates and migratory morphologies compared to CLA- and dEn- Car3 neurons, but share a common transcriptomic profile when Nr4a2 is deleted at the embryonic stage or in adulthood. Notably, Nr4a2 misexpression ectopically induces Car3 -enriched genes in vivo . Mice lacking Nr4a2 in Car3 ensembles during the embryonic stage or in adulthood display hyperactivity and reduced anxiety-like behaviors. Therefore, our results demonstrate that Nr4a2 is a key factor in regulating the development and functional maintenance of the forebrain Car3 neurons.

Soil carbon sequestration and microbial metabolic limitation under wheat-cotton straw returning with potassium fertilization - Qiang Li; Ying Zhang; Zhaorui Cheng; Li’an Wang; Wei Hu; Wenqing Zhao; Zhiguo Zhou; Haishui Yang; Yali Meng (Journal of Soils and Sediments, 2026)

Microbial traits mediate the functional components of soil organic carbon under long-term fertilization - Yanhong Yuan; Jiachang Zhang; Zhanrong Feng; Qi Zhang; Zihan Zhao; Qiang Li; Shuiqing Zhang; Gehong Wei; Xinhui Han; Minggang Xu; Andong Cai; Chengjie Ren (Applied Soil Ecology, 2026)

Adverse outcome pathway analysis identifies DRP1-driven mitochondrial dysfunction as a central event in silver nanoparticle-induced hepatocyte ferroptosis - Jiangyan Li; Jiaqi Lan; Zhiwen Liu; Yujia Zhang; Zhuang Duan; Xinyue Wang; Zhijun Geng; Bao Zhao; Hezuo Lü; Qiang Fang; Fengchao Wang (Apoptosis, 2026)

Large Potential for CH 4 Mitigation and Yield Improvement in China's Paddies Through Locally Optimized N Management - Haoyu Qian; Zhengqi Yuan; Xiangcheng Zhu; Yuanfa Huang; Min Li; Jiarui Li; Yuxin Ren; Jinfei Feng; Shan Huang; Wenjun Dong; Feng Jin; Jiping Gao; et al. (Global Change Biology, 2026)
Nitrogen (N) management is critical for ensuring food security and mitigating greenhouse gas (GHG) emissions. In rice paddies, the effectiveness of N management in maximizing yields and minimizing N losses is highly dependent on local environmental conditions and thus varies widely across regions. However, the influence of optimized, site‐specific N management on methane (CH 4 ) emissions remains poorly quantified and is not reflected in current IPCC Tier 1 methodologies. Here, we synthesize data from multiregional field experiments and conduct a meta‐analysis to show that locally optimized N management practices—such as delayed fertilizer application, reduced N input, and deep placement—reduce CH 4 emissions from rice paddies by 16%–21%. The experiments further show that these practices suppress CH 4 emissions by lowering soil N availability and organic matter decomposition, thereby limiting substrates for methanogenesis. Combining survey data from 155 counties with machine learning models, we estimate that implementing optimized N strategies across China's rice‐growing regions could reduce CH 4 emissions by 16% while simultaneously increasing rice yields by 7%. These findings underscore the dual benefits of locally optimized N management for agricultural productivity and climate change mitigation, and provide a foundation for improving CH 4 emission estimates under diverse management regimes.

The interplay between antihypertensive medication and lifestyle with cardiovascular outcomes in patients with hypertension: the PURE-China study - Biyan Wang; Zhiguang Liu; Tong Bu; Sumathy Rangarajan; Qiuyan Ma; Xiaocong Li; Qi Qiu; Yang Lin; Lap Ah Tse; Bo Hu; Salim Yusuf; Qiujing Cai; et al. (EPMA Journal, 2026)

Variations in hydrochemical characteristics and their controlling factors among different types of lakes in the northeastern region of the Qinghai-Xizang Plateau - Jiping Chen; Ling Li; Weijie Li; Bingbing Liang; Yu Lin; Yutai Dai; Mengdi Zhao; Hong Shen; Xi Yang; Qiang Gao; Xuwei Deng (Environmental Monitoring and Assessment, 2026)

Quantifying The Evolution of Rock Stiffness During Pre-peak Cyclic Loading: Influence of Porosity and Lithology - Zhao-Qiang Zheng; Li Zhuo; Jian-Liang Pei; Hong-Qiang Xie; Ming-Li Xiao; Huai-Zhong Liu (Rock Mechanics and Rock Engineering, 2026)

Mechanistic investigation of soil detachment in the corn root–soil complex using coupled MBD–DEM - Xuejie Ma; Zhihong Yu; Qiang Su; Peng Li; Wenhang Liu; Dongxu Zhao; Jianchao Zhang (Computers and Electronics in Agriculture, 2026)

ANXA2 stabilizes mTOR at the plasma membrane to facilitate autophagic flux for CSFV release - Tao Wang; Liangcai Da; Junfang Zhao; Hong Yuan; Ying Sun; Liang Zhang; Kun Li; Jing Zhang; Pu Sun; Zhixun Zhao; Qiang Zhang; Yuanji Zhang; et al. (Veterinary Microbiology, 2026)

A bHLH transcription factor negatively regulates effective panicle number and grain yield by modulating auxin transport and distribution in rice - Tao Yang; Rui Zhu; Jinlong Li; Yulong Wang; Lei Zhou; Qiaoqiao Zhao; Ningjia Jiang; An Zeng; Yanli Qin; Haixia Liu; Chenyu Xia; Shichen Han; et al. (Molecular Plant, 2026)

Catalytic performance and reaction mechanism for CO-SCR of NOx on copper and nitrogen doped OMS-2 catalysts - Qiang Zhou; Dong Li; Yan Du; Yue Wang; Chengming Zhong; Jia Hou; Di Yu; Lanyi Wang; Nan Li; Ke Yu; Jiaxin Song; Chengyang Yin; et al. (Journal of Environmental Chemical Engineering, 2026)

Unlocking the potential of umami peptides: A comprehensive review of preparation methods, evaluation strategies, health benefits, and taste transduction mechanisms - Jianhua Zhao; Xinyu Li; Lunjie Huang; Hongbin Lin; Qiang He (Food Research International, 2026)

Combination of cold plasma and sonication for efficient carotenoid extraction from Capsicum annuum L.: Optimization, mechanism exploration, and food application - Jinpeng Zhu; Li Jiang; Jianhua Zhao; Yan Xiang; Yingyi Mao; Yunhao Lu; Yumeng Xia; Yuanping Lv; Qiang He (Food Chemistry, 2026)

Integrating legume rotation and optimal nitrogen management enhances cotton yield and mitigates greenhouse gas emissions in a jujube-cotton intercropping system - Tiantian Li; Lu Feng; Jinbin Wang; Zhengjun Cui; Hang Qiao; Qiang Hu; Nan Cao; Ling Li; Wei Zhang; Mingwei Du; Yaru Zhao; Gulinigaer Taxi; et al. (European Journal of Agronomy, 2026)

Adaptive model reduction and nonlinear dynamics analysis of space truss-hinged deployable arm coupled with nonlinear energy sink - Tao Peng; Rongqiang Liu; Runchao Zhao; Chuang Shi; Biao Li; Hongwei Guo; Qiang Cong (Engineering Structures, 2026)

Creep of water-bearing soft rock and its influence on long-term rock mass stability - Zhao-Qiang Zheng; Li Zhuo; Jian-Liang Pei; Ming-Li Xiao; Huai-Zhong Liu; Hong-Qiang Xie; Tao Luo (Engineering Geology, 2026)

Multiple resonance thermally activated delayed fluorescence emitters containing novel S-based acceptor with narrowed FWHM and enhanced EQE - Xiao-Xue Xia; Guo Yuan; Feng-Ming Xie; Qiang Zhang; Yan-Qing Li; Ze Hua; Jian-Xin Tang; Xin Zhao (Chemical Engineering Journal, 2026)

A physicochemical model for accurate prediction of oil shale in-situ conversion - Cunhan Fan; Wei Guo; Qiang Li; Yuan Wang; Yanwei Li; Zhao Liu (Chemical Engineering Journal, 2026)

Injectable anti-inflammatory nanofiber hydrogel reprograms immunosuppressive tumor microenvironment via cascade-amplified immunogenic cell death - Ruo-Yun Zhang; Wei Yue; Yang Xuan; Long Qi; Lin-Lin Guo; Zhen-Zhen Zhu; Ming Yang; Zhang-Jie Pu; Guo-Qiang Li; Xin-Yi Mao; Ding Zhou; Zhao-Wei Zhang (Chemical Engineering Journal, 2026)

An agro-bionic approach to co-chelating ultrafine high-entropy metal phosphosulfide nanoparticles for superior Li/K-ion storage - Bing-Jie Feng; Jia-Jie Liu; Xiao-Hui Wu; Zhi-Qiang Gu; Li-Zhong Liu; Li-Bing Yang; Chen Dai; Ke Han; Ming-Jun Zhao; Wei-Jun Jiang; Yi Zhao (Chemical Engineering Journal, 2026)

Modulating electrode-electrolyte interface by covalent organic framework coatings for high-performance aqueous zinc-copper batteries - Lei Zhao; Yixuan Xiao; Congcong Zhu; Mengyuan Li; Fengshi Cai; Qiang Bai; Libei Yuan (Chemical Engineering Journal, 2026)

A structurally distinct arabinose-bridged arabinogalactan from Lycium barbarum as a TLR4-activating adjuvant for nanovaccine-based cancer immunotherapy - Chun-Jie Bao; Meng-Qiu Liu; Ya-Nan Liu; Li-Qiang Zhao; Yu-Xuan Li; Xin-Lan Zhang; Fang Zhang; Sheng Guo; Er-Xin Shang; Jia-Lun Duan; Jin-Ao Duan (Carbohydrate Polymers, 2026)

Hydroxybutyl chitosan-based thermosensitive hydrogel enhanced osteoporotic bone regeneration through sustained release of alendronate and BMP-2 - Mingyuan Lei; Haibing Liu; Qiang Zhong; Libo Zhao; Jingwen Liu; Huaming Mai; Yuheng Zhang; Hongyu Wang; Yourong Chen; Rong Chen; Yixin Xu; Hao Li; et al. (Carbohydrate Polymers, 2026)

Synergistic enhancement of nitrogen removal and greenhouse gas reduction in manganese-based integrated vertical constructed wetland for wastewater treatment through improved redox environment - Mingde Ji; Zhengkai Li; Qiang Kong; Qian Wang; Congcong Zhao; Jiaxing Lu; Ying Guo; Jian Zhang (Bioresource Technology, 2026)

Source identification and risk assessment of selenium and trace metals in the soil-tea system in Enshi, China - Minglong Li; Tianyu Zhao; Yunfen Zhu; Xunru Ai; Qiang Zhu; Keyuan Xu; Deshun Zheng; Liang Qiu (Plant and Soil, 2026)

Effects of Dietary Strontium Supplementation on Growth Performance, Strontium Enrichment, Muscle Nutrition, and Hepatic Lipid Metabolism in Juvenile Hybrid Sturgeon (Acipenser baerii ♀ × Acipenser schrenckii ♂) - Shilin Li; Qiang Zhao; Hang Chen; Yanhan Yang; Zhe Zhao; Jianxi Mei; Yuexin Sun; Li Peng; Hailong Ge; Fang Li; Zhijian Wang (Fishes, 2026)
To explore a safe and effective approach for producing strontium-enriched fish, in this study, we modified the feed for juvenile hybrid sturgeon (Acipenser baerii ♀ × Acipenser schrenckii ♂) and set three different levels of strontium chloride content in their diet (0 mg/kg (Sr0, control), 80 mg/kg (Sr80), and 160 mg/kg (Sr160)) for a period of 8 weeks, analyzing their growth performance, strontium enrichment, muscle nutrition, and hepatic physiological, biochemical, and transcriptomic characteristics. The results show that dietary strontium had no significant impact on sturgeon growth or survival rate (p > 0.05). The strontium content in tissues increased with dietary strontium levels, with the highest enrichment in bone plates (p

Spatiotemporal Characteristics and Long-Term Variability of Large-Wave Frequency in the Northwest Pacific - Zhen-Yu Zhao; Hong-Ze Leng; Yu-Han Wei; Jin-Hui Yang; Xuan Zhou; Ze-Zheng Zhao; Hui-Peng Wang; Bao-Xu Li; Wu-Xin Wang; Jun-Qiang Song (Journal of Marine Science and Engineering, 2026)
This study provides a systematic analysis of the spatiotemporal distribution and trends in the frequency of significant wave height (SWH) exceeding level 5 (SWH > 2.5 m) and level 7 (SWH > 6 m) in the Northwest Pacific (NWP) for 1993–2024, which are defined as f5 and f7, respectively, as well as their correlations with major climate indexes. Our results indicate that (1) the high-value zones for the annual mean f5 and f7 are both located in the south waters of the Aleutian Islands, with maximum values of 58.0% and 6.4%, respectively. Winter’s contribution is greatest (maximum values of 96.9% and 16.8% per year), while summer’s is the smallest. (2) f5 exhibits a significant decline trend across the entire NWP basin (of −0.15 to −0.30%/yr), with the steepest decline occurring in autumn (−0.69%/yr) and the shallowest in summer. f7 exhibits a significant linear decrease in the open ocean east of Japan (−0.08%/yr) while showing a significant linear increase in the waters east of the Kamchatka Peninsula (0.08%/yr). Both variations peak in winter (maximum values of −0.27% and 0.30% per year) and are smallest in summer. (3) Seasonal and regional variations in climate index–f5 and f7 relationships reflect large-scale atmospheric modulation of waves. For example, the Oceanic Niño Index shows a predominantly negative correlation with f5 in winter (maximum correlation coefficient rm = −0.70) around the Luzon Strait, shifting to a significant positive correlation in summer (rm = 0.70) across the extensive region east of Taiwan Island and the Philippines. The Pacific Decadal Oscillation index shows a significant positive correlation with f7 in summer and autumn (rm = 0.69) east of Taiwan Island and a strong negative correlation in winter (rm = −0.77) to the east of Kamchatka Peninsula.

Phosphorus dynamics in the drilosphere: Unraveling earthworm-mediated soil biogeochemistry - Zhen-Yu Qiang; Gang Li; Daniel Menezes-Blackburn; Zhao-Feng Yuan; Tida Ge; Yvan Capowiez; Dong-Xing Guan (Critical Reviews in Environmental Science and Technology, 2026)

Research on Scenario Deduction of Mass Life-Threatening Incidents at Sea Based on Bayesian Network - Qiaojie Wang; Jiacai Pan; Jun Li; Qiang Zhao; Feng Zhang; Feng Ma; Zhihui Hu (Journal of Marine Science and Engineering, 2026)
The growth of the cruise industry and rising passenger numbers have led to an increase in cruise-related accidents, presenting challenges for mass rescue operations. It is crucial to understand the evolution of MAss Life-Threatening Incidents at Sea (MALTISs) in order to make effective decisions in such situations. This study, therefore, presents a scenario deduction model for MALTIS, integrating knowledge element theory, Bayesian Networks (BNs), fuzzy set theory, and improved Dempster–Shafer (DS) evidence theory. Based on knowledge element theory, this study identifies the scenario elements in typical maritime accidents. Given the large scale and complex disaster chain characteristics of MALTISs, the BN method is employed to convert the scenario elements into BN nodes, therefore constructing the MALTIS deduction model. To minimize the subjectivity associated with expert assessments, this study combines fuzzy set theory and the improved DS evidence theory to integrate the opinions of multiple experts, thereby enhancing the reliability of the model’s deduction. BN inference is then used to calculate the probabilities of various situational states, and sensitivity analysis is conducted to identify the key nodes. The Costa Concordia grounding incident serves as an empirical case study. The deduction results closely align with the actual accident evolution, and sensitivity analysis reveals five critical nodes in the event’s progression. This validates the effectiveness of the proposed scenario deduction model. These findings demonstrate that the model can effectively support emergency decision-making in MALTISs.

Two new compounds isolated from an endophytic fungus Eutypella sp. XLE005 derived from Conus leopardus - Xin-Ming Li; Li Yang; Qing-Yun Ma; Qing-Yi Xie; Jiao-Cen Guo; Hao-Fu Dai; Du-Qiang Luo; You-Xing Zhao (Natural Product Research, 2026)

Early kick detection based on multi-scale temporal modelling and interpretability framework - Hu Yin; Yuhao Zhou; Qian Li; Xiuwen Zhao; Qiang Wei (Process Safety and Environmental Protection, 2026)

Study on the behavior of potassium in bauxite during the digestion phase of Bayer process - Yunchuan Gao; Mengnan Li; Qiang Liu; Zhanwei Liu; Wenhui Ma; Keqiang Xie; Jiaping Zhao; Hengwei Yan (Minerals Engineering, 2026)

Direct CH4 electrosynthesis from CO2 via unmodified commercial carbon black: Structural synergy and defect-driven catalysis - Rong-Chun Zhong; Yu-Nan Liu; Zengrong Wang; Li-Yuan Zhao; Teng Shi; Qiang Sun (Fuel, 2026)

Ferroptosis triggered by gill dysbiosis mediates immune failure in grass carp overwintering syndrome - Yang Feng; Senyue Liu; Xiaoli Huang; Yi Geng; Chengyan Mou; Han Zhao; Jian Zhou; Qiang Li; Yongqiang Deng (Fish & Shellfish Immunology, 2026)

Associations of PM2.5 carbonaceous and ionic constituents with fractional exhaled nitric oxide (FeNO): A panel study with 16 follow-up visits over 4 years - Nan Zhang; Yuqi Guo; Deyan Wu; Zinuo Li; Jialin Wang; Nan Zhang; Jia Xu; Xueli Yang; Qiang Zhang; Changping Li; Shi Zhao; Xumei Zhang; et al. (Environmental Research, 2026)

A carbon sink calculation model for concrete buildings considering time-variant environment - Jia-cheng Xu; Bei Li; Ye Tian; Ruo-yi Zhao; Guo-yi Zhang; Qiang Zeng; Cong-cong Ma; Bo-Tao Huang; Hong-jing Xue; Yun-jian Li; Qing Cai (Environmental Impact Assessment Review, 2026)

Quantitative Characterization of Rock-TBM Interaction for Tunnel Widening Through a Tunnelling Test Platform - Wei-Qiang Xie; Xiao-Li Liu; Jian Chen; Jin-Peng Zhao; Wen-Zhao Meng (Rock Mechanics and Rock Engineering, 2026)

Retraction Note to: TAT-PEP Enhanced Neurobehavioral Functional Recovery by Facilitating Axonal Regeneration and Corticospinal Tract Projection After Stroke - Bin Deng; Liya Li; Xingchun Gou; Hao Xu; Zhaohua Zhao; Qiang Wang; Lixian Xu (Molecular Neurobiology, 2026)

miR-133b-3p Mitigates D-Galactose-Induced Hippocampal Neuron Aging Through Autophagy Regulation via the MAPK/ERK Signaling Pathway - Yang Cao; Chen Zhao; Jiaxin Li; Qiang Gao; Chunmei Lv; Jiao Wang; Na Qiang; Wenwen Zhang; Huiyu Su; Xinyu Min; Jinfeng Liu; Xiaoqi Dai; et al. (Molecular Neurobiology, 2026)

Reciprocal rate-modulated evolution of slow-moving reservoir landslide: learning from hydrological-adapted block model - Shu Zhang; Qiang Li; Huiming Tang; Zongxing Zou; Jianfan Zhao; Jiefei Zhang; Meiling Wu (Landslides, 2026)

Machine learning-based global landslide susceptibility analysis: spatiotemporal variability and dominant environmental associations - Pinglang Kou; Haoran Yu; Qiang Xu; Minggao Tang; Zhengwu Yuan; Xu Dong; Huajin Li; Chuanhao Pu; Zhao Jin (Bulletin of Engineering Geology and the Environment, 2026)

Effects of co-application of microalgae and beneficial bacteria on flue-cured tobacco yield and soil microbial communities - Yu Peng; Yihua Quan; Wang Yao; Yi Zhao; Xinyao Liu; Deyuan Peng; Xiaoming Tang; Changwu Fu; Zhenhua Wang; Qiang Li (Applied Soil Ecology, 2026)

Supramolecular cucurbit[7]uril@AuNPs self-assembled membranes for impedimetric sensing and selective removal of cationic dyes - Ehsan Bahojb Noruzi; Qiang He; Govindasami Periyasami; Zhihang Zhao; Yuchao Liu; Cuiguang Ma; Haifan Zhang; Jing Cheng; Haibing Li (Analytica Chimica Acta, 2026)

Predation risk effects of bat foraging ultrasound on Ostrinia furnacalis: scaring without preying - Li Wang; Qiang Qu; Qiulin Guo; Junhao Guan; Jiayi Zhao; Yue Zhu; Tinglei Jiang; Jiang Feng; Hui Wu (Behavioral Ecology and Sociobiology, 2026)

Four new dammarane nortriterpenoids isolated from mastic ( Pistacia lentiscus L.) and their anti-inflammatory and cytotoxic activities - Xue Tian; Xue-Rui An; Zhi-Qiang Zhao; Jian-Hua Fan; Su-Ning Yuan; Tian-Zhi Li; Wei Liu (Natural Product Research, 2025)

Iron oxide-mediated enhancement of extracellular electron transfer and symbiosis in consortium of electroactive bacteria and microalgae for wastewater treatment - Pingyin Shu; Li Zhao; Xin Wen; Ziqi Wei; Chaowei Yuan; Huazu Liu; Xiangdong Zhang; Xizi Long; Qiang He; Wei Li (Water Research, 2025)

Welding surface epitaxial layer enables high-loading sulfide all-solid-state batteries - Zhuomin Qiang; Yanbin Ning; Wei Zhao; Yajie Song; Chaoqun Zhang; Shengwei Dong; Yifei Zhao; Yan Zhang; Yinyong Sun; Biao Deng; Xudong Li; Geping Yin; et al. (Science Bulletin, 2025)

Intensification of Weddell Sea deep water in the southern Scotia Sea since ∼0.4 Ma: Mechanistic links to the mid-Brunhes transition - Qiang Zhao; Hongli Wang; Yanpeng Zheng; Kai Liu; Xishuang Li; Chenguang Liu; Yanliang Pei; Qingfeng Hua; Long Ma; Yonghua Wu; Shulan Ge; Fei Cao; et al. (Quaternary Science Reviews, 2025)

Temporal and spatial variations of redox conditions in the middle Triassic Chang 7 member of the Yanchang formation, Ordos Basin, North China - Hanlin Liu; Yuangeng Huang; Xiangdong Zhao; Wei Wang; Xincheng Qiu; Zhen Qiu; Juan Han; Zhen Shen; Yujie Li; Ganlin Hua; Zhong-Qiang Chen; Caineng Zou (Marine and Petroleum Geology, 2025)

Micron-sized iron-sulfur minerals orchestrate micro-interface redox processes for sustainable wastewater treatment - Xin-Han Chen; Ze-Fan Chen; Chen-Peng Fang; Zhi-Zeng Zhao; Xiao-Qiang Cao; Jian Zhang; Zhao-Jing Zhu; Gang Zhou; Yi-Fan Wang; Lu-Cheng Fan; Li-Jiang Wu (Journal of Water Process Engineering, 2025)

Future climate change exacerbates streamflow depletion in the Wei River Basin, China - Hongli Chen; Lijing Fan; Qiang Li; Yaping Wang; Dengfeng Liu; Fubo Zhao (Journal of Hydrology, 2025)

Modified biochar effectively removes tetracycline and antibiotic resistance genes to enhance anaerobic digestion performance - Chuan Ding; Jiahao Liu; Jinghui Wang; Jiayu Le; Beini Lu; Nannan Qu; Shenggeng Zhao; Haoyu Zhang; Jianping Su; Yeqing Li; Qiang Liu (Journal of Environmental Chemical Engineering, 2025)

Ecological zoning management of Fenhe River Basin based on the ecosystem “structure-form-function” framework - Qiang Li; Xueyi Shi; Zhongqiu Zhao; An Cao (Journal of Environmental Management, 2025)

Molecular insights into the stability of CO2 hydrate in variable-diameter nano-slit - Xu Li; Han Jia; Qiuxia Wang; Yuanbo Wang; Fangning Fan; Bowen Wang; Qiang Wang; Yurong Zhao; Pan Huang (Gas Science and Engineering, 2025)

Covalent grafting of corn stover cellulose nanofibers with zein for pickering emulsion stabilization and controlled quercetin delivery - Xinling Wu; Qiang Zhang; Deyi Zhou; Jianpeng Dou; Qing Liang; Li Zhang; Haigen Zhou; Xiaodi Gao; Xuelin Zhao; Jinsong Zhang (Food Chemistry, 2025)

Response of Rhinogobio ventralis skin to Ichthyophthirius multifiliis infection: pathological, transcriptomic and metabolomic analyses - Qiang Zhao; Shilin Li; Siya Wang; Zhe Zhao; Xuemei Li; Hanchang Sun; Xingbing Wu; Zhijian Wang; Fang Li (Fish & Shellfish Immunology, 2025)

Leaf senescence and source-sink dynamics in soybean: Insights from maize-soybean intercropping systems - Zhen Fan; Binbin Qiang; Yanrong Lin; Pengzhao Liu; Zhipeng Li; Mengwei Cheng; Xining Zhao; Xiaolong Ren; Xiaoli Chen (Field Crops Research, 2025)

Low-carbon alkali-activated geopolymer of industrial byproducts: Parameter optimization and life-cycle advantages for the green construction material - Hui Gao; Qiang Zhao; Li Zuo; Wei Guo (Environmental Research, 2025)

Development and validation of a magnetic - based corrosion detection system for reinforced concrete structures - Jian Cheng; Yu-meng Xie; Rong-sen Gao; Ye Tian; Guo-yi Zhang; Dongming Yan; Bo Chen; Ruo-yi Zhao; Bei Li; Jun Chen; Dong-yang Cai; Wei-qiang Wu; et al. (Engineering Structures, 2025)

Dual-coated Akkermansia muciniphila for the treatment of inflammatory bowel disease - Peixu Zhao; Guangshuai Zhang; Hongge Wang; Xiaolang Luo; Mengdi Qin; Manlin Teng; Genyang Ye; Zhaohua Li; Qiang Fu (Chemical Engineering Journal, 2025)

Photothermal nanomedicine for glioblastoma: From material design to clinical translation challenges - Chan Li; Hui-Zhe Xu; Xue-Yan Cheng; Xin Yu; Zhi-Qiang Gong; Yi-Jiang He; Ling-Xiao Zhao; Zhan-You Wang (Chemical Engineering Journal, 2025)

Asymmetric actuators via lignin-cellulose nanofibrous composite films with programmable wet-light dual-responsiveness - Qiang Mu; Qiangli Zhao; Min Mao; Yao Liu; Jie Tao; Jiahao Kang; Wei Yong; Xinhai He; Jianhua Ma; Jianwei Li (Carbohydrate Polymers, 2025)

Impact of climate change and vegetation greening on sediment transport in the Yarlung Tsangpo River - Yiyi Li; Ting Zhang; Yi Zhao; Ziqi Guo; Peng Han; Qiang Zhong; Liu Liu; Shuyue Mao; Yichu Wang; Dongfeng Li (CATENA, 2025)

Alteration of Cecal Microbiota by Antimicrobial Peptides Enhances the Rational and Efficient Utilization of Nutrients in Holstein Bulls - Jinping Shi; Yu Lei; Zemin Li; Li Jia; Pengjia He; Qiang Cheng; Zhao Zhang; Zhaomin Lei (Probiotics and Antimicrobial Proteins, 2025)

IF-MMCL: an individual focused network with multi-view and multi-modal contrastive learning for cross-subject emotion recognition - Qiaoli Zhou; Jiawen Song; Yi Zhao; Shun Zhang; Qiang Du; Li Ke (Medical & Biological Engineering & Computing, 2025)

Analysis of the Electrical Structure and Fluid Content of the Southern San Andreas Fault - Bao-Chun Li; Shao-Huai Sun; Bao-Qiang Tai; Cheng Gao; Ji-En Dong; Kuo Zhang; Xin-Yi Zhang; Zhao-Yuan Kang; Xiang-Guo Guo (Applied Geophysics, 2025)

Advancements in DNAzyme-based biosensors for the detection of hazardous substances in foodstuff: current applications and future perspectives - Taolin Li; Yijia Zhang; Weiwei Cheng; Tiantian Wang; Shuai Hou; Siqi Zhao; Leiqing Pan; Min Chen; Chao Ding; Qiang Liu (Critical Reviews in Food Science and Nutrition, 2025)

A discriminative invariant feature learning network based on sample selection for partial domain adaptation in industrial process fault diagnosis - Qiang Zhao; Chuan Sun; Mingyu Li; Yinghua Han (Process Safety and Environmental Protection, 2025)

Cyetpyrafen, chlorfenapyr and spirodiclofen affect the olfactory recognition of Dastarcus helophoroides by acting on DhelOBP4 and DhelOBP21 - Zhengyi Mao; Wen Zhao; Dongping Chen; Zhiyan Jiang; Qiang Liu; Jiayun Li; Yunxuan Wu; Nannan Lv; Jianting Fan (Pesticide Biochemistry and Physiology, 2025)

Chlorholones A−H, bioactive sesquiterpenoids with diverse skeletons from Chloranthus holostegius - Zhao-Chun Zhan; Ting Lu; Hai-Shan Zhang; Mei-Ting Weng; Hui-hui Zhu; Qiang Lin; Hai-Yue Zhao; Yue-Hao Huang; Tian-Yuan Wu; Miao Wang; Yao-Lan Li; Yi-Wen Zhang; et al. (Phytochemistry, 2025)

The dual role of organic carbon: Mitigation of nitrogen-induced soil acidification but amplification of greenhouse gas emissions - Lin Zhao; Qinghua Li; Yufang Lu; Hongmei Chen; Ju Min; Ren Fang Shen; Xue Qiang Zhao (Journal of Environmental Management, 2025)

The properties of alginate-cyclodextrin hybrid bubble hydrogel for ethylene gas encapsulation and storage - Zhanpeng Liu; Hongxin Jiang; Renyong Zhao; Xinwei Wang; Bin Zhang; Qiang Huang; Hao Li; Paul Van der Meeren (Food Research International, 2025)

MOF-enabled magnetic-fluorescent sensors for on-site organophosphorus/carbamate pesticide detection in fruits and vegetables - Yihang Zhao; Ruonan Li; Jiaze Tang; Mengge Liu; Beining Zhang; Jie Chen; Shujuan Ren; Qiang Ma; Zhaowei Sun; Haibo Weng (Food Chemistry, 2025)

Ratiometric fluorescence immunoassay based on PtPdRu trimetallic nanozyme with enhanced oxidase-like activity for sensitive detection of xylazine - Liang Luo; Zizhe Li; Qiang Li; Qiyuan Zhao; Xiaonan Wang; Ghulam Mujtaba Mari; Jianzhong Shen; Xuezhi Yu; Zhanhui Wang; Yantong Pan; Jijun Kang (Food Chemistry, 2025)

Improving the surface hydrophilicity of ZnFe-LDO for efficient catalytic ozonation achieves durable interfacial water purification - Qiang Tan; Zhonglin Chen; Jimin Shen; Pengwei Yan; Jing Kang; Binyuan Wang; Shengxin Zhao; Yang Shen; Yabin Li (Chemical Engineering Journal, 2025)

Photoresponsive leaf-like structured two-dimensional metal-organic framework/nanocellulose crystal composites for efficient and rapid adsorption of pollutants from wastewater - Saisai Li; Luying Wang; Juan Dai; Na Zhang; Li Zhao; Shuyun Zheng; Xinxin Li; Caicai Lin; Dashuai Zhang; Qiang Li (Chemical Engineering Journal, 2025)

Association of environmental factors and biological metrics with lung health: an environment‐wide association study - Zongyuan Li; Yueli Shu; Zhi Yang; Jian Zhang; Kejia Zhao; Qiang Pu; Lunxu Liu (Environmental Geochemistry and Health, 2025)

Optimal scale landscape ecological risk evaluation based on the SI-ERI model: A case study of Leshan City, Southwest China - Kai Ye; Qiang Zou; Chengxia Wang; Ying Luo; Xishun Li; Renrui Ye; Xuhong Luo; Ting Wang; Bo Yuan; Qiuquan Zhao; Zhe Wang (Journal of Mountain Science, 2025)

Synergistic effects of slow-release fertilizer and biochar on crop yield and soil carbon-nitrogen dynamics under reduced nitrogen input - Lianhao Zhao; Wen Yin; Qiang Chai; Pan Li; Zhipeng Guo; Zhilong Fan; Falong Hu; Cai Zhao; Aizhong Yu; Pingxing Wan; Wei He; Hong Fan; et al. (Agriculture, Ecosystems & Environment, 2025)

Formulated feed enhances food consumption and gonad production of the sea urchin Strongylocentrotus intermedius at low temperature - Guo Wu; Ruihuan Tian; Xiang Li; Huiyan Wang; Gang Song; Qiang Sun; Donghong Yin; Chong Zhao (Aquaculture International, 2025)

Glutathione contributes to alleviating hepatic injury via host-microbiome interaction and CAR-dependent pathway - Xuan Xiang; Siwei Liu; Houfu Wang; Chenyu Wang; Wentao Zhou; Heshu Chen; Yanzhong Feng; Xinmiao He; Gang Xu; Qiang Zhao; Tiejun Li; Di Liu; et al. (Science China Life Sciences, 2025)

The recycling use of MSWI bottom ash as road construction material for carbon emissions reduction based on life cycle Assessment—A case study in China - Xinhao Shen; Chenyi Liu; Yao Zhao; Qiang Li; Jiaqing Wang (Waste Management, 2025)

Modeling of carbon sink for concrete structures: From hydration kinetics to climate-driven carbonation - Ye Tian; Jia-Cheng Xu; Guo-Yi Zhang; Zu-Shi Tian; Bei Li; Ruo-Yi Zhao; Qiang Zeng; Bo-Tao Huang; Dong-Ming Yan (Sustainable Chemistry and Pharmacy, 2025)

Sb-doped Cu-Fe/TiO2 catalysts with enhanced K-poisoning resistance for simultaneous NO and CO removal - Yang-wen Wu; Zheng-long Wu; Hai-yuan Zhao; Han-wen Wang; Yao Dong; Xin-yue Zhou; Jing-tao Li; Qiang Lu (Journal of Environmental Chemical Engineering, 2025)

Nitrogen addition decouples the microbial necro-mass from soil organic carbon formation in a temperate grassland - Huanhuan Cheng; Yingbin Li; Shuo Li; Tianran Sun; Guoxiang Niu; Qi Li; Junjie Yang; Yanxia Ma; Yingzhi Gao; Qiang Yu; Haitao Zhao; Qiushi Ning; et al. (Journal of Environmental Sciences, 2025)

Virtual screening and molecular mechanism of novel anti-benign prostatic hyperplasia peptides from Syngnathus schlegeli - Ailing Duan; Xiangxi Yi; Xiangtan Zhao; Si Li; Xinjian Qu; Geng Qin; Qiang Lin; Hua Chen; Peng Wan; Deke Chen; Xin Chen; Weimao Zhong; et al. (Food Research International, 2025)

A ratiometric fluorescent probe for sensitive detection of benzoyl peroxide and hypochlorite in food - Shun-Qiang Cui; Xin-Yi Liang; Zhi-Qiang Cai; Hou-Qun Yuan; Qiu-Yu Zhang; Yi-Fan Xia; A.K.I.M.A.N.A. Sandra; Ling-Yi Guo; Ran Wang; Shi-Yu Zhao; Yan-Xia Li; Guang-Ming Bao (Food Chemistry, 2025)

Sponge-based FeSx triggers enhanced and durable water decontamination from Cr(VI): Accelerated electron transfer and slow-releasing property - Shou Mei; Longjie Liu; Yiqing Du; Rongling Wang; Ziyi Zhan; Aoxue Qin; Shenglan Zhao; Yuxuan Ye; Yuwei Deng; Qiang Li; Fei Pan (Environmental Research, 2025)

Ground subsidence monitoring and prediction based on InSAR and CNN-BiGRU-Attention: A case study of Chengdu - Zhihua Zhang; Qiang Lin; Haowen Yan; Xinyu Zhu; Xinxiu Zhang; Shuwen Yang; Chunlin Huang; Yueling Shi; Jie Hu; Xuhui Li; Li Hou; Lujia Zhao; et al. (Engineering Geology, 2025)

Gene-metabolite correlations underpin the hepatic fibrosis and metabolic disruption induced by methyltestosterone in juvenile Chinese longsnout catfish (Leiocassis longirostris) - Yang Feng; Yongqiang Deng; Zhao Li; Zheng Wei; Zhongmeng Zhao; Han Zhao; Senyue Liu; Lu Zhang; Yuanliang Duan; Zhipeng Huang; Jun Du; Qiang Li; et al. (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Rational design of SnO2 quantum dots/SnS2 hybrids for enhanced NO2 sensing at room temperature: Insights from DFT and in-situ DRIFTS - Jinzhou Bai; Yanbai Shen; Ang Li; Meili Wu; Siyao Liu; Wenbao Liu; Qiang Zhao; Sikai Zhao; Fanli Meng (Chemical Engineering Journal, 2025)

Corrigendum to “In-situ electrostatic anchoring of highly oxidized Ir single atoms on NiFe LDH for efficient water oxidation” [Chem. Eng. J. 519 (2025) 165662] - Dandan Li; Lei Ding; Sihang Zhang; Pengfang Zhang; Claudia Prestigiacomo; Degao Wang; Qiang Zhao (Chemical Engineering Journal, 2025)

An integrated experimental and computational study of waste printed circuit boards pyrolysis: the fate of bromine and the influence of copper - Ji Liu; Hong-jin Zhang; Yuan-gu Xia; Bin Hu; Zhen-xi Zhang; Li Zhao; Qiang Lu (Chemical Engineering Journal, 2025)

Charge-engineered biomass enables concurrent salt rejection and antibacterial performance toward efficient and sustainable interfacial solar desalination - Fengbo Zhu; Ke Qian; Fukai Li; Jianhang Zhao; Peng Yan; Meng An; Qiang Zheng; Zi Liang Wu; Wenwen Yu (Chemical Engineering Journal, 2025)

Optimizing electrochemical performance and temperature stability of NVPF via copper doping - Ramon Alberto Paredes Camacho; Xin-Yu Wang; Lei Shen; Qiang Wang; Yi-Ming Zhao; Ming-Xia Gao; Li Lu (Chemical Engineering Journal, 2025)

Linking low δ44/40Ca basalts to recycled carbonates through coupled chemical and Ca-Zn-Mg isotopic covariations - Hang Xu; Xiao-Jun Wang; Xiao-Yu Zhang; Gang Zeng; Jian-Qiang Liu; Jian Zhao; Fang Liu; Li-Hui Chen (Chemical Geology, 2025)

Single cell protein production of co-culture Kodamaea ohmeri and Lactococcus lactis in corn straw hydrolysate - Yong-Qiang Yang; Xu Li; Zhen-Zhi Wang; Xiao-Yan Huang; Du-Wen Zeng; Xin-Qing Zhao; Zhi-Qiang Liu; Feng-Li Zhang (Bioresource Technology, 2025)

Unraveling the seasonal variability of meteorological droughts: multiscale insights into the coupling with atmospheric circulation factors - Jianwen Xue; Qiang Zhao; Guoqing Sang; Qingguo Li; Qi Wang; Qingfan Song; Xiumei Li (Theoretical and Applied Climatology, 2025)

Mulberry (Morus alba L.) planting increased the abundance of soil carbon cycling functional genes by improving soil properties, and further enhanced the stability of soil carbon pool - Meina Zhu; Zi Yang; Zhenjiang Wang; Victor Edem Tsigbey; Zipei Cui; Wenfeng Zhang; Weijun Zhu; Jianbin Li; Changyu Qiu; Qiang Lin; Haonan Li; Hanfa Shahid; et al. (Plant and Soil, 2025)

Design and synthesis of glycyrrhetinic acid glycosides against acute lung injury and pulmonary fibrosis - Wei Li; Jianrong Liu; Tianbo Wu; Xin Qiang; Yijie Peng; Quanyi Zhao; Dian He (Molecular Diversity, 2025)

CDIP-ChatGLM3: A dual-model approach integrating computer vision and language modeling for crop disease identification and prescription - Changqing Yan; Zeyun Liang; Han Cheng; Shuyang Li; Guangpeng Yang; Zhiwei Li; Ling Yin; Junjie Qu; Jing Wang; Genghong Wu; Qi Tian; Qiang Yu; et al. (Computers and Electronics in Agriculture, 2025)

Silicon supplementation via carriers to enhance diatom competition with cyanobacterial blooms and remediate eutrophic waters - Rui Zhou; Bang Xiao; Li Zhao; Yangyang Tang; Wei Yang; Huazu Liu; Xiangdong Zhang; Chaowei Yuan; Xinqi Wang; Xizi Long; Qiang He; Wei Li (Water Research, 2025)

Root plasticity improves the potential of maize/soybean intercropping to stabilize the yield - Zhen Fan; Pengzhao Liu; Yanrong Lin; Binbin Qiang; Zhipeng Li; Mengwei Cheng; Qihang Guo; Jinpeng Liu; Xiaolong Ren; Xining Zhao; Xiaoli Chen (Soil and Tillage Research, 2025)

Putting the recent 100-year of Asian summer monsoon weakening into context - Jingyao Zhao; Hai Cheng; Liangkang Pan; Kexin Wang; Jiahui Cui; Ming-Qiang Liang; Xiyu Dong; Jiayu Lu; Qiang Li; Yan Yang (Science Bulletin, 2025)

Efficacy and safety of an mRNA encoding neutralizing antibody against SARS-CoV-2 in non-human primates - Hang Chi; Suo-Qun Zhao; Yun-Peng Liu; Xiao-Chuan Xiong; Xia Zhong; Xing-Xing Suo; Xing-Yao Huang; Can Yue; Jing-Jing Zhang; Zhe Cong; Na Li; Fei-Xue Du; et al. (Science Bulletin, 2025)

Enhanced ozone decomposition in humid conditions by bismuth-doped OMS-2 - Tianhong Mei; Dilong Qiang; Hongyang Jin; Juncheng Li; Liwei Qiu; Wei Liu; Zhen Li; Songjian Zhao (Process Safety and Environmental Protection, 2025)

Effects of dissolved organic matter on the adsorption–desorption process and bioavailability of polycyclic aromatic hydrocarbons in constructed wetland substrates - Congcong Zhao; Zaixin Zhang; Wenying Li; Luxing Liu; Jian Zhang; Jiarong Yu; Jiatong Wang; Jingtao Xu; Qian Wang; Jiaxing Lu; Mingde Ji; Qiang Kong (Process Safety and Environmental Protection, 2025)

The GRAS transcription factor BpGRAS34 functions as a positive regulator of salt stress response in Betula platyphylla - Lei Li; Zengzhi Tian; Zizhuo Zhao; Qiang Wang; Weiqi Li; Huiyan Guo; Xiaoyu Ji (Plant Science, 2025)

Morphology, proteome and metabolome characterization of the sporoplasm of Ameson portunus (Microsporidia) - Ya-Li Xu; Min Zhou; Zhi-Qiang Zhu; Zhao-Zhe Xin; Jin-Yong Zhang (Journal of Invertebrate Pathology, 2025)

Fatty acids as biomarkers of organohalogen contaminant exposure in mangrove insects from the Pearl River Estuary, South China - Qiang Xie; Lihua Yang; Fenglong Jia; Lvyan Tan; Shuang Zhao; Yuhai Lu; Yingjie Cao; Yuping Wu; Li Lin; Tiangang Luan (Journal of Hazardous Materials, 2025)

Effects of lightweighting on emissions of vehicles with different powertrains: Insights from dynamic and interpretable life cycle assessment - Yu Lu; Qiang Liu; Jinglong Zhu; Zhangzhen Zhao; Zilong Li; Qing Li (Journal of Cleaner Production, 2025)

Catalytic fast pyrolysis of waste battery separators with limited removal of the Al2O3 layer for selective aromatic hydrocarbons production over HZSM-5 catalyst - Li Zhao; Wan-zhao Huang; Shi-guan Yang; Qi Niu; Shi-yu Feng; Pu-cheng Wang; Ying Mo; Yu-han Fan; Kai Li; Qiang Lu (Journal of Environmental Management, 2025)

Tracking climate fluctuations in the North China during the Carboniferous-Permian transition using chemical weathering indices - Wanli Gao; Qin Zhang; Jingtao Zhao; Qiang Fang; Wen Liu; Weiliang Kong; Wenyu Li; Hongjie Peng; Tianquan Qu; Guangyin Cai; Jianghai Yang; Zhen Qiu (Global and Planetary Change, 2025)

Operando magnetometry decodes fast sodium storage: Biomass-derived Bi@NSC anodes with triple-phase kinetics - Jing Chen; Shuxuan Liao; Jinghao Zhao; Boyu Zhao; Yao Liu; Qiang Li; Xin Li (Chemical Engineering Journal, 2025)

Construction of dynamically regulated biomimetic nanochannels inspired by temperature-sensitive proteins for intelligent release of pesticides - Haonan Qu; Jiaxin Quan; Ehsan Bahojb Noruzi; Haifan Zhang; Cuiguang Ma; Qiang He; Yuchao Liu; Zhihang Zhao; Chenyu Su; Haibing Li (Chemical Engineering Journal, 2025)

In-situ electrostatic anchoring of highly oxidized Ir single atoms on NiFe LDH for efficient water oxidation - Dandan Li; Lei Ding; Sihang Zhang; Pengfang Zhang; Claudia Prestigiacomo; Degao Wang; Qiang Zhao (Chemical Engineering Journal, 2025)

All-screen-printed tactile sensor for robotic arm via polymeric thermal foaming - Xun Fu; Yugang Chen; Shuting Xie; Mengyu Cao; Qiang Zhao; Yixiao Liu; Yang Li; Shasha Wang; Xiaogang Cheng; Linghai Xie (Chemical Engineering Journal, 2025)

Suspended microalgae biofilm particles driven by fluid shear force for high efficiency of livestock wastewater purification - Yun Huang; Zitao Zhao; Ai Song; Yabo Sun; Dongdong Li; Xianqing Zhu; Ao Xia; Xun Zhu; Qiang Liao (Chemical Engineering Journal, 2025)

Multi-crosslinked network enables robust cellulose/chitosan composite aerogel for triboelectric sensor with humidity adaptivity - Jiahao Kang; Qiangli Zhao; Min Mao; Yugen Wang; Qiang Mu; Jie Tao; Xiaoliang Zhao; Xinhai He; Jianwei Li (Chemical Engineering Journal, 2025)

Nuclide classification and prediction method based on correlation coefficient with dynamic mode decomposition - Pengchao Xue; Qian Zhang; Yunfei Zhang; Shuai Qin; Shifu Wu; Qiang Zhao; Zhuo Li (Annals of Nuclear Energy, 2025)

Quantitative analysis of H2O2-related biomarkers using surface-enhanced Raman spectroscopy technology based on TMB-Au@PB nanoparticles - Yanglan Zhao; Han Xia; Yuqing Li; Shuying Mao; Conghui Zhou; Jizhong Yan; Shengqiang Tong; Qiang Wang; Hui Zhang (Analytica Chimica Acta, 2025)

Cover Image - Yuanliang Duan; Wenqiong Wu; Zhipeng Huang; Lu Zhang; Chengyan Mou; Zhongmeng Zhao; Han Zhao; Jun Du; Jian Zhou; Qiang Li (Reviews in Aquaculture, 2025)
The cover image is based on the article Research on Longsnout Catfish ( Leiocassis longirostris ) Worldwide: Current Status and Future Prospects by Qiang Li et al., https://doi.org/10.1111/raq.70092 . image

Research on Longsnout Catfish ( Leiocassis longirostris ) Worldwide: Current Status and Future Prospects - Yuanliang Duan; Wenqiong Wu; Zhipeng Huang; Lu Zhang; Chengyan Mou; Zhongmeng Zhao; Han Zhao; Jun Du; Jian Zhou; Qiang Li (Reviews in Aquaculture, 2025)
The longsnout catfish ( Leiocassis longirostris ) is primarily found in the Yangtze River Basin in China. This species has been studied for more than 40 years, predominantly by researchers at the Fisheries Research Institute, Sichuan Academy of Agricultural Sciences (Sichuan Fisheries Research Institute), Southwest University, and the Institute of Hydrobiology of the Chinese Academy of Sciences. Concurrently, multiple research institutions worldwide have also conducted studies on this species, including Aberystwyth University and the University of Copenhagen in Europe, the University of Hawaii and the University of Prince Edward Island in North America, Korea Maritime and Ocean University and the ICAR National Bureau of Fish Genetic Resources in Asia, and the University of Adelaide in Oceania. Most studies on L. longirostris have focused on aquaculture techniques. In this review, we consider all studies on L. longirostris from 1974 to 2023, providing a detailed analysis of the current research status regarding its aquaculture, physiological characteristics, germplasm resources, new variety development, and deep processing. We also speculated on potential future research directions. In summary, this review establishes a solid foundation for future scientific research and aquaculture production of the species, which may promote the further development of new varieties and value‐added products derived from L. longirostris .

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Antithrombotic macrocyclic sesquiterpene pyridine alkaloids from Tripterygium hypoglaucum - Qiong Jin; Jia-Shan Shen; Xian-Run Wu; Hui-Zhen Peng; Zi-Hao Fu; Li-Qiang Chen; Yun-Li Zhao; Min Ye; Xiao-Dong Luo (Phytochemistry, 2025)

The adsorption capacity and genetic mechanism analysis of Yarrowia phangngaensis for multiple heavy metals - Wenqi Xiao; Shuyi Chen; Maojie Zhao; Dan Wen; Lianxin Peng; Liang Zou; Jialiang Han; Qiang Li (Journal of Hazardous Materials, 2025)

Spatial-temporal evolution pattern, driving mechanism and prediction of dietary sustainability in China - Rui Zhao; Xia Li; Qiang Ren; Zhenci Xu; Fengting Li (Journal of Cleaner Production, 2025)

Study on expansion methods of the DC flow for transferring the temperature-distributed refrigeration power - Qiang Cao; Pengcheng Wang; Zhiping Wang; Yuji Chen; Lichun Ge; Peng Li; Qinyu Zhao; Bo Wang; Zhihua Gan (International Journal of Refrigeration, 2025)

Additive interaction of maternal early pregnancy exposure to particulate matter and residential greenness on congenital heart disease in the Offspring: Mediation of DNA methylation in placental tissue - Honglu Zhang; Lei Pan; Chengjie Pan; Zhao Ma; Hongyue Sun; Zinuo Wang; Wei Gao; Yiqing Wang; Weiqin Li; Ying Chang; Wen Li; Wei Zhang; et al. (International Journal of Hygiene and Environmental Health, 2025)

CO2 metabolism and energy acquisition mechanisms of Rhodococcus ruber lz1 under autotrophic conditions - Qiqi Zhao; Guobao Zhang; Huijie Liu; Xinyu Gao; Lingyi Hou; Qiang Li (International Biodeterioration & Biodegradation, 2025)

Ni nanoparticles inlaid in amorphous silicon nitride-derived nickel phyllosilicate: A highly stable and active catalyst for ammonia decomposition - Han Yang; Jing Li; Qiang Chang; Qun-chao Zhao; Meng-na Zhang; Huan-jiang Wang; Cheng-hua Zhang; Fei Wang; Xiao-dong Wen (Fuel, 2025)

SiO2 particles induce pulmonary fibrosis by modulating NLRP3 through the ROS/Keap1/Nrf2 signaling pathway in rats - Shuang Li; Wei-Lei Gong; Lin Liu; Bo Shao; Shun-Li Jiang; Huan Li; Ye Song; Gui-Zhi Han; Zhao-Qiang Zhang (Food and Chemical Toxicology, 2025)

Taxonomic and functional responses of benthic macroinvertebrates to wastewater effluents in the receiving river of ecologically vulnerable karst areas in Southwest China - Rui Nie; Xuming Xu; Peijie Xu; Yisi Zhuge; Tong Zheng; Xiao Yu; Rui Yao; Hongwu Tan; Guoqiang Li; Xiaohui Zhao; Qiang Du (Environmental Research, 2025)

A novel multi-dimensional viscoelastic mitigation device: Shake table tests and numerical assessment of precast concrete sandwich wall panel structure - Jia-Xuan He; Zhao-Dong Xu; Zhong-Wei Hu; Lian-Yu Zhang; Qiang-Qiang Li; Yao-Rong Dong; Gabriele Milani (Engineering Structures, 2025)

De-aggregation of sonosensitizers enhances bactericidal activity in sonodynamic therapy of deep-seated bacterial osteomyelitis - Gang Zhao; Qiang Yu; Ming Li; Guanghua Lu; Hanqing Li; Li Wei; Jiong Zhang; Shen Wang; Min Lu (Chemical Engineering Journal, 2025)

Acetyl alkannin, a Shikonin monomer, inhibits the ATM/DDR pathway by targeting ATM and sensitizes cisplatin in solid tumors - Xinwen Xu; Jianyi Gu; Peiwen Yang; Lifang Huang; Na Zhao; Jingjing Tang; Zifeng Liang; Qiang Li; Shunqian Wen; Jianwei Jiang; Qing Zhang (Chemico-Biological Interactions, 2025)

Laminaria Japonica hydrolysate as a novel biostimulant for enhancing DHA accumulation in Aurantiochytrium limacinum - Jia-Xue Lin; Ying Wang; Shao-Geng Zhao; Bei-Chen Huang; Yue Zhang; Zhi-Qiang Wang; Sheng-Jie Li; Qian Liu; Yan Ma; Jing-Run Ye; Hai-Ying Wang; Zhi-Peng Wang (World Journal of Microbiology and Biotechnology, 2025)

Interpretable drug-target affinity prediction based on pre-trained models’ output as embeddings and based on structure-aware cross-attention for feature fusion - Fang Zheng; Juanjuan Zhao; Zihang Yuan; Yuanchen Gao; Yafeng Li; Yaheng Li; Yan Geng; Yan Qiang (Molecular Diversity, 2025)

Characterizing the HLA region’s genetic architecture through local heritability and correlation analyses across complex traits in diverse ancestries - Menghan Wei; Yunjia Liu; Yunqi Huang; Ana Vazquez; Xing Zhao; Miaoxin Li; Pak-Chung Sham; Hongsheng Gui; Qiang Wang (Human Genetics, 2025)

Assessment of Soil Organic and Inorganic Carbon Stocks in Coastal Salt Marshes of China: Key Mechanisms Elucidated - Lele Wu; Zhaoliang Song; Zhineng Xiao; Xinyu Zhang; Lukas Van Zwieten; Laodong Guo; Zimin Li; Xiaomin Yang; Xiangwei Zhao; Yidong Wang; Ding He; Weiqi Wang; et al. (Global Change Biology, 2025)
Coastal salt marsh ecosystems are among the most important blue carbon (C) sinks. However, due to disparate data sources, limited sample sizes, and inconsistent methodologies, large variations exist in blue C stock estimation. Furthermore, studies focus on soil organic carbon (SOC), with minimal attention given to soil inorganic carbon (SIC). We conducted an intensive field survey across 114 sites along approximately 5000 km of China's coastline, investigating all C stock sectors associated with Phragmites australis , Spartina alterniflora , Suaeda salsa , and mudflats to better explore the biogeographical patterns and drivers of SOC and SIC and to estimate regional and national C pools. The results revealed significant spatial heterogeneity in SOC and SIC densities in the top 100 cm of soil, ranging from 20.89 to 246.95 Mg ha −1 and 0 to 249.33 Mg ha −1 , respectively. These densities varied as a function of wetland location, vegetation type, climatic zone, and soil depth. The SOC and SIC content were jointly dependent on soil properties, climatic factors, and vegetation types. Soil available silicon was the most important environmental variable controlling both SOC and SIC. Climatic factors and vegetation types mainly controlled SOC and SIC through their interaction with soil properties. Increased vegetation productivity increased the SOC pool but decreased the SIC pool. Therefore, vegetation restoration in coastal wetlands should target suitable areas, such as soil pH

Source analysis of soil selenium and evaluation of soil environmental quality and safety in the eastern area of Zichuan District, Shandong Province - Jia-Wen Cui; Li-Yuan Yang; Jie-Rui Dai; Xi-Qiang Zhao; Jia-Liang Li (Environmental Monitoring and Assessment, 2025)

Influence of Geometric Effects on Dynamic Stall in Darrieus-Type Vertical-Axis Wind Turbines for Offshore Renewable Applications - Qiang Zhang; Weipao Miao; Kaicheng Zhao; Chun Li; Linsen Chang; Minnan Yue; Zifei Xu (Journal of Marine Science and Engineering, 2025)
The offshore implementation of vertical-axis wind turbines (VAWTs) presents a promising new paradigm for advancing marine wind energy utilization, owing to their omnidirectional wind acceptance, compact structural design, and potential for lower maintenance costs. However, VAWTs still face major aerodynamic challenges, particularly due to the pitching motion, where the angle of attack varies cyclically with the blade azimuth. This leads to strong unsteady effects and susceptibility to dynamic stalls, which significantly degrade aerodynamic performance. To address these unresolved issues, this study conducts a comprehensive investigation into the dynamic stall behavior and wake vortex evolution induced by Darrieus-type pitching motion (DPM). Quasi-three-dimensional CFD simulations are performed to explore how variations in blade geometry influence aerodynamic responses under unsteady DPM conditions. To efficiently analyze geometric sensitivity, a surrogate model based on a radial basis function neural network is constructed, enabling fast aerodynamic predictions. Sensitivity analysis identifies the curvature near the maximum thickness and the deflection angle of the trailing edge as the most influential geometric parameters affecting lift and stall behavior, while the blade thickness is shown to strongly impact the moment coefficient. These insights emphasize the pivotal role of blade shape optimization in enhancing aerodynamic performance under inherently unsteady VAWT operating conditions.

Corrigendum: Integrated transcriptomic and metabolomic analyses identify key factors in the vitellogenesis of juvenile Sichuan bream (Sinibrama taeniatus) - Zhe Zhao; Qiang Zhao; Haoyu Wang; Lan Wei; Siya Wang; Shilin Li; Dengyue Yuan; Zhijian Wang (Frontiers in Marine Science, 2025)

Impact of different green manure crops or fallow on yield and quality of a Chinese cabbage - Cai Zhao; Li Jin; Hong Fan; Yu Jia; Zhilong Fan; Wen Yin; Aizhong Yu; Falong Hu; Wei He; Qiang Chai (Plant and Soil, 2025)

Black soldier fly larvae mediate Zinc and Chromium transformation through the ZnuCBA and citric acid cycle system - Bo Deng; Zihe Ren; Qiang Li; Zhijian Zhang; Chao Xu; Panpan Wang; Heping Zhao; Qiaoxia Yuan (Water Research, 2025)

Hydrodynamic response of an integrated structure with monopile-type offshore wind turbine and UHMWPE cage affected by wave and current - Haisheng Zhao; Yiyang Hu; Qiang Shi; Wei Shi; Xin Li (Ocean Engineering, 2025)

A new approach to color correction and equalization for generating mars global color image mosaics from Tianwen-1 MoRIC images - Xin Ren; Xiaoxia Zhang; Wangli Chen; Wei Yan; Xingguo Zeng; Xu Tan; Xingye Gao; Qiang Fu; Lin Guo; Qing Zhang; Zhaopeng Chen; Guobin Yu; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Environment-friendly dual-mode immunoassay based on the inner filter effect of polydopamine-polyethylenimine copolymer nanoparticles for the highly sensitive detection of norfloxacin - Zizhe Li; Liang Luo; Chaochao Chen; Qiang Li; Qiyuan Zhao; Ghulam Mujtaba Mari; Chen Xing; Xuefeng Xia; Jianzhong Shen; XueZhi Yu; Zhanhui Wang; Yantong Pan (Food Chemistry, 2025)

Probabilistic vulnerability evaluation of buildings under landslide runout impacts considering the 3D dynamic interaction processes - Xiaoping Sun; Peng Zeng; Tianbin Li; Qiang Xu; Hua Zhao; Xin Wang (Engineering Geology, 2025)

Entropy engineering to modulate oxygen adsorption of bi-functional perovskite-type catalysts toward intermediate-temperature solid oxide cells - Chao Huang; Zixuan Tang; Yingnan Dou; Liping Sun; Qiang Li; Lihua Huo; Hui Zhao (Chemical Engineering Journal, 2025)

Humidity-adaptive microcrystalline cellulose triboelectric composite film with engineered microstructures for sensing and energy harvesting - Min Mao; Qiangli Zhao; Jiahao Kang; Qiang Mu; Jie Tao; Xiaoliang Zhao; Xinhai He; Jianwei Li (Chemical Engineering Journal, 2025)

Designing ultrathin single and multilayered Ti3C2TX MXene as photocatalysts for enhanced acetaminophen degradation in Photo-Fenton-like reactions - Qiang Li; Tianhui Zhao; Junjie Zhu; Muyuan Ma; Guoqing Hou; Mengyuan Fang; Yu Shen; Xiaoli Zhao; Zhi Tang; Fengchang Wu (Chemical Engineering Journal, 2025)

Clinical characteristics and co-infection analysis of influenza a virus in pediatric respiratory infections: a study based on tNGS technology - Chunyun Fu; Qiang Huang; Jiangyang Zhao; Lishai Mo; Wenting Tang; Junming Lu; Yili Zhang; Xiangjun Lu; Ya Huang; Yanhua Feng; Xuehua Hu; Yanqing Tang; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Oxygen/sulfate radicals-generating CaS2O8 nanosonosensitizers induce PANoptosis and calcium overload for enhanced peritoneal metastasis immunotherapy - Qiang Wang; Yingfei Wen; Bo Bi; Kuan Li; Yuanqi Liu; Binbin Li; Shangbo Zhou; Zihang Li; Jiaqi Xu; Miaojuan Qiu; You Li; Meiying Wu; et al. (Science Bulletin, 2025)

Climate forcing of turbidite system on the northern South China Sea margin during the Late Quaternary - Xuan Zhao; Wei Li; Christopher J. Stevenson; Qiang Zhang; Shuang Li; Lingyun Wu; Zhiyuan Cai; Xiting Liu; Wenhuan Zhan (Sedimentary Geology, 2025)

A combined DFT and experimental study for the synergistic removal of NO and toluene on FeVO4/TiO2 catalysts: Insights from redox ability and charge transfer - Yang-Wen Wu; Zheng-Long Wu; Yi-Fei Yu; Xu Su; Xin-Yue Zhou; Bing Zhang; Li Zhao; Jing-Tao Li; Qiang Lu (Process Safety and Environmental Protection, 2025)

MdNAC2 enhances K+ deficiency stress tolerance by maintaining K+ homeostasis in apple - Jianyu Li; Yaqi Cui; Tianchao Wang; Caihong Wang; Xiaodong Zheng; Zhijuan Sun; Qiang Zhao; Changqing Ma; Yi Lyu; Yike Tian (Plant Science, 2025)

Reduced graphene oxide modified nickel foam-based quaternary layered double hydroxides nanosheets as catalysts for vaporized hydrogen peroxide decomposition - Haiyun Li; Lei Zhao; Enyuan Hu; Yiran Shang; Qiang Liu; Jinhui Wu; Zongxing Zhang; Ying Yi; Cheng Deng; Mengfu Zhu (Journal of Hazardous Materials, 2025)

Experimental evidence for viral impact on microbial community, nitrification, and denitrification in an agriculture soil - Hu Li; Sha Zhao; Meng-Ke Gao; Yanyan Zhou; Bo Xu; Le-Yang Yang; Xiao-Ru Yang; Jian-Qiang Su (Journal of Hazardous Materials, 2025)

From soil to the intestinal tract: The key role of beneficial elements and probiotics in promoting health and longevity - Wen Zhang; Shimao Wu; Eun Hea Jho; Junhao Chen; Qiang Liu; Jian Hu; Guanlin Li; Xin Zhao; Mingming Sun (Journal of Environmental Management, 2025)

Bimetallic MOFs@PAN ordered nanofibrous membranes with antibacterial activity for air filtration and personal protective equipment - Xiao Cheng; Enyuan Hu; Haiyun Li; Qiang Liu; Lei Zhao; Cheng Deng; Yanhua Fang; Mengfu Zhu (Journal of Environmental Chemical Engineering, 2025)

Rigid polyelectrolyte multilayer membrane with ultrahigh permeance and excellent dye/salt separation performance - Na Zhang; Fanglu Fu; Wen Bo; Hussein Baqiah; Li Zhao; Wenbo Lu; Yadi Cai; Jiahui Tian; Tingting Yan; Saisai Li; Shuyun Zheng; Qiang Li (Journal of Environmental Chemical Engineering, 2025)

Minerals change the equilibrium condition and water transformation ratio of methane hydrates - Jianzhong Zhao; Yijie Li; Li Huang; Zhengcai Zhang; Qiang Chen; Jianye Sun; Xiluo Hao; Qiang Gao; Jiapeng Jin; Renat B. Shakirov; Nengyou Wu (Fuel, 2025)

Rapid absolute quantification of glucose and fructose isomers in honey using a boronic acid-based reactive matrix by MALDI-TOF/TOF tandem mass spectrometry - Zhang-Na Qin; Jia-Min Chen; Jia-Wei Li; Zhen-Peng Zhen; Qi-Zhao Chen; Zhi-Qiang Zhang; Gui-Hua Wang; Yu-Feng Gao (Food Chemistry, 2025)

Flavonoids from Cerasus humilis seed coat alleviate constipation in mice: Role of AQP3/4 and c-Kit/SCF signaling pathways - Xiao Qiang; Jinjiang Zhao; Zongshuo Li; Weidong Li (Food Bioscience, 2025)

Exploration of rapid testing methods for unsaturated soils - Xu Li; Yu-Xin Zhao; A-Qiang Liu (Engineering Geology, 2025)

Titanium isotopes as a tracer of eclogite in the mantle sources of continental intraplate basalts - Jian Zhao; Xiao-Jun Wang; Xin-Miao Zhao; Jian-Qiang Liu; Gang Zeng; Chun-Xia Yi; Bing Liu; Jin Li; Xiang-Kun Zhu; Li-Hui Chen (Earth and Planetary Science Letters, 2025)

Correction to: Comparison of Long‑Term Outcomes in Ruptured Diffuse Brain Arteriovenous Malformations Between Interventional Therapy and Conservative Management - Changyu Lu; Heze Han; Li Ma; Ruinan Li; Zhipeng Li; Haibin Zhang; Kexin Yuan; Yukun Zhang; Anqi Li; Ke Wang; Yang Zhao; Weitao Jin; et al. (Translational Stroke Research, 2025)

Epidemiological and clinical profiles of respiratory syncytial virus infections in hospitalized children: a retrospective cohort study utilizing targeted next-generation sequencing - Chunyun Fu; Jialing Ruan; Lishai Mo; Jiangyang Zhao; Junming Lu; Ya Huang; Xuehua Hu; Qiang Huang; Yanhua Feng; Wenting Tang; Ning Zhu; Cuihong Lu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Influence of prenatal exposure to per- and polyfluoroalkyl substances under gestational diabetes mellitus on birth and child growth - Qiang Li; Yabin Hu; Pengpeng Wang; Liyi Zhang; Hang Wang; Yuyan Gui; Yaqi Xu; Yue Zhao; Weizhao Cao; Minghao Wang; Huijing Shi; Yingya Zhao; et al. (Environmental Chemistry Letters, 2025)

Unraveling the Spatio-Temporal Pattern of Mine Water Accidents in China - Wenjie Sun; Wenjie Li; Qiang Wu; Suqi Zhao; Wen Liu; Chenxu Wang (Mine Water and the Environment, 2025)

Three-dimensional Copula-based Assessment of Meteorological Drought Characteristics and Driving Mechanisms in Haihe River Basin, China - Jianwen Xue; Qiang Zhao; Yuhu Zhang; Yali Chen; Xuan Wang; Xiangzhou Dou; Xiumei Li (Chinese Geographical Science, 2025)

Nitrogen-rich roots regulate microbial- and plant-derived carbon in alkali-saline soil under land-use conversions in the Songnen Plain - Juan Hu; Yueqi Lv; Siqin Zhao; Yingxin Huang; Qiang Li; Daowei Zhou (Soil and Tillage Research, 2025)

Magnetic proxy in the Heqing drill core revealed Indian Summer Monsoon variations linked with AMOC at the orbital -scale during the late Pleistocene - Xinwen Xu; Xiaoke Qiang; Xubin Li; Haijun Qiu; Hui Zhao; Chaofeng Fu; Ziyi Yang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Decoupling soil pH and geography: Universal drivers of cadmium bioavailability in rice across terrains - Qiang Liu; Shuyue Liu; Danling Wang; Dawei Sun; Yun Ge; Songwei Zhang; Guanlin Li; Eun Hea Jho; Jin Chul Joo; Xin Zhao; Mao Ye; Jian Hu (Journal of Environmental Management, 2025)

No tillage with straw mulching enhanced radiation use efficiency of wheat via optimizing canopy radiation interception and photosynthetic properties - Pan Li; Wen Yin; Lianhao Zhao; Pingxing Wan; Zhilong Fan; Falong Hu; Yunyou Nan; Yali Sun; Hong Fan; Wei He; Qiang Chai (Field Crops Research, 2025)

Regional pollution and diet drive organohalogen contaminant accumulation in mangrove-settled spiders (Nephila pilipes) - Qiang Xie; Lihua Yang; Lvyan Tan; Fenglong Jia; Shuang Zhao; Yuhai Lu; Yuping Wu; Li Lin; Tiangang Luan (Environmental Pollution, 2025)

Enhanced activation of peroxymonosulfate by nickel sulfide with sulfur vacancies for ultrafast organic pollutants degradation: Roles of active sites and mechanism - Cai-Wu Luo; Liang Jiang; Xian-Feng Li; Qiang-Mao Wan; Tian-Jiao Jiang; Sen-Ping Mao; Jing-Qian Guo; Run-Ze Zhao; Chao Xie (Environmental Pollution, 2025)

Antibacterial conductive hydrogels with freeze-directed microstructures reinforced by polyaniline-encapsulated bacterial cellulose for flexible sensors - Feihong Hu; Dehai Yu; Baoting Dong; Xi Gong; Zhiyang Li; Rui Zhao; Qiang Wang; Guodong Li; Huili Wang; Wenxia Liu; Fengshan Zhang; Zhixin Chen; et al. (Chemical Engineering Journal, 2025)

Cation effect on dual-function amine-based electrolytes for CO2 capture and electroreduction - Qiang Li; Yuhang Ding; Teng Wang; Zhuo Xiong; Junying Zhang; Yongchun Zhao (Chemical Engineering Journal, 2025)

Fully recyclable flame-retardant PLA composites with balanced performance based on a phosphorus/nitrogen-containing zwitterion - Qiang Zhang; Xing Cao; Yan-Peng Ni; Li-Ping Zhang; Zhao Ding; Ying-Jun Xu; Yu-Zhong Wang (Chemical Engineering Journal, 2025)

Covalent functionalization of Wnt pathway inhibitor with reduced graphene oxide-polyethylene glycol to inhibit urethral scar hyperplasia - Danyang Li; Zhidong Ma; Kai Wang; Bingjie Hao; Xi Yang; Weixin Zhao; Jie Liu; Yu Zheng; Wenyao Li; Qiang Fu; Kaile Zhang (Chemical Engineering Journal, 2025)

Bacterial cellulose-based Pickering emulsions reinforced with silver and silica nanoparticles for advanced antibacterial and hydrophobic food packaging solutions - Qimin Chen; Fan Yang; Yalong Hou; Zhiyang Li; Di Yuan; Chao Liu; Feihong Hu; Rui Zhao; Huili Wang; Wenxia Liu; Fengshan Zhang; Qiang Wang; et al. (Carbohydrate Polymers, 2025)

Quantifying the impacts of climate change and human activities on vegetation in ecologically fragile regions: a case study of Northern China - Xiangzhou Dou; Xiumei Li; Guoqing Sang; Ping Yang; Yuhu Zhang; Jianing Wang; Zhicheng Zhong; Feng Lin; Qiang Zhao (Theoretical and Applied Climatology, 2025)

Prevalence of malnutrition among adult inpatients in China: a nationwide cross-sectional study - Yan Liu; Chunhua Song; Xue Wang; Xianghua Ma; Pianhong Zhang; Gaiyun Chen; Zhenqian Cheng; Juying Liu; Ying Yao; Wenjun Ma; Zengning Li; Ping Sun; et al. (Science China Life Sciences, 2025)

The effects of simulated Martian regolith on Arabidopsis growth, circadian rhythms and rhizosphere microbiota - Yuanyuan Zhao; Rujia Luo; Haoran Zhang; Li Yuan; Xiaoting Fang; Xinjie Tong; Yongyu Qian; Zengxuan Zhou; Yilin Yang; Xiaojia Zeng; Jian-Feng Li; Xiaodong Xu; et al. (Plant and Soil, 2025)

Mechanisms of microbial life strategy regulate the temperature sensitivity of soil respiration under winter warming conditions - Renjie Hou; Haihong Zhao; Qiang Fu; Tianxiao Li; Liuwei Wang; Wei Huang; Bingyu Zhu; Yuxuan Wang; Yunjia Hong (Applied Soil Ecology, 2025)

Multiobjective optimization of daily scale irrigation schedules for rice in irrigation districts considering joint uncertainties in water supply and demand - Mo Li; Xu Zhang; Yingshan Chen; Yaowen Xu; Rentao Li; Li Zhao; Qiang Fu (Computers and Electronics in Agriculture, 2025)

Porcine antibodies reveal novel non-neutralizing universal epitopes on FMDV and their overlaps with neutralization sites - Ying Sun; Shenglin Huang; Fengjuan Li; Shulun Huang; Pinghua Li; Qiongqiong Zhao; Tao Wang; Huifang Bao; Yuanfang Fu; Pu Sun; Xingwen Bai; Hong Yuan; et al. (Veterinary Microbiology, 2025)

A critical life cycle assessment of present and potential rare earth circularity routes from permanent magnets - Qian-Qian Wang; Lu Wang; Shen Zhao; Fu-Ping Li; Wei-Qiang Chen; Peng Wang (Resources, Conservation and Recycling, 2025)

Loess-paleosol sedimentological characteristics in northern Iran since the last interglacial and their paleoenvironmental significance - Dongxue Li; Hui Zhao; Haichao Xie; Aijun Sun; Farhad Khormali; Xin Wang; Qiang Wang; Hamid Lahijani; Hassan Fazeli Nashli; Yujie Xu; Fahu Chen (Quaternary Science Reviews, 2025)

Associations of prenatal organophosphate esters exposure with risk of eczema in early childhood, mediating role of gut microbiota - Yuhan Zhou; Liyi Zhang; Ling Lin; Yang Liu; Qiang Li; Yingya Zhao; Yunhui Zhang (Journal of Hazardous Materials, 2025)

The promotional effect of MoO3 on the CeO2/TiO2 catalyst for simultaneous removal of NO and toluene: From the insights of experimental and DFT studies - Zhuang Hu; Yi-fei Yu; Hai-yuan Zhao; Zheng-long Wu; Rong Guo; Jia-le Zhou; Xin-yue Zhou; Bing Zhang; Yang-wen Wu; Li Zhao; Qiang Lu (Journal of Environmental Chemical Engineering, 2025)

Establishing a database of volatile metabolites in whole wheat (Triticum aestivum L.) flour provides novel insights into quality breeding - Peimin Zhao; Zhanghan Pang; Ting Chen; Qianqian Li; Jianhao Wei; Yize Meng; Bo Yang; Zhen Jia; Jianming Yu; Yudong Liao; Qiang Li (Food Research International, 2025)

Amylopectin-enhanced MXene/gallium hydrogels: High-performance flexible conductive materials for multifunctional sensing, EMI shielding, and energy storage applications - Feihong Hu; Dehai Yu; Xi Gong; Zhiyang Li; Rui Zhao; Qiang Wang; Fengshan Zhang; Guodong Li; Huili Wang; Wenxia Liu; Yingjie Zhao; Huihui Li (Chemical Engineering Journal, 2025)

A sandwich-structured nanofibrous textile with moisture wicking for passive radiative cooling and heating - Xin Meng; Muxing Zhang; Qi Zhao; Qiang Li; Xuemei Chen (Chemical Engineering Journal, 2025)

The structures of two polysaccharides from Fructus Corni and their protective effect on insulin resistance - Guang-Yuan Ma; Lu-Kuan Hou; Jia-Hui Guo; Jing-Chun Sun; Qiuna Nong; Yu-Fan Wang; Sheng-Wei Hu; Wen-Jing Zhao; Jin Tan; Xiao-Feng Liu; Yuan Guo; Bo-Jing Zhang; et al. (Carbohydrate Polymers, 2025)

Recurrence of Cerebral Arteriovenous Malformation Following Complete Obliteration Through Endovascular Embolization - Qiang Hao; Haibin Zhang; Heze Han; Hengwei Jin; Li Ma; Ruinan Li; Zhipeng Li; Anqi Li; Kexin Yuan; Qinghui Zhu; Ke Wang; Runting Li; et al. (Translational Stroke Research, 2025)

Floral trait dissimilarity indirectly decreases heterospecific pollen transfer through pollinator sharing in a subalpine meadow - Chunyan Zhao; Suyan Ba; Tao Zhang; Yage Li; Qiang Fang (Oecologia, 2025)

Identification, distribution, and mechanisms of large landslides in the upper reaches of Jinsha River - Weihua Zhao; Fengjiao Wang; Qiang Xu; Jianjun Zhao; Fuling Zhang; Weile Li; Xiujun Dong; Jian Yang; Decun Guo; Wantong He (Bulletin of Engineering Geology and the Environment, 2025)

Three-dimensional stability analysis and groundwater table estimation of a retrogressive shallow soil landslide: A case study of the Zhongzhai landslide in Gansu Province, China - Shiyao Jia; Qiang Xu; Wanlin Chen; Dalei Peng; Pinliang Li; Haoxing Zhao; Haoyu Li; Xiaoling Song; Hailong Chen (Bulletin of Engineering Geology and the Environment, 2025)

Effects of Water Temperature, Light Intensities and Photoperiod on the Survival and Growth of Juvenile Schizothorax irregularis and Diptychus maculates - Zhulan Nie; Huimin Hao; He Zhao; Nianhua Zhao; Li Li; Zhuang Qiang; Syeda Maira Hamid; Jie Wei (Fishes, 2025)
An experimental ecological method was used to study the effects of water temperature, photoperiod, and light intensity on the survival, feeding, and growth of juvenile Schizothorax irregularis and Diptychus maculates. The Box–Benhnken experiment was designed to predict the optimal environmental conditions for juvenile growth. With the maximum specific growth rate at 15 °C and a photoperiod of LD16:8, the results demonstrated that the juvenile S. irregularis had a survival rate of over 85% in water temperatures ranging from 5 to 25 °C. A daily light duration of 15.86 h and a light intensity of 1166.28 lx, with the water temperature maintained at 10.45 °C, allowed the juvenile S. irregularis fish to attain the optimal circumstances for growth and survival. At water temperatures below 25 °C, the juvenile D. maculates exhibited maximum specific growth rates at 10 °C and LD16:8 light period. Additionally, as the light intensity reached 1000 lx, the juvenile fish grew better. Furthermore, the juvenile D. maculates fish achieved theoretically optimal survival and growth circumstances when the water temperature was maintained at 10.87 °C with a light period of 15.0.5 h per day and a light intensity of 1474.68x. The results showed that both fish species may be raised in captivity in highland regions, but precise control over water temperature is required.

Inversion of Rayleigh Surface Wave Dispersion Curves Based on Deep Learning - Bing-kai Zhao; Yan-li Ding; Jia-qiang Song; Pei-yan He; Shao-yuan Bai (Applied Geophysics, 2025)

Recombinant probiotic Escherichia coli delivers the polymeric protein of swine influenza virus for protection - Jin-Mei Sun; Wen-Qiang Zhang; Yan-Jin Li; Tian-Kui Guo; Rong-Rong Zhang; Yong-Lei Yang; Ying Zhao; Ling-Jiao Yu; Chun-Wei Shi; Gui-Lian Yang; Hai-Bin Huang; Yan-Long Jiang; et al. (Veterinary Microbiology, 2025)

Pre-industrial Common Era temperature fluctuations in South China inferred based upon bacterial tetraether lipids from Lake Poyang - Rui Miao; Hong Yang; Qin Leng; Yuwei Chen; Shangbin Xiao; Xiaoke Qiang; Xiangzhong Li; Yuan Yao; Zenghao Zhao; Hongxuan Lu; Zhonghui Liu; Huanye Wang; et al. (Quaternary Science Reviews, 2025)

Genomic analysis of Vreelandella sp. F11 reveals its role in alginate utilization - Xin-Xiao Qu; Yu-Qi Zhang; Fei-Yu He; Xi-Ying Zhang; Peng Wang; Fei Xu; Yu-Qiang Zhang; Long-Sheng Zhao; Ping-Yi Li; Fang Zhao (Marine Genomics, 2025)

Preparation and property evolution mechanism of high sludge-content ceramsite with blast furnace slag and red mud - Wenhao Zhang; Qiang Zhao; Shuo Peng; Mingfu Chen; Qibang Tong; Xin Zhou; Lifang Jiang; Yan Li; Yong Guo (Journal of Water Process Engineering, 2025)

Biosafe Cu-MOF loaded chitosan/gelatin-based multifunctional packaging film for monitoring shrimp freshness - Peini Li; Yiqing Deng; Wangcai Zou; Zhenqiao Ma; Xiandi Yang; Qiang Zhao (Food Hydrocolloids, 2025)

Revealing terrestrial uplift in large-scale land creation areas on the Loess Plateau using InSAR time series data - Qiang Xu; Chuanhao Pu; Xiaochen Wang; Xiang Gong; Zhigang Li; Kuanyao Zhao; Wanlin Chen; Huajin Li; Pinglang Kou (Engineering Geology, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Direct dehydrogenation condensation of ethanol to ethyl acetate with superior selectivity over acid-base balanced CuZnZrO solid solution catalyst - Siqi Li; Yuda Zhang; Qiang Guo; Yafei Liang; Yuji Qi; Xiaowei Zhao; Yehong Wang; Feng Wang (Chemical Engineering Journal, 2025)

Multifunctional Modification of the Buried Interface in all-inorganic perovskite solar cells - Linde Li; Yuanyuan Zhao; Qing Su; Qiyao Guo; Jialong Duan; Jie Dou; Liqing Sun; Qiang Zhang; Qunwei Tang (Chemical Engineering Journal, 2025)

Enhanced low-temperature activity for CO2 methanation over N-doped NiMn-LDO - Dilong Qiang; Tianhong Mei; Yue Liu; Hongyang Jin; Zhaolian Ye; Zhen Li; Songjian Zhao (Chemical Engineering Journal, 2025)

Revealing the regulation mechanism of carbon dots on Ni(OH)2 for optimizing methanol electrooxidation activity - Man Zhao; Liwu Qiang; Meng Bai; He Xiao; Li Zhang; Junming Zhang; Tianjun Hu; Baoliang Lv; Shengxiang Wang; Jianfeng Jia (Chemical Engineering Journal, 2025)

Structure characteristics of a novel pectic polysaccharide from Fructus Corni and its protective effect on alcoholic fatty liver - Hong-Xin Bai; Yu-Xuan Gao; Shuyao Wang; Guang-Yuan Ma; Wenjing Zhao; Xiao-Qiang Li; Yu-Fan Wang; Qiu-Na Nong; Yu-Bo Wang; Jin Tan; Qimei Duan; Wei Cao (Carbohydrate Polymers, 2025)

Discovery, optimization and biological evaluation of chromone derivatives as novel BRD4 inhibitors - Zhao-Tong Jia; You Li; Wei Shi; Jian-Qiang Qian; Ya-Yu Xu; Hai-Ran Fan; Xiao-Long Hu; Hao Wang (Medicinal Chemistry Research, 2025)

Conductivity characteristics of magmatic rock intrusions contained in metamorphic rock strata in Mupi Highway Tunnel - Bin Li; Qiang Xu; Jianhua Yu; Qiang Cheng; Chongde Feng; Hu Zhao; Tianxiang Liu; Xubo Yang (Applied Geophysics, 2025)

Neuronal Injury after Ischemic Stroke: Mechanisms of Crosstalk Involving Necroptosis - Xuanning Zhang; Hongyu Li; Yaowei Zhao; Tingting Zhao; Zhihao Wang; Qiang Tang (Journal of Molecular Neuroscience, 2025)

Disaster losses in Shanghai decreased under rapid urbanization: Evidence from 1980 to 2019 - Li Li; Jiahong Wen; Yong Shi; Yuxi Chen; Zhongchao Shi; Yanjuan Wu; Jianli Liu; Tongfei Tian; Jianping Yan; Luna Zhao; Qiang Dong (Urban Climate, 2025)

Freeze-thaw cycles affect hydrothermal and heavy metal transport mechanisms in porous media: Closed and transient flooded system conditions - Tianxiao Li; Chengye Zhao; Qiang Fu; Fanxiang Meng; Dong Liu; Mo Li (Science of The Total Environment, 2025)

Phenylhydrazine-based hyper-cross-linked polymers as adsorbents for reversible capture of iodine - Jun Li; Qiang Zhou; Lihan Yue; Dan Wang; Liqiu Sun; Jianjun Wang; Xiaohong Zhang; Liying Qi; Zhichun Shi; Ming Zhao (Journal of Water Process Engineering, 2025)

Efficient removal of cationic malachite green using co-pyrolyzed corn straw biochar-montmorillonite composites - Xiaodong Yang; Zhiyong Hou; Xuefei Yang; Minghui Li; Yuanxia Guo; Kai Wang; Shuaiqi Luo; Jin Zhao; Pengkai Sun; Qiang Yang; Rui Chen; Yan Yan; et al. (Journal of Environmental Management, 2025)

Enhanced study of ozone advanced oxidation for P-nitrophenol degradation in a three-phase fluidized bed using an eulerian multiphase flow model - Xin Zhou; Mingfu Chen; Shuo Peng; Qiang Zhao; Qibang Tong; Wenhao Zhang; Lifang Jiang; Yan Li; Yong Guo (Journal of Environmental Chemical Engineering, 2025)

Light iron isotopes in high-silica granites record fluid evolution in magmatic-hydrothermal systems - Qi-Wei Li; Qiang Wang; Lin Ma; Andrew C. Kerr; Jing-Jing Fan; Jun-Hong Zhao; Hai-Ou Gu; Wei Wang; Zhi-Kun Su (Geochimica et Cosmochimica Acta, 2025)

Exploration of the impact of different drying methods on the quality of Gastrodia elata: A study based on drying kinetics and multidimensional quality evaluation - Ming-xuan Li; Bin Wang; Yu Li; Xin-ru Nie; Jing Mao; Qiang Guo; Nuo Xu; Rao Fu; Zhi-jun Guo; Xiao-li Zhao; Zhen-hua Bian; Tu-lin Lu; et al. (Food Chemistry, 2025)

Material engineering of porous calcium oxide for boosting CO2 capture - Jiawei Hu; Yongjun Jiang; Qiang Gao; Yikang Zhao; Sheng Dai; Xuesong Li; Wei Wei (Chemical Engineering Journal, 2025)

Mathematical Model and Application of Overtopping Breach of Cascade earth-rock dams Considering Flood peak Enhancement Effect - Wen Qiu; Yanlong Li; Wei Zhao; Qiang Zhang; Lifeng Wen; Ye Zhang; Ting Wang (Water Resources Management, 2025)

Feasibility analysis of expanding winter rapeseed northwards in China - Junqiang Fan; Gang Yang; Junyan Wu; Yuanyuan Pu; Lijun Liu; Li Ma; Tingting Fan; Wangtian Wang; Yahong Zhang; Jianming Lei; Qiang Li; Xianfei Hou; et al. (Agricultural and Forest Meteorology, 2025)

First discovery of dinosaur tracks from the Lower Cretaceous Duoni Formation in eastern Tibet, China - Yangui Li; He Zhao; William J. Foster; Yue Yu; Lida Xing; Qiang Ye; Chuanshang Wang; Huazhou Yao (Cretaceous Research, 2025)

Classification Prediction of Hydrocephalus After Intercerebral Haemorrhage Based on Machine Learning Approach - Enwen Zhu; Zhuojun Zou; Jianxian Li; Jipan Chen; Ao Chen; Naifei Zhao; Qiang Yuan; Caicai Liu; Xin Tang (Neuroinformatics, 2025)

A study on the effects of dispersion coefficient on groundwater pollutant transport simulation - Zongjun Gao; Qiang Li; Jianguo Feng; Yao Wang; Menghan Tan; Guiyu Zhao (Environmental Monitoring and Assessment, 2025)

Sesquiterpenoids from the whole plants of Elephantopus mollis with cytotoxicity activities - Qiang Lin; Jing-Yi Du; Si-Yu Yang; Zhao-Chun Zhan; Qing Tang; Hui Sun; Jin-Lin Tan; Hai-Yue Zhao; Yao-Lan Li; Yu-Bo Zhang; Guo-Cai Wang (Natural Product Research, 2025)

Improved anaerobic digestion of food waste under ammonia stress by side-stream hydrogen domestication - Yi Wang; Haoyang Li; Keke Ding; Xueyu Zhao; Miao Liu; Linji Xu; Li Gu; Jinze Li; Lin Li; Qiang He; Jianjun Liang (Water Research, 2025)

Study on working mechanism and mechanical properties of retractable U-shaped steel gangue prevention structure - Jun Yang; Yuxuan Liu; Changjiang Li; Qiang Fu; Hongxu Song; Jianbo Cui; Jiarui Tang; Junpeng Zhao (Tunnelling and Underground Space Technology, 2025)

Tunable refractive index transparent conductive adhesives for efficient monolithic tandem solar cells - Xingliang Li; Sanlong Wang; Xiangqing Zhou; Yucheng Li; Hui Liu; Biao Shi; Qiang Sun; Ying Zhao; Xiaodan Zhang (Science Bulletin, 2025)

Fate of heavy metals and importance of influencing factors during vermicomposting - Qingmiao Zhang; Xiaoming Guo; Qiang Zhang; Ziyan Li; Tongqian Zhao (Journal of Cleaner Production, 2025)

How to develop nature-based solutions for revegetation on abandoned farmland in the Loess Plateau of China? - Xin Song; Zi-Qiang Yuan; Chao Fang; Xiang Li; Yang-Yang Zhao; Feng-Min Li; Jordi Sardans; Josep Peñuelas (Journal of Environmental Management, 2025)

Insight into the molecular structure construction and pyrolysis mechanism simulation of typical carbonaceous feedstocks for the rapid design and preparation of porous carbon-based materials - Li Zhao; Bo Yuan; Lele Gong; Hongwei Wang; Qiansong Ran; Lingyan Qin; Jiaqi Liu; Luchao Zhang; Kai Li; Guojie Liang; Li Li; Qiang Xie (Fuel, 2025)

The necessity of enhancing the human health risk assessment of 1,3,6,8-tetrabromocarbazole: Based on in vitro experiments, theoretical calculations, and model predictions - Junchao Ma; Mengxi Ren; Jiangyan He; Pengcheng Shi; Dawei Xing; Xiaochao Tang; Qiang Yang; Yunhong Song; Qiang Li; Tingting Zhao; Chao Qin; Xiaoju Chen (Environmental Pollution, 2025)

Factors affecting the different growth rates of PM2.5：Evidence from composition variation, formation mechanisms, and importance analysis of water-soluble inorganic ions with case study in northern China - Huan Li; Ting Zhang; Hui Su; Sui Xin Liu; Ying Qiang Shi; Lu Yao Wang; Dong Dong Xu; Jia Mao Zhou; Zhu Zi Zhao; Qi Yuan Wang; Steven Sai Hang Ho; Yao Qu; et al. (Atmospheric Environment, 2025)

Kv3.1 Interaction with UBR5 Is Required for Chronic Inflammatory Pain - Ying Zeng; Meng-Lan Sun; Di Liu; Yue Huang; Shan Xie; Ya-Xuan Zhao; Zi-Xuan Wu; Ya Liu; Gan Ma; Ling Xie; Yu-Tao Dang; Ling-Yun Hao; et al. (Molecular Neurobiology, 2025)

Genetic relationship analysis and fingerprint construction of some species in the genus Vanda (Orchidaceae) by interprimer binding site (iPBS) markers - Wen-Yi Yin; Xue-Qiang Cui; Qiu-Ju Zhao; Jie-Ling Deng; Chang-Yan Huang; Zi-Bin Zhang; Jia-Wei Li (Genetic Resources and Crop Evolution, 2025)

Recent advances of food safety detection by nucleic acid isothermal amplification integrated with CRISPR/Cas - Jiali Qiao; Zhiying Zhao; Yaru Li; Minghui Lu; Shuli Man; Shengying Ye; Qiang Zhang; Long Ma (Critical Reviews in Food Science and Nutrition, 2024)

Corrigendum: Coral reefs of Pakistan: a comprehensive review of anthropogenic threats, climate change, and conservation status - Ishfaq Ahmad; Pu Guo; Mei-Xia Zhao; Yu Zhong; Xiao-Yun Zheng; Shu-Qi Zhang; Jian-Wen Qiu; Qi Shi; Hong-Qiang Yan; Shi-Chen Tao; Li-Jia Xu (Frontiers in Marine Science, 2024)

Integrating remote sensing assimilation and SCE-UA to construct a grid-by-grid spatialized crop model can dramatically improve winter wheat yield estimate accuracy - Qiang Li; Maofang Gao; Sibo Duan; Guijun Yang; Zhao-Liang Li (Computers and Electronics in Agriculture, 2024)

Effects of dietary tryptophan levels on growth performance, serotonin metabolism, brain 5-HT and cannibalism activities in tiger puffer, Takifugu rubripes fingerlings - Yuliang Wei; Zhibin Zhou; Zhijun Zhang; Lili Zhao; Yanlu Li; Qiang Ma; Mengqing Liang; Houguo Xu (Aquaculture, 2024)

Optimising maize threshing process with temporal proximity soft actor-critic deep reinforcement learning algorithm - Qiang Zhang; Xuwen Fang; Xiaodi Gao; Jinsong Zhang; Xuelin Zhao; Lulu Yu; Chunsheng Yu; Deyi Zhou; Haigen Zhou; Li Zhang; Xinling Wu (Biosystems Engineering, 2024)

Biogenic amorphous FeOOH activated additional intracellular electron flow pathways for accelerating reductive dechlorination of tetrachloroethylene - Yang Yu; Ang Li; Sheng-Qiang Fan; He-Ping Zhao (Water Research, 2024)

Advancing anaerobic digestion with MnO2-modified biochar: Insights into performance and mechanisms - Yeqing Li; Jinglei Zhang; Xinran Wen; Mahmoud Mazarji; Shuo Chen; Qiang Liu; Shenggeng Zhao; Lu Feng; Gang Li; Hongjun Zhou; Junting Pan (Science of The Total Environment, 2024)

A novel biochar derived from Prunella vulgaris L. residue of Chinese herbs for eco-efficient removal of four heavy metals from water: Optimization, mechanism, assessment and recycle - Xing-yi Yang; Dong Liang; Qiang Li; Huan Chang; Zhao-qiong Chen; Xin Liu (Process Safety and Environmental Protection, 2024)

Synergistic removal of ammonia nitrogen and hexavalent chromium by the hybrid-system of Acinetobacter baumannii AL-6 and original walnut shell biochar in solution: Mechanism and application - Yang Yu; Qiang An; Zheng Li; Bin Zhao (Journal of Environmental Chemical Engineering, 2024)

Ferrihydrite optimizing Feammox inoculum to enhance ammonia removal from concentrate wastewater through continuous upflow anaerobic sludge blanket (UASB) - Linji Xu; Lin Li; Jianxi Liu; Xingzu Wang; Yanping Zhao; Jujiao Zhao; Li Gu; Qiang He; Xinzhu Wang; Jinhua Zhang (Journal of Environmental Chemical Engineering, 2024)

Electrostatic self-assembly of hydrotalcite-based g-C3N4 composites for adsorption and photocatalytic degradation of aqueous norfloxacin - Xiaodong Yang; Minghui Li; Zhiyong Hou; Xuefei Yang; Yuanxia Guo; Shuaiqi Luo; Jin Zhao; Kai Wang; Pengkai Sun; Qiang Yang; Rui Chen; Shuo Yang; et al. (Journal of Environmental Chemical Engineering, 2024)

Valorizing Arthrospira cell residues into polysaccharides: Characterization and application in yogurt - Genyuan Li; Qing Guo; Qian Chen; Kefan Ouyang; Hexiang Xie; Hua Xiong; Yulan Du; Qiang Zhao (Food Chemistry, 2024)

Blood cadmium levels and overactive bladder in middle-aged and older adults in the United States: Insights from NHANES 2007–2020 data - Fan Gao; Yin Lu; Qiang Cheng; Qing Ai; Bin Jiang; Zhen-Jun Luo; Guo-Rong Yang; Kai-Kai Lv; Qing Yuan; Hong-Zhao Li (Environmental Pollution, 2024)

Interfacial evaporation and salt-blocking kinetics in Janus membrane for solar desalination - Haowei Hu; Jin Wang; Qi Zhao; Mengyuan Qiang; Qin Li; Lin Guo; Yawei Yang (Desalination, 2024)

Changes in the radial growth patterns of two dominant tree species in north-central China under climate warming - Jiachuan Wang; Shuheng Li; Yili Guo; Yijie Han; Qi Liu; Yiqi Zhao; Qiang Li (Dendrochronologia, 2024)

Double-gradient host enabling bottom-up Li deposition towards hybrid lithium-ion/metal anode with long lifespan - Zhicui Song; Chaohui Wei; Jicheng Jiang; Donghuang Wang; Xin Wang; Qijiu Deng; Qiang Zhao; Aijun Zhou; Hong Li; Jingze Li (Chemical Engineering Journal, 2024)

Comparison of Long-Term Outcomes in Ruptured Diffuse Brain Arteriovenous Malformations Between Interventional Therapy and Conservative Management - Changyu Lu; Heze Han; Li Ma; Ruinan Li; Zhipeng Li; Haibin Zhang; Kexin Yuan; Yukun Zhang; Anqi Li; Ke Wang; Yang Zhao; Weitao Jin; et al. (Translational Stroke Research, 2024)

Embryonic Genome Activation (EGA) Occurred at 1-Cell Stage of Embryonic Development in the Mud Crab, Scylla paramamosain, Revealed by RNA-Seq - Li-Kun Xu; Chun-Yan Ma; Feng-Ying Zhang; Wei Wang; Ming Zhao; Xin Jin; Jin-Ju Yin; Ling-Bo Ma; Wei Chen; Jia-Yuan Xu; Ke-Yi Ma; Zhi-Qiang Liu (Marine Biotechnology, 2024)

Pollinator-mediated selection on flowering start and corolla tube length differed between mating systems in a primrose species - Zhao-Li Tong; Yong-Peng Cha; Yin-Mei Ma; Yun Wu; Zhi-Qiang Zhang (Evolutionary Ecology, 2024)

Myxobolus liuyangensis sp. n. (Myxosporea: Myxobolidae) from the gills of exotic mrigal carp Cirrhinus mrigala (Actinopterygii: Cyprinidae) in China - Shen Yuan; Xiaojing Zhao; Xiancheng Song; Cheng Chen; Qiang Wei; Deliang Li; Jinping Wang; Xinhua Liu (Systematic Parasitology, 2024)

Field Experimental Study of Sulfuric Acid Extraction from Acid Mine Drainage - Zhiqiang Wang; Honglei Liu; Zehua Zhao; Hujun Ren; Xibin Li; Hao Wang; Qiang Wu (Mine Water and the Environment, 2024)

Tight integration of real-time GNSS PPP and INS: Ionosphere-free combined vs uncombined models - Lei Zhao; Paul Blunt; Lei Yang; Qiyuan Zhang; Guangcai Li; Qiang Wen (Advances in Space Research, 2024)

Numerical simulation of two-dimensional magnetotelluric forward modeling of Heifangtai loess landslide in Gansu, China - Bin Li; Qiang Xu; Sui-wang Ji; Qiang Cheng; Tian-Xiang Liu; Hu Zhao; Ming-gao Tang; Guang Zheng (Applied Geophysics, 2024)

Sirtuin 7 ameliorates cuproptosis, myocardial remodeling and heart dysfunction in hypertension through the modulation of YAP/ATP7A signaling - Yu-Fei Chen; Rui-Qiang Qi; Jia-Wei Song; Si-Yuan Wang; Zhao-Jie Dong; Yi-Hang Chen; Ying Liu; Xin-Yu Zhou; Jing Li; Xiao-Yan Liu; Jiu-Chang Zhong (Apoptosis, 2024)

Biogenic silica dynamics in coastal wetland sediments: A key driver of silicon and carbon biogeochemical cycling - Xiangwei Zhao; Zhaoliang Song; Yuntao Wu; Lukas Van Zwieten; Laodong Guo; Changxun Yu; Zimin Li; Lele Wu; Xiaomin Yang; Xiangbin Ran; Jun Sun; Yuqiu Wei; et al. (Limnology and Oceanography, 2024)
Biogenic silica (biogenic Si) is a bioactive component crucial for the biogeochemical cycling of Si in terrestrial and aquatic ecosystems. Its formation and dissolution dynamics are intricately linked to carbon (C) cycling. However, knowledge about the source, composition, and factors controlling the distribution of biogenic Si in coastal wetland sedimentary environments is still limited. To address this lack of knowledge, we introduced a suite of geometric models for biogenic Si biovolume calculation and investigated biogenic Si assemblages, along with biogenic Si and biogenic Si‐occluded C contents, in sediments from representative coastal wetlands along the west coast of Bohai Bay. Our analysis showed that sedimentary biogenic Si predominantly derived from phytoliths (78.1% ± 5.8%), diatoms (18.2% ± 4.8%), and sponge spicules (3.7% ± 2.9%). Notably, phytolith assemblages were primarily composed of forms derived from the Poaceae family. The biogenic Si‐occluded C content (0.035–1.870 g kg −1 ) within these wetland sediments was consistent across both sites, accounting for 0.97–5.71% of the total organic C pool. Structural equation modeling indicated that total organic C, pH, and amorphous aluminum oxides either directly or indirectly influenced the biogenic Si content in coastal wetlands sediments. These results demonstrate the critical role that biogenic Si plays in the Si biogeochemical cycle and provide valuable information that advances our understanding of the biogeochemical interactions between Si and C in coastal wetland ecosystems.

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

Mendelian randomization reveals predictive, preventive, and personalized insights into inflammatory bowel disease: the role of gut microbiome and circulating inflammatory proteins - Wuqing Zhao; Shixiao Li; Qianqian Li; Qiang Li; Ya Zheng; Hong Lu (EPMA Journal, 2024)

The role of bound polyphenols in the anti-obesity effects of defatted rice bran insoluble dietary fiber: An insight from multi-omics - Bing Zheng; Xiaole Zhao; Tianxiang Ao; Yi Chen; Jianhua Xie; Xingcai Gao; Li Liu; Xiaobo Hu; Qiang Yu (Food Chemistry, 2024)

Pyrrole adducts mediated mitochondrial dysfunction activates SARM1-dependent axon degeneration in 2,5-hexanedione-induced neuropathy - Wenting Ni; Yihan Ye; Shuai Wang; Xianjie Li; Hui Li; Dong Cheng; Qiang Jia; Zhidan Liu; Shulin Shan; Yalong Qiang; Shihua Chao; Xiulan Zhao; et al. (Environmental Pollution, 2024)

Phase change thermal interface film with bicontinuous and textured filler network for efficient wearable heat dissipation - Jia-Qing Zhao; Xiang Wang; Xun-Rui Wang; Hong-Wei Zhao; Mei-Na Lu; Wayne-Qiang Xu; Hong-En Nian; Jin-Hong Li (Chemical Engineering Journal, 2024)

High-efficient synthesis of straw-derived carbon quantum dots for facilitating methanogenic performance in high-load co-digestion of food waste and excess sludge - Qiang Liu; Haoyu Zhang; Haozhen Wang; Shenggeng Zhao; Yeqing Li; Lu Feng; Junting Pan; Hongjun Zhou; Chunming Xu (Chemical Engineering Journal, 2024)

Closed-loop recyclable wood-plastic composite as a sustainable alternative to wood: A solution for utilizing wood waste and promoting carbon sequestration - Shuang-Xi Hou; Chun-Yan Zhao; Wan-Ting Xiong; Jie Zhang; Mao-Qin Li; Guo-Qiang Tian; Gang Wu; Si-Chong Chen; Yu-Zhong Wang (Chemical Engineering Journal, 2024)

Engineering multifunctional intracellular energy metabolism enhanced polycitrate-based hydrogel for MRSA infected wound therapy - Sihua Li; Yanzi Zhao; Meng Luo; Qingsong Zhang; Chaoyan Hu; Weipeng Qiang; Xiaoyan Qu; Qian Huang; Bo Lei (Chemical Engineering Journal, 2024)

Augmented Mitochondrial Transfer Involved in Astrocytic PSPH Attenuates Cognitive Dysfunction in db/db Mice - Hongli Ma; Shuxuan He; Yansong Li; Xin Zhang; Haiqing Chang; Mengyu Du; Chaoying Yan; Shiqiu Jiang; Hui Gao; Jing Zhao; Qiang Wang (Molecular Neurobiology, 2024)

Overlooked Vital Role of Persistent Algae‐Bacteria Interaction in Ocean Recalcitrant Carbon Sequestration and Its Response to Ocean Warming - Hanshuang Zhao; Zenghu Zhang; Shailesh Nair; Hongmei Li; Chen He; Quan Shi; Qiang Zheng; Ruanhong Cai; Genming Luo; Shucheng Xie; Nianzhi Jiao; Yongyu Zhang (Global Change Biology, 2024)
Long‐term carbon sequestration by the ocean's recalcitrant dissolved organic carbon (RDOC) pool regulates global climate. Algae and bacteria interactively underpin RDOC formation. However, on the long‐term scales, the influence of their persistent interactions close to in situ state on ocean RDOC dynamics and accumulation remains unclear, limiting our understanding of the oceanic RDOC pool formation and future trends under global change. We show that a Synechococcus ‐bacteria interaction model system viable over 720 days gradually accumulated high DOC concentrations up to 84 mg L −1 . Concurrently, the DOC inertness increased with the RDOC ratio reaching > 50%. The identified Synechococcus ‐bacteria‐driven RDOC molecules shared similarity with over half of those from pelagic ocean DOC. Importantly, we provide direct genetic and metabolite evidence that alongside the continuous transformation of algal carbon by bacteria to generate RDOC, Synechococcus itself also directly synthesized and released RDOC molecules, representing a neglected RDOC source with ~0.2–1 Gt y −1 in the ocean. However, we found that although ocean warming (+4°C) can promote algal and bacterial growth and DOC release, it destabilizes and reduces RDOC reservoirs, jeopardizing the ocean's carbon sequestration capacity. This study unveils the previously underestimated yet significant role of algae and long‐term algae‐bacteria interactions in ocean carbon sequestration and its vulnerability to ocean warming.

Accurately estimate soybean growth stages from UAV imagery by accounting for spatial heterogeneity and climate factors across multiple environments - Yingpu Che; Yongzhe Gu; Dong Bai; Delin Li; Jindong Li; Chaosen Zhao; Qiang Wang; Hongmei Qiu; Wen Huang; Chunyan Yang; Qingsong Zhao; Like Liu; et al. (Computers and Electronics in Agriculture, 2024)

An integrated analysis of transcriptome and metabolome to reveal the effects of temperature stress on energy metabolism and physiological responses in Schizothorax wangchiachii muscles - Han Zhao; Zhongmeng Zhao; Can Liu; Jian Zhou; Zhipeng Huang; Yuanliang Duan; Lu Zhang; Hongyu Ke; Jun Du; Chengyan Mou; Qiang Li (Aquaculture, 2024)

WITHDRAWN: Global at-risk basins of socio-ecological impacts from water scarcity - Fubo Zhao; Qichen Wang; Wenbo Shi; Yinuo Shan; Xi Wang; Qiang Li; Dengfeng Liu; Jun Du; Yiping Wu (Science of The Total Environment, 2024)

Vegetation response to large-scale mountain excavation and city construction projects on the Loess Plateau of China - Chuanhao Pu; Qiang Xu; Xiaochen Wang; Lina Hao; Fanshu Xu; Wanlin Chen; Kuanyao Zhao; Pinglang Kou; Huajin Li (Science of The Total Environment, 2024)

Organic matter composition and stability in estuarine wetlands depending on soil salinity - Lele Wu; Zhaoliang Song; Yuntao Wu; Shaopan Xia; Yakov Kuzyakov; Iain P. Hartley; Yunying Fang; Changxun Yu; Yidong Wang; Ji Chen; Laodong Guo; Zimin Li; et al. (Science of The Total Environment, 2024)

Innovative utilization of plant-derived dissolved organic matter to promote polycyclic aromatic hydrocarbons removal in constructed wetlands: Unraveling the synergy among substrate adsorption, plant uptake, and microbial degradation - Congcong Zhao; Qilong Ma; Jiaxue Luo; Luxing Liu; Zaixin Zhang; Jingtao Xu; Jiatong Wang; Wenying Li; Qiang Kong; Qian Wang; Huanxin Zhang; Jian Zhang (Process Safety and Environmental Protection, 2024)

Numerical modelling of the spatial distribution of wave overtopping water behind dikes under regular wave action using OpenFOAM - Haitao Zhao; Junwei Ye; Shudi Dong; Yadong Hou; He Xu; Weifang Gu; Qiang Li; Xizeng Zhao (Ocean Engineering, 2024)

Alkali pretreatment-assisted catalytic pyrolysis of waste cellulose acetate for selective preparation of levoglucosenone - Shi-Yu Feng; Sheng Li; Wan-Zhao Huang; Qi Niu; Deng-Yu Chen; Zhi-Mo Fang; Li-Juan Gao; Kai Li; Qiang Lu (Journal of Environmental Chemical Engineering, 2024)

Iron-doped manganese oxide octahedral molecular sieve catalysts for ozone decomposition - Dilong Qiang; Hongyang Jin; Qishun Qing; Su Wang; Tianhong Mei; Zhen Li; Songjian Zhao (Journal of Environmental Chemical Engineering, 2024)

Degradation effect on oxidation of 5-hydroxymethyl-2-furaldehyde over cobalt-iron electrocatalysts in alkaline condition - Yusrin Ramli; Virdi Chaerusani; Ziyuan Yang; Zhongbao Feng; Surachai Karnjanakom; Qiang Zhao; Shasha Li; Yongfeng Li; Abuliti Abudula; Guoqing Guan (Journal of Environmental Chemical Engineering, 2024)

Anaerobic co-digestion of food waste and excess sludge by humus composites: Characteristics and microbial community structure - Ke Zhao; Qiang Wei; Ximing Zhang; Yuze Liu; Fengxiang Li (Journal of Environmental Chemical Engineering, 2024)

Impact of biochar synergized bacteria on Mn2+ and NH4+-N removal and CO2 immobilization in water by enhanced extracellular electron transfer - Shuman Deng; Qiang An; Weifeng Zhang; Zheng Li; Jiali Song; Yichen Yang; Bohan Xu; Binbin Ran; Bin Zhao (Journal of Environmental Chemical Engineering, 2024)

Waste reduction and high value utilization of jarosite-alunite residue (JAR) produced from the recovery of spent lithium-ion battery - Wenke Liu; Ping Li; Qingwei Qin; Wei Zhao; Hailin Zhang; Yunwu Han; Feijie Wu; Qiang Zhang; Shili Zheng; Guangqiang Li (Hydrometallurgy, 2024)

Enhancing the capacitance of carbonized wood by regulating the morphology and valence state of guest electrochemically active materials - Kai Yang; Qiang Yang; Zhao Li; Daotong Zhang; Chaozheng Liu; Pu Yang; Yiying Ling; Yaorong Hu; Yimei Liu; Min Luo; Weimin Chen; Xiaoyan Zhou (Chemical Engineering Journal, 2024)

Structure–activity relationship of a dual-function amine-based electrolyte for integrated CO2 capture and electrochemical conversion - Qiang Li; Tongxin Qu; Shuting Tan; Teng Wang; Yuhang Ding; Chang Wang; Junying Zhang; Zhuo Xiong; Yongchun Zhao (Chemical Engineering Journal, 2024)

Graphene/MXene/Cellulose cellulosic paper-based flexible bifunctional sensors utilizing molecular bridge strategy with tunable piezoresistive effect for Temperature-Pressure sensing - Tianxu Zhang; Yunong Zhao; Qiang Long; Xiaowen Zhu; Langyu He; Zhuoyang Li; Xingyu Qian; Xin He; Jiahao Li; Cancan Lv; Yuxing Zha; Yiting Chen; et al. (Chemical Engineering Journal, 2024)

Exceptional thermoelectric and mechanical performance in (Bi, Sb)2Te3 matrix facilitated by AgInSe2 alloying - Ruiheng Li; Wenxin Ou; Jianglong Zhu; Qian Deng; Xiaobo Tan; Qi Zhao; Tianbo Lu; Shaojingya Gao; Huangshui Ma; Hao Wu; Qiang Sun; Ran Ang (Chemical Engineering Journal, 2024)

Pure-phase two-dimensional perovskite capping layer enables high-performance and durable carbon-based photovoltaics - Shouye Dai; Huaiman Cao; Walid Sharmoukh; Yue Qiang; Liangyu Zhao; Yulong Chen; Yuxin Li; Hani Nasser Abdelhamid; Nima Taghavinia; Ze Yu (Chemical Engineering Journal, 2024)

Coral reefs of Pakistan: a comprehensive review of anthropogenic threats, climate change, and conservation status - Ishfaq Ahmad; Pu Guo; Mei-Xia Zhao; Yu Zhong; Xiao-Yun Zheng; Shu-Qi Zhang; Jian-Wen Qiu; Qi Shi; Hong-Qiang Yan; Shi-Chen Tao; Li-Jia Xu (Frontiers in Marine Science, 2024)
The coral reefs along Pakistan’s coastline are of ecological and economic significance. However, they are increasingly threatened by anthropogenic threats and climate change. These vulnerable ecosystems are declining due to various factors such as sedimentation, climate change, overfishing, destructive fishing practices, marine pollution, and tourism development. We found that 29%, 24%, 26%, 16% and 18% of the studies exceeding, marine pollution, overfishing/destructive fishing, coastal tourism, climate change and sedimentation, respectively; thus, indicating inadequate water quality status in part of Pakistan coastal water. These influences lead to several negative impacts, such as jeopardized coral health, decline in biodiversity, and the simplification of reef structures. In response to these threats, conservation efforts are imperative. This literature review provides an in-depth analysis of anthropogenic threats, climate change and the conservation of coral reefs in Pakistan. This review provides suggestions on how the country could better conserve its coral reef ecosystem. These include (1) initiatives such as establishing marine protected areas (MPAs), (2) encouraging sustainable fishing practices and reducing pollution, (3) developing the country as an ecotourism destination and implementing climate change adaptation measures, and (4) community engagement through awareness campaigns and fostering collaboration among, governmental organizations, non-governmental organizations (NGOs) and scientists. These comprehensive conservation policies address human-caused and other challenges, safeguarding their ecological, economic, and cultural relevance for future generations.

Calcium regulates the interactions between dissolved organic matter and planktonic bacteria in Erhai Lake, Yunnan Province, China - Fan Xia; Zaihua Liu; Yunling Zhang; Qiang Li; Min Zhao; Haibo He; Qian Bao; Bo Chen; Qiufang He; Chaowei Lai; Xuejun He; Zhen Ma; et al. (Water Research, 2024)

Endoplasmic reticulum stress response modulator OsbZIP39 regulates cadmium accumulation via activating the expression of defensin-like gene OsCAL2 in rice - Jian Li; Ling-Yan Wang; Huan-Chao Huang; Wu Yang; Guang-Yi Dai; Zhi-Qiang Fang; Jun-Liang Zhao; Kuai-Fei Xia; Xuan Zeng; Meng-Ling He; Nan Yao; Ming-Yong Zhang (Journal of Hazardous Materials, 2024)

Recovery of Li from waste Li-containing Al electrolytes with high F and Na contents by using a CaO roasting–water leaching process - Shuai Zhao; Yongli Li; Qiang Guo; Lina Wang; Tao Qi; Ling Zhang (Journal of Environmental Management, 2024)

Highly efficient conversion of lignin bio-oil and derived phenols to cyclohexanols over low-loading Ni/C catalyst - Jin-Xuan Xie; Yun-Peng Zhao; Qiang Li; Le-Le Qiu; Fang-Jing Liu; Jing Liang; Jian Li; Jing-Pei Cao (Fuel, 2024)

Improving crop productivity by optimizing straw returning patterns to delay senescence of wheat leaves - Pan Li; Wen Yin; Zhilong Fan; Falong Hu; Lianhao Zhao; Hong Fan; Wei He; Qiang Chai (European Journal of Agronomy, 2024)

Comprehensive investigation of a dangerous counter-tilt landslide in the upper reaches of Jinsha River, China - Qiang Xu; Zhigang Li; Weihua Zhao; Weile Li; Xing Zhu; Xiujun Dong; Congwei Yu; Weimin Li; Xueqing Li; Xincheng Wang; Huiyan Lu; Shouyu Wang; et al. (Landslides, 2024)

Overcoming mechanistic limitations of process-based phenological models: A data clustering method for large-scale applications - Jiaojiao Tan; Gang Zhao; Qi Tian; Lei Zheng; Xiaofeng Kang; Qinsi He; Yu Shi; Bin Chen; Dingrong Wu; Ning Yao; Liang He; Amit Kumar Srivastava; et al. (Agricultural and Forest Meteorology, 2024)

Optimising maize threshing by integrating DEM simulation and interpretive enhanced predictive modelling - Xuwen Fang; Jinsong Zhang; Xuelin Zhao; Li Zhang; Deyi Zhou; Chunsheng Yu; Wei Hu; Qiang Zhang (Biosystems Engineering, 2024)

Association between residential greenness and incident delirium: A prospective cohort study in the UK Biobank - Qida He; Mengtong Sun; Yu Wang; Guoxian Li; Hanqing Zhao; Ze Ma; Zhaolong Feng; Tongxing Li; Qiang Han; Na Sun; Linyan Li; Yueping Shen (Science of The Total Environment, 2024)

Seasonal and spatial characteristics of microbial community in intertidal wetlands: Aspect of microbial coupling - Qian Wang; Kejin Zong; Yinghui Wang; Guoying Zhou; Huiyu Li; Xiaohan Sun; Congcong Zhao; Yi Lv; Yinli Ji; Shuai Wang; Xianrui Song; Qiang Kong (Process Safety and Environmental Protection, 2024)

Evaluating the necessity of autumn irrigation on salinized soil by considering changes in soil physicochemical properties - Hang ZHAO; Jingwei WU; Changsen LI; Yawen LIU; Rui ZHANG; Qiang ZHAO (Pedosphere, 2024)

Characterizing spatial distribution of ice and methane hydrates in sediments using cross-hole electrical resistivity tomography - Yang Liu; Qiang Chen; Sanzhong Li; Xiujuan Wang; Jinhuan Zhao; Changchun Zou (Gas Science and Engineering, 2024)

Comprehensive assessment of the anti-obesity effects of highland barley total, insoluble, and soluble dietary fiber through multi-omics analysis - Bing Zheng; Tianxiang Ao; Xiaole Zhao; Yi Chen; Jianhua Xie; Xingcai Gao; Li Liu; Xiaobo Hu; Qiang Yu (Food Research International, 2024)

Identification of COP9 signalosome (CSN) subunits and antiviral function analysis of CSN5 in shrimp - Li-Xia Lv; Qiang Zhang; Xiao-Fan Zhao; Jin-Xing Wang (Fish & Shellfish Immunology, 2024)

Deciphering the formation of granules by n-DAMO and Anammox microorganisms - Zhi-Cheng Zhao; Ruo-Lin Li; Sheng-Qiang Fan; Yang Lu; Bing-Feng Liu; De-Feng Xing; Nan-Qi Ren; Guo-Jun Xie (Environmental Research, 2024)

Efficient desalination in fluorinated multilayered covalent organic framework: Tunning the energy landscape inside the nanochannel - Meili Yuan; Yong-Qiang Li; Mingwen Zhao; Weifeng Li; Yuanyuan Qu (Desalination, 2024)

Mantle-rooted fluid pathways and world-class gold mineralization in the giant Jiaodong gold province: Insights from integrated deep seismic reflection and tectonics - Li-Qiang Yang; Jun Deng; Liang Zhang; Ai-Hua Zhao; M. Santosh; Xue-Feng Yu; Wei Yang; Da-Peng Li; Wei Shan; Dong Xie; Xiang-Dong Liu; Xue Gao; et al. (Earth-Science Reviews, 2024)

Study on the variations in the mesostructure and mechanical properties of soil around laterally loaded GFRP–trapezoidal core sandwich piles based on the continuum–discrete coupling method - Junzheng Xiang; Jiajie Li; Sheng Qiang; Yunpeng Zhao; Chengpeng Zhang; Chong Shi (Computers and Geotechnics, 2024)

Two-photon polymerization-based 3D micro-scaffolds toward biomedical devices - Wei Wang; Zi-Qing Chen; Bin Lin; Mei-Chen Liu; Yang Zhang; Shu-Juan Liu; Yang Li; Qiang Zhao (Chemical Engineering Journal, 2024)

The Association Between Branched-Chain Amino Acid Concentrations and the Risk of Autism Spectrum Disorder in Preschool-Aged Children - Qi Gao; Dan Bi; Bingbing Li; Min Ni; Dizhou Pang; Xian Li; Xiaoli Zhang; Yiran Xu; Qiang Zhao; Changlian Zhu (Molecular Neurobiology, 2024)
Several studies have linked branched-chain amino acid (BCAA) metabolism disorders with autism spectrum disorder (ASD), but the results have been inconsistent. The purpose of this study was to explore the association between BCAA concentrations and the risk of ASD. A total of 313 participants were recruited from two tertiary referral hospitals from May 2018 to July 2021. Concentrations of BCAAs in dried blood spots were analyzed using liquid chromatography-tandem mass spectrometry-based analysis. Multivariate analyses and restricted cubic spline models were used to identify the association between BCAAs and the risk of ASD, and a nomogram was developed by using multivariate logistic regression and the risk was determined by receiver operating characteristic curve analysis and calibration curve analysis. Concentrations of total BCAA, valine, and leucine/isoleucine were higher in the ASD group, and all of them were positively and non-linearly associated with the risk of ASD even after adjusting for potential confounding factors such as age, gender, body mass index, and concentrations of BCAAs ( P < 0.05). The nomogram integrating total BCAA and valine showed a good discriminant AUC value of 0.756 (95% CI 0.676–0.835). The model could yield net benefits across a reasonable range of risk thresholds. In the stratified analysis, the diagnostic ability of the model was more pronounced in children older than 3 years. We provide evidence that increased levels of BCAAs are associated with the risk of ASD, and the nomogram model of BCAAs presented here can serve as a marker for the early diagnosis of ASD.

Aging- and alcohol-associated spatial transcriptomic signature in mouse acute pancreatitis reveals heterogeneity of inflammation and potential pathogenic factors - Rachel R. Tindall; Yuntao Yang; Isabella Hernandez; Amy Qin; Jiajing Li; Yinjie Zhang; Thomas H. Gomez; Mamoun Younes; Qiang Shen; Jennifer M. Bailey-Lundberg; Zhongming Zhao; Daniel Kraushaar; et al. (Journal of Molecular Medicine, 2024)
The rapidly aging population is consuming more alcohol, leading to increased alcohol-associated acute pancreatitis (AAP) with high mortality. However, the mechanisms remain undefined, and currently there are no effective therapies available. This study aims to elucidate aging- and alcohol-associated spatial transcriptomic signature by establishing an aging AAP mouse model and applying Visium spatial transcriptomics for understanding of the mechanisms in the context of the pancreatic tissue. Upon alcohol diet feeding and caerulein treatment, aging mice (18 months) developed significantly more severe AAP with 5.0-fold increase of injury score and 2.4-fold increase of amylase compared to young mice (3 months). Via Visium spatial transcriptomics, eight distinct tissue clusters were revealed from aggregated transcriptomes of aging and young AAP mice: five acinar, two stromal, and one islet, which were then merged into three clusters: acinar, stromal, and islet for the comparative analysis. Compared to young AAP mice, > 1300 differentially expressed genes (DEGs) and approximately 3000 differentially regulated pathways were identified in aging AAP mice. The top five DEGs upregulated in aging AAP mice include Mmp8 , Ppbp , Serpina3m , Cxcl13 , and Hamp with heterogeneous distributions among the clusters. Taken together, this study demonstrates spatial heterogeneity of inflammatory processes in aging AAP mice, offering novel insights into the mechanisms and potential drivers for AAP development. Key messages Mechanisms regarding high mortality of AAP in aging remain undefined. An aging AAP mouse model was developed recapturing clinical exhibition in humans. Spatial transcriptomics identified contrasted DEGs in aging vs. young AAP mice. Top five DEGs were Mmp8 , Ppbp , Serpina3m , Cxcl13 , and Hamp in aging vs. young AAP mice. Our findings shed insights for identification of molecular drivers in aging AAP.

Enhancing shrimp growth and immunity with green algal Caulerpa lentillifera polysaccharides through gut microbiota regulation - Yanmei Tong; Qiangyong Li; Chunling Yang; Min Peng; Xiuli Chen; Qiang Liu; Yuliu Huang; Pengfei Feng; Digang Zeng; Fan Wang; Tingjun Hu; Qingyun Liu; et al. (Algal Research, 2024)

Two new alkaloids from the endophytic fungus Schizophyllum sp. HM230 isolated from Vincetoxicum mongolicum Maxim - Zhuang Li; Bing-Wen Zhang; Li Jiang; He Wang; Qing-Yun Ma; Hong-Fei Wang; Jun Zhang; Feng-Li Chen; You-Xing Zhao; Du-Qiang Luo (Natural Product Research, 2024)

Macaque Brainnetome Atlas: A multifaceted brain map with parcellation, connection, and histology - Yuheng Lu; Yue Cui; Long Cao; Zhenwei Dong; Luqi Cheng; Wen Wu; Changshuo Wang; Xinyi Liu; Youtong Liu; Baogui Zhang; Deying Li; Bokai Zhao; et al. (Science Bulletin, 2024)

Carbon-Sulfur isotope and major and trace element variations across the Permian–Triassic boundary on a shallow platform setting (Xiejiacao, South China) - Zijie Zheng; Zhong-Qiang Chen; Stephen E. Grasby; Xue Wang; Dominic Papineau; Ziheng Li; Xiangdong Wang; Lei Zhang; He Zhao; Yuangeng Huang; Xueqian Feng; Lewei Su; et al. (Chemical Geology, 2024)

Overcoming genotypic dependency and bypassing immature embryos in wheat transformation by using morphogenic regulators - Ziru Zhou; Yawen Yang; Guo Ai; Miaomiao Zhao; Baozhu Han; Chunjie Zhao; Yiqian Chen; Yuwei Zhang; Hong Pan; Caixia Lan; Chao He; Qiang Li; et al. (Science China Life Sciences, 2024)

Toward a solid microneedle patch for rapid and enhanced local analgesic action - Yue Liu; Ze Qiang Zhao; Ling Liang; Li Yue Jing; Jianhao Wang; Yun Dai; Bo Zhi Chen; Xin Dong Guo (Drug Delivery and Translational Research, 2024)

Maize kernel damage dynamic prediction in threshing through PSO-LSTM and discrete element modelling - Xuwen Fang; Jinsong Zhang; Xuelin Zhao; Qiang Zhang; Li Zhang; Deyi Zhou; Chunsheng Yu; Wei Hu; Hao Wang (Biosystems Engineering, 2024)

The boom era of emerging contaminants: A review of remediating agricultural soils by biochar - Renjie Hou; Jian Zhang; Qiang Fu; Tianxiao Li; Shijun Gao; Rui Wang; Shan Zhao; Bingyu Zhu (Science of The Total Environment, 2024)

Laser induced graphene goes stretchable for multimodal sensing - Yang Li; Yuzhe Gu; Yuncong Pang; Qiang Zhao (Science Bulletin, 2024)

Microbially induced fabrics in the Upper Ediacaran coated grain dolostone, Northeast Sichuan Basin, SW China: Implications for reconstruction of the paleoceanic environment - Zuozhen Han; Shourui Dai; Yongjie Zhang; Chao Han; Chenlin Zhu; Yanyang Zhao; Yuetong Zhang; Qiang Li (Sedimentary Geology, 2024)

Characteristics and paleoenvironmental conditions of the well-preserved Early Mesoproterozoic Fengjiawan Formation stromatolites in the southern North China Craton - Ahmed Khaled; Rongxi Li; Bangsheng Zhao; Futian Liu; Xiaoli Wu; Yanni Zhang; Xiaoli Qin; Qiang Yu (Precambrian Research, 2024)

Neoarchean clockwise P-T trajectories with evolution sequence from HP to UHT metamorphism during decompression: Evidence from petrology, mineralogy, and phase equilibria modeling of mafic granulites in the Sittampundi Complex, southern India - Xu Kong; Jun-Sheng Lu; Ming-Guo Zhai; Cheng-Li Zhang; M.P. George; Long-Long Gou; Yan Zhao; Wen-Hao Ao; Yu-Hua Hu; Qiang Feng; Gang Liu (Precambrian Research, 2024)

The microplastics distribution characteristics and their impact on soil physicochemical properties and bacterial communities in food legumes farmland in northern China - Yuepeng La; Li Zhang; Nan Zhao; Huike Ye; Qiang Zeng; Lijie Zhao; Zhengjun Wang; Dasong Lin; Ruigang Wang (Journal of Hazardous Materials, 2024)

Carbon nanotube incorporated quaternized lignin-based loose nanofiltration membrane toward dye/salt separation - Zhenyu He; Na Zhang; Li Zhao; Zhenghua Li; Wanling Cui; Yuangang Zhu; Yi Wang; Huining Deng; Chengrun Si; Wen Bo; Jie Zhou; Shicai Xu; et al. (Journal of Environmental Chemical Engineering, 2024)

Study on transferring the refrigeration power in the temperature-distributed regenerative refrigeration cycle - Qiang Cao; Pengcheng Wang; Zhiping Wang; Miaomiao Wang; Yuji Chen; Lichun Ge; Peng Li; Qinyu Zhao; Bo Wang; Zhihua Gan (International Journal of Refrigeration, 2024)

Preparation of slag-based foam concrete and its carbon dioxide sequestration performance - Jing Zhao; Yu-qing Li; Jing-jing Yang; Xiao-qiang Cao; Jun-xiang Wang; Gang Wang; Lu-lu Sun; Qi-ming Huang; Wei-min Cheng; Zhi-wen Lyu (International Journal of Greenhouse Gas Control, 2024)

Head-Mounted coating on graphite host enabling highly reversible Li Plating/Stripping in Lithium-ion/Lithium metal hybrid anode - Zhicui Song; Jing Xue; Chaohui Wei; Qiang Zhao; Aijun Zhou; Jingze Li (Chemical Engineering Journal, 2024)

Au-embedded mesoporous molecular sieve enables robust organic/inorganic hybrid solid electrolyte interphase for high-performance lithium metal batteries - Yiping Liu; Qiang Zhang; Congcong Dang; Jie Dong; Lingti Kong; Ming Li; Liancheng Zhao; Liming Gao (Chemical Engineering Journal, 2024)

Deep-injected straw incorporation enhances subsoil quality and wheat productivity - Jun Ling; Jie Zhou; Gong Wu; De-Qiang Zhao; Zhi-Tong Wang; Yuan Wen; Shun-Li Zhou (Plant and Soil, 2024)

Sugarcane borers: species, distribution, damage and management options - Ao-Mei Li; Zhong-Liang Chen; Fen Liao; Yong Zhao; Cui-Xian Qin; Miao Wang; You-Qiang Pan; Shao-Long Wei; Dong-Liang Huang (Journal of Pest Science, 2024)
Lepidopteran borers stand out as the most destructive pests in sugarcane, leading to reductions in stalk weight, juice quality and sugar recovery. Presently, integrated pest management (IPM) systems are utilized for sugarcane borer management, employing diverse methods encompassing cropping system, chemical pesticides, behavioral manipulation, biological agents and the selection of resistant varieties. However, the effectiveness of this strategy remains controversial due to concerns about harmful residues, formulation limitations, environmental variability, labor shortages and increased input costs. Currently, multiple lines of transgenic sugarcane expressing insecticidal genes from the bacterium Bacillus thuringiensis (Bt) have been developed globally, offering the prospect of increases production with reduced pesticides application, thereby eliminating the negative effect of IPM. In Brazil, the first genetically modified sugarcane cultivars resistant to the sugarcane borer have been approved and released for commercial cultivation, shedding a bright light on a viable solution for sugarcane borers. This paper reviews borer species and distribution, the significant damage caused by sugarcane borers, current control approaches and the future effective control strategies. Additionally, this work provides comprehensive understanding on Bt sugarcane, serving as an additional tool to complement conventional sugarcane borers control resistance programs.

Identification of a QTL for Setaria italica bristle length using QTL-seq - Aiying Zhang; Zhaolan Cui; Erhu Guo; Peiyue Zhao; Zongchang Xu; Qiang Li; Shihua Guo; Yuxiang Wu; Zhang Li (Genetic Resources and Crop Evolution, 2024)

Sex differences of signal complexity at resting-state functional magnetic resonance imaging and their associations with the estrogen-signaling pathway in the brain - Cheng-li Zhao; Wenjie Hou; Yanbing Jia; Barbara J. Sahakian; Qiang Luo (Cognitive Neurodynamics, 2024)

Advances in ice avalanches on the Tibetan Plateau - Minggao Tang; Guang Li; Huanle Zhao; Qiang Xu; Guangjian Wu; Wei Yang; Daojing Guo (Journal of Mountain Science, 2024)

Dynamic energy evolution and fragmentation characteristics of damaged rock under impact compression loading - Qiang-Qiang Zheng; Jia-Wei Qian; Ping-Feng Li; Zhi-Qiang Yin; Huan-Ting Zhao (Applied Geophysics, 2024)

Effects of dietary bacterial culture of fengycin-producing Bacillus subtilis on growth performance, intestinal and hepatopancreas health, intestinal microbiota and disease resistance of common carp (Cyprinus carpio) - Rui Xia; Shenghui Li; Hongwei Yang; Yajie Zhao; Tsegay Teame; Qiang Hao; Mingxu Xie; Min Li; Qile Chen; Chunling Song; Chao Ran; Yalin Yang; et al. (Aquaculture, 2024)

Study on the performance of vortex suction cup for an underwater inspection robot - Qinyun Tang; Ying Du; Mingxuan Ding; Shuo Zhang; Qiang Zhao; Shihao Hu; Changda Tian; Liquan Wang; Yingxuan Li; Gang Wang (Ocean Engineering, 2024)

The impact of arbuscular mycorrhizal fungi and endophytic bacteria on peanuts under the combined pollution of cadmium and microplastics - Zi-tian Pu; Dan-dan Wang; Wei-xing Song; Chao Wang; Zhao-yu Li; Ying-long Chen; Tori Shimozono; Zhao-min Yang; Yong-qiang Tian; Zhi-hong Xie (Journal of Hazardous Materials, 2024)

hOGG1: A novel mediator in nitrosamine-induced esophageal tumorigenesis - De-Rong Tang; Cheng-Lin Li; Zhi-Yun Xu; Zhen-Zhong Zhang; Qian-Wei Wang; Jian-Qiang Zhao (Food and Chemical Toxicology, 2024)

A bipolar SMPS network for measuring atmospheric aerosols using natural air ions - Yiran Li; Jin Wu; Hao Wu; Xiaomeng Liu; Qi Zhou; Yiqun Lu; Yuhang Wu; Mengyu Liu; Hengjia Ou; Shixin Mai; Xuehui He; Huaying Song; et al. (Atmospheric Environment, 2024)

Integrated microbiome and metabolome analyses reveal the effects of low pH on intestinal health and homeostasis of crayfish (Procambarus clarkii) - Zhanqi Wang; Jiapeng Li; Pengfei Zhao; Zaihang Yu; Lianlian Yang; Xueyan Ding; He Lv; ShaoKui Yi; Qiang Sheng; Liqin Zhang; Fan Zhou; Hua Wang (Aquatic Toxicology, 2024)

Mechanical Responses of a Porous Red Sandstone to Quasi-Static Cyclic Loads Under Uniaxial Compression - Zhao-Qiang Zheng; Huai-Zhong Liu; Hong-Qiang Xie; Jiang-Da He; Ming-Li Xiao; Li Zhuo (Rock Mechanics and Rock Engineering, 2024)

Preliminary analysis of the catastrophic February 22nd 2023 Xinjing open-pit mine landslide, Inner Mongolia, China - Zhigang Li; Weile Li; Qiang Xu; Huiyan Lu; Hao Fu; Pengyu Guo; Jianjun Zhao; Congwei Yu (Landslides, 2024)

La-activated biochar addition improves phosphorus adsorption performance in soil: Competitive adsorption dominated by organic phosphorus - Di Zhao; Li-sheng Zhang; Meng-meng Li; Shang-kai Qiu; Ke-qiang Zhang; Feng Wang (Journal of Soils and Sediments, 2024)

Influence of building spatial patterns on wind environment and air pollution dispersion inside an industrial park based on CFD simulation - Qiang Zhao; Rui Li; Kaifa Cao; Mingjian Yi; Hao Liu (Environmental Monitoring and Assessment, 2024)

Physical Experimental Study on the Wave Reflection and Run-Up of a New Ecological Hollow Cube - Haitao Zhao; Feiyue Ding; Junwei Ye; Huabin Jiang; Wei Chen; Weifang Gu; Gengfeng Yu; Qiang Li (Journal of Marine Science and Engineering, 2024)
Implementing quadrangular hollow blocks on breakwaters is a common method for wave mitigation and ocean disaster prevention. In order to improve the wave-damping performance of conventional quadrangular hollow blocks, a new quadrangular hollow block is proposed. In this study, a series of physical modeling experiments were conducted in a two-dimensional wave flume to investigate the wave reflection and wave run-up height of a new quadrilateral hollow block under regular wave action. Test results showed that wave reflection and wave run-up height decreased with the breakwater slope. The wave run-up height increased with wave height, and the reflection coefficient decreased with wave height. Wave reflection and run-up height increased with the wave period. The reflection coefficient of the new quadrangular hollow blocks was lower than that of the conventional quadrangular hollow blocks and decreased with frame height. In addition, this study found that the reflection coefficient and relative run-up height increased with the average wave breaking parameter. The new quadrilateral hollow block has advantages in wave mitigation compared to the conventional quadrilateral hollow block.

Study on the Adsorption Performance of a Vortex Suction Cup under Varying Diameters of Underwater Structure Tubes - Qinyun Tang; Ying Du; Zhaojin Liu; Shuo Zhang; Qiang Zhao; Yingxuan Li; Liquan Wang; Tong Cui; Gang Wang (Journal of Marine Science and Engineering, 2024)
In certain precision work scenarios, underwater robots require the ability to adhere to surfaces in order to perform tasks effectively. An efficient and stable suction device plays a pivotal role in the functionality of such underwater robots. The vortex suction cup, distinguished by its uncomplicated design, high suction efficiency, and capability for non-contact adhesion, holds significant promise for integration into underwater robotic systems. This paper presents a novel design for a vortex suction cup and investigates its suction force and torque when encountering surfaces with varying curvature radii using Computational Fluid Dynamics (CFD) simulations and experimental testing. These findings offer valuable insights for the development of robots capable of adapting to underwater structures of different dimensions. Results from both experiments and simulations indicate that reducing the curvature radius of the adhered surface results in a decrease in suction force and an increase in torque exerted on the suction cup. As the adhered surface transitions from flat to a curvature radius of 150 mm, the adhesion force of our proposed vortex suction cup decreases by approximately 10%, while the torque increases by approximately 20% to 30%. Consequently, the adhesion efficiency of the suction cup decreases by about 25% to 30%.

Developing a land development compensation model for returned land in tract expropriation: Towards a unified urban-rural land market in China - Jingpeng Guo; Yinghui Zhao; Frank Yonghong Li; Kebiao Mao; Jinfeng He; Qiang He (Land Use Policy, 2024)

Multicomponent metal nanoparticles supported on nickel foam for efficient catalytic decomposition of vaporized hydrogen peroxide - Haiyun Li; Yiran Shang; Qiang Liu; Cheng Deng; Ying Yi; Jinhui Wu; Lei Zhao; Mengfu Zhu (Journal of Environmental Chemical Engineering, 2024)

Enhancement of adsorption performance for I2 and Cr(VI) by the metal-organic framework UiO-66-NH2 via post-synthetic modification - Ya-Yu Zhao; Zhen Xu; Xin Chen; Meng-Qiang Deng; Peng Li; Wei Gao; Ji-Yang Li; Xiu-Mei Zhang (Journal of Environmental Chemical Engineering, 2024)

Efficient Cr(VI) removal by pyrite/porous biochar: Critical role of potassium salt and sulphur - Lei Zhao; Chuang Li; Hong Li; Zihan Shu; Yang Luo; Hailan Yang; Qiang Chen; Weihua Xu; Wei Zhang; Xiaofei Tan (Environmental Pollution, 2024)

Lignin/mesoporous hollow silica nanosphere thin film nanocomposite loose nanofiltration membrane for dye/salt separation - Qiang Li; Wenge Sun; Bin Shang; Na Zhang; Li Zhao; Huining Deng; Peng Du; Mei Qiao; Jinlong Lu; Zengyu Wang (Desalination, 2024)

The isomorphous substitution of Si(4Al) with P in FAU zeolite and its stabilization effect - Qiang Zhang; Hongjuan Zhao; Xingyu Liu; Rui Li; Tian Xia; Yue Ma; Yuren Wang; Kang Chen; Jiujiang Wang; Penghui Zeng; Honghai Liu; Chaowei Liu; et al. (Chemical Engineering Journal, 2024)

Interfacial Si–O–Zr bonds induced well dispersed zirconia on magnetic mesoporous silicas for enhanced tetracycline removal - Li-Jia Xie; Ying Tan; Yu-Qiu Ke; Kang-Qiang Lu; Kai Yang; Dan Li; Wei-Ya Huang; Yong-Cai Zhang; Zhao-Qing Liu (Chemical Engineering Journal, 2024)

In-capillary aptamer-functionalized dispersive solid-phase microextraction for dynamic transfer enrichment and miniature mass spectrometry analysis: A magnetically driven capture-and-release strategy - Linsen Li; Ying Zhang; Liping Zhao; Yueguang Lv; Feng Qu; Qiang Ma (Chemical Engineering Journal, 2024)

Phosphorus mining activities alter endophytic bacterial communities and metabolic functions of surrounding vegetables and crops - Qiang Li; Peng Xiang; Lijiao Li; Ting Zhang; Qian Wu; Zhijie Bao; Wenying Tu; Changsong Zhao (Plant and Soil, 2024)

A triggered DNA nanomachine with enzyme-free for the rapid detection of telomerase activity in a one-step method - Huajie Pang; Yanan Peng; Rui Zhang; Zhijun Gao; Xiangde Lai; Dongxia Li; Xuan Zhao; Yuanyuan Wang; Hua Pei; Bin Qiao; Yuxiang Ji; Qiang Wu (Analytica Chimica Acta, 2024)

The impacts of planting patterns combined with irrigation management practices on soil water content, watermelon yield and quality - Xiaolin Qiang; Zhaojun Sun; Xingqiang Li; Siqi Li; Zhao Yu; Jun He; Qian Li; Lei Han (Agroforestry Systems, 2024)

Weak correlations among leaf thermal metrics, economic traits and damages under natural heatwaves - Qiu-Rui Ning; Qiang Li; Hao-Ping Zhang; Yi Jin; Xue-Wei Gong; Rui-Fang Jiao; Emily Patience Bakpa; Han Zhao; Hui Liu (Science of The Total Environment, 2024)

Insights into the differential molecular response of non-germinated and germinated spores of Ameson portunus in vitro by comparative transcriptome analysis - Zhao-Zhe Xin; Zhi-Qiang Zhu; Jiu-Yang Chen; Ya-Li Xu; Xin-Tong Zhang; Jin-Yong Zhang (Journal of Invertebrate Pathology, 2024)

Differential response of Hg-methylating and MeHg-demethylating microbiomes to dissolved organic matter components in eutrophic lake water - Zhengyu Wu; Zhike Li; Bo Shao; Ji Chen; Xiaomei Cui; Xiaoyu Cui; Xianhua Liu; Ying Xin Zhao; Qiang Pu; Jiang Liu; Wei He; Yiwen Liu; et al. (Journal of Hazardous Materials, 2024)

The effect of the endogenous protein on the rheological and digestive properties of rice starch - Hao Hu; Genyuan Li; Tingting Zhang; Sixing Lai; Kefan Ouyang; Fang Huang; Songyu Wang; Hua Xiong; Qiang Zhao (Journal of Cereal Science, 2024)

Subducted serpentinite contributes to the formation of arc lavas with heavy Mo isotopic compositions - Fu-Qiang Dai; Yi-Xiang Chen; Ren-Xu Chen; Zi-Fu Zhao; Jie Li; Yu Wang (Geochimica et Cosmochimica Acta, 2024)

Applications of distributed activation energy model on the pyrolysis of green renewable wood - Hao Liu; Mi Li; Shuna Zhao; Lin Jiang; Qiang Xu; Andrea Majlingová (Fuel, 2024)

Constraints of palaeoenvironment on organic matter of Benxi Formation shale and discussion on enrichment mechanism under different facies - Qianyang He; Delu Li; Qiang Sun; Jianwen Gao; Haibin Li; Xinhu Li; Xiaochen Zhao; Shaofei Wang; Gaozhe Ji (Frontiers of Earth Science, 2024)

Sustainable building materials-recycled aggregate and concrete: a systematic review of properties, modification techniques, and environmental impacts - Zhong Li; Yadong Bian; Jihui Zhao; Yiren Wang; Xuan Qiu; Qiang Liu (Environmental Science and Pollution Research, 2024)

Source identification of sedimentary organic carbon in coastal wetlands of the western Bohai Sea - Juqin Zhang; Qian Hao; Qiang Li; Xiangwei Zhao; Xiaoli Fu; Weiqi Wang; Ding He; Yuan Li; Zhenqing Zhang; Xiaodong Zhang; Zhaoliang Song (Science of The Total Environment, 2024)

Silicon fractionations in coastal wetland sediments: Implications for biogeochemical silicon cycling - Xiangwei Zhao; Zhaoliang Song; Lukas Van Zwieten; Yidong Wang; Xiangbin Ran; Qian Hao; Juqin Zhang; Zimin Li; Jun Sun; Yuqiu Wei; Lele Wu; Shuyan Liu; et al. (Science of The Total Environment, 2024)

A model to quantify permeability in solute mixing precipitation porous media - Chenyao Guo; Jingwei Wu; Qiang Zhao; Hang Li; Haoyu Yang; Zhe Wu; Shuai Qin (Journal of Hydrology, 2024)

Enhanced activation of persulfate by modified red mud biochar for degradation of dye pollutant: Resource utilization and non-radical activation - Zheng Li; Shuman Deng; Qiang An; Bin Zhao; Zihao Yang; Bohan Xu; Weifeng Zhang (Journal of Environmental Management, 2024)

Experiment and dynamic simulation of hydrogen recovery from hydrogen-containing gas mixtures via hydrate-membrane coupling method - Jingbo Gao; Qiang Sun; Jia Luo; Leyan Li; Ninghui Liu; Rong Ma; Hang Zhao; Xiangming Li; Zongyu Qin; Yiwei Wang; Xuqiang Guo (Fuel, 2024)

No-tillage with total green manure mulching: A strategy to lower N2O emissions - Hanqiang Lyu; Yue Li; Yulong Wang; Feng Wang; Zhilong Fan; Falong Hu; Wen Yin; Cai Zhao; Aizhong Yu; Qiang Chai (Field Crops Research, 2024)

Diversity and composition of microbial communities in Jinsha earthen site under different degree of deterioration - Jing Li; Yanqiu He; Changjie He; Lin Xiao; Ning Wang; Luman Jiang; Juncheng Chen; Ke Liu; Qiang Chen; Yunfu Gu; Menggen Ma; Xiumei Yu; et al. (Environmental Research, 2024)

Low-temperature degradation of waste epoxy resin polymer improved by swelling-assisted pyrolysis - Yachang Wu; Mingxin Xu; Jie Yang; Jinyi Di; Xiangxi Meng; Haiwen Ji; Li Zhao; Qiang Lu (Chemical Engineering Journal, 2024)

One-stone, two birds: Three-dimensional structure and rich-inorganic solid electrolyte interface derived from Bi nanoparticles modified Ti3C2/CNT/rGO aerogel for anode-free potassium metal batteries - Dong-Ting Zhang; Mao-Cheng Liu; Min-Peng Li; Zi-Zhou Yuan; Yu-Xia Hu; Hao Chen; Chen-Yang Li; Ling-Bin Kong; Kun Zhao; Jun-Qiang Ren; Bao Liu (Chemical Engineering Journal, 2024)

Strain-insensitive bioelectronics - Yang Li; Jiayang Feng; Lele Wang; Tianyu Li; Yuncong Pang; Baoguang Liu; Shujuan Liu; Qiang Zhao (Chemical Engineering Journal, 2024)

The accumulation and carbon sequestration potential of biogenic silica in coastal salt marshes: Implications for relative sea-level rise - Xiangwei Zhao; Xiaodong Zhang; Zhaoliang Song; Lukas Van Zwieten; Xiangbin Ran; Yulin Pu; Jun Sun; Qiang Li; Lele Wu; Xiaomin Yang; Yuqiu Wei; Zimin Li; et al. (CATENA, 2024)

Gemfibrozil Alleviates Cognitive Impairment by Inhibiting Ferroptosis of Astrocytes via Restoring the Iron Metabolism and Promoting Antioxidant Capacity in Type 2 Diabetes - Nan Wang; Yujing Zhao; Meiyan Wu; Na Li; Chaoying Yan; Hongyan Guo; Qiao Li; Qing Li; Qiang Wang (Molecular Neurobiology, 2024)

High fat diet-induced downregulation of TRPV2 mediates hepatic steatosis via p21 signalling - Pengfei Wei; Lixuan Li; Chenqiu Ran; Mingyue Jin; Huijuan Zhao; Kelaier Yang; Yu Wang; Huaqiu He; Mengyang Jia; Hongyan Pan; Qiang Li; Jing Guo (Journal of Physiology and Biochemistry, 2024)

Effects of uranium mining on soil bacterial communities and functions in the Qinghai-Tibet plateau - Qiang Li; Zhuang Xiong; Peng Xiang; Lin Zhou; Ting Zhang; Qian Wu; Changsong Zhao (Chemosphere, 2024)

Weed control performance of different sowing modes in organic wheat production - Zhiwei Zhao; Li Han; Mengyuan Li; Yangyang Sheng; Min Xie; Qiang Wu; Yongping Zhang (Crop Protection, 2024)

When graphene meets circular agriculture: Insights into agricultural sustainable development - Lijiao Li; Yuanmou Tang; Zhijie Bao; Wenying Tu; Lianxin Peng; Liang Zou; Changsong Zhao; Qiang Li (Biosystems Engineering, 2024)

Effects of polystyrene microplastics on the agronomic traits and rhizosphere soil microbial community of highland barley - Peng Xiang; Wenlong Liao; Zhuang Xiong; Wenqi Xiao; Yingyong Luo; Lianxin Peng; Liang Zou; Changsong Zhao; Qiang Li (Science of The Total Environment, 2024)

Inactivation of pathogenic microorganisms in water by electron beam excitation multi-wavelength ultraviolet irradiation: Efficiency, influence factors and mechanism - Yong-Qiang Li; Rui Sun; Chong-Miao Zhang; Zi-Xuan Liu; Rui-tao Chen; Jian Zhao; Hua-dong Gu; Huan-Cai Yin (Journal of Environmental Management, 2024)

Controlling mechanism of shale palaeoenvironment on its tensile strength: A case study of Banjiuguan Formation in Micangshan Mountain - Haibin Li; Delu Li; Qianyang He; Qiang Sun; Xiaochen Zhao (Fuel, 2024)

RuO2/CeO2 heterostructure anchored on carbon spheres as a bifunctional electrocatalyst for efficient water splitting in acidic media - Yun Wu; Rui Yao; Kaiyang Zhang; Qiang Zhao; Jinping Li; Guang Liu (Chemical Engineering Journal, 2024)

Frontostriatal circuitry and the tryptophan kynurenine pathway in major psychiatric disorders - Sugai Liang; Liansheng Zhao; Peiyan Ni; Qiang Wang; Wanjun Guo; Yan Xu; Jia Cai; Shiwan Tao; Xiaojing Li; Wei Deng; Lena Palaniyappan; Tao Li (Psychopharmacology, 2024)

Technological diversity in the tropical-subtropical zone of Southwest China during the terminal Pleistocene: excavations at Fodongdi Cave - Fa-Xiang Huan; Shi-Xia Yang; Feng Gao; Xin-Ying Zhou; Jian-Ping Yue; Yu-Xiu Zhang; Jin-Xu Wu; Qi-Jun Ruan; Kai-Wei Qiu; Jing-wen Xu; Nai-Ru Lin; Yi-Ren Wang; et al. (Archaeological and Anthropological Sciences, 2024)

Isolation and characterization of 55 SNP markers in Triplophysa (Hedinichthys) yarkandensis macroptera - Qiang Li; Yeyu Chen; Hongyu Ke; Zhongmeng Zhao; Han Zhao; Jiansheng Lai; Xiaoyun Wu; Mingjiang Song; Feiyang Li; Ya Liu (Conservation Genetics Resources, 2023)

K252a inhibition of sperm viability for efficient crossbreeding of hermaphroditic bivalves - Tian Liu; Huilan Wei; Lijing Zhang; Liangjie Liu; Yajuan Li; Ya Shu; Yaxin Yang; Baojun Zhao; Qiang Xing; Qifan Zeng; Chunde Wang; Shi Wang; et al. (Aquaculture, 2023)

ASC/Caspase-1-activated endothelial cells pyroptosis is involved in vascular injury induced by arsenic combined with high-fat diet - Qiang Su; Meng Li; Lingling Yang; Linhua Fan; Penghui Liu; Xiaodong Ying; Yannan Zhao; Xiaolin Tian; Fengjie Tian; Qian Zhao; Ben Li; Yi Gao; et al. (Toxicology, 2023)

GRACE-based dynamic assessment of hydrological drought trigger thresholds induced by meteorological drought and possible driving mechanisms - Zhiming Han; Shengzhi Huang; Jian Peng; Jianfeng Li; Guoyong Leng; Qiang Huang; Jing Zhao; Fang Yang; Panxing He; Xiaoyu Meng; Zhi Li (Remote Sensing of Environment, 2023)

Diverse indole-diterpenoids with protein tyrosine phosphatase 1B inhibitory activities from the marine coral-derived fungus Aspergillus sp. ZF-104 - Fei Zhang; Li Yang; Qing-Yi Xie; Jiao-Cen Guo; Qing-Yun Ma; Lu-Ting Dai; Li-Man Zhou; Hao-Fu Dai; Fan-Dong Kong; Du-Qiang Luo; You-Xing Zhao (Phytochemistry, 2023)

Sea level controls on the provenance of fine-grained sediments in the Xisha Trough, northwestern South China Sea over the last ∼30 ka - Qiang Zhang; George E.A. Swann; Jianguo Liu; Weijian Gao; Zhenang Cui; Gang Li; Xuan Zhao; Wei Li (Marine Geology, 2023)

Redox mediators stimulated chain elongation process in fluidized cathode electro-fermentation systems for caproate production - Jingwei Ma; Yingxin Feng; Lu Li; Liang Zhu; Qiulai He; Zhou Shi; Shuizhou Ke; Qiang Ke; Quanbao Zhao (Journal of Environmental Management, 2023)

Efficient activation of peroxydisulfate by modified red mud biochar derived from waste corn straw for levofloxacin degradation: Efficiencies and mechanisms - Zihao Yang; Qiang An; Shuman Deng; Bohan Xu; Zheng Li; Shian Deng; Bin Zhao; Zhihong Ye (Journal of Environmental Chemical Engineering, 2023)

Hidden dangers of ice avalanches and glacier lake outburst floods on the Tibetan Plateau: identification, inventory, and distribution - Minggao Tang; Qiang Xu; Lina Wang; Huanle Zhao; Guangjian Wu; Jian Zhou; Guang Li; Wenjing Cai; Xu Chen (Landslides, 2023)

Myxobolus dumerilii sp. n. (Myxozoa: Myxobolidae) infecting the brain of Chinese longsnout catfish Tachysurus dumerili (Bleeker) in China - Xiaojing Zhao; Liwen Xu; Ren Shisi; Qiang Wei; Qi Yin; Yijing Yang; Jinyong Zhang; Jianguo Xiang; Jianbo Yu; Deliang Li; Xinhua Liu (Systematic Parasitology, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Conductivity characteristics of the Xiaojiang fault in highway tunnel of wakeamo - Bin Li; Qiang Xu; Qiang Cheng; Chong-De Feng; Hu Zhao; Jian-Hua Yu; Tian-Xiang Liu (Applied Geophysics, 2023)

Three Types of Enteromorpha prolifera Bio-Products Based on Different Processing Procedures as Feed Additives in the Diets of Pacific White Shrimp (Litopenaeus vannamei) - Zhibin Zhou; Lubo Wang; Mingqin Dai; Qingyan Gao; Peng Wang; Lili Zhao; Yanlu Li; Rui Xi; Mingchao Pan; Qiang Ma; Houguo Xu; Mengqing Liang; et al. (Fishes, 2023)
A feeding trial was conducted to evaluate the biological activities of Enteromorpha prolifera bio-products in the diets of Pacific white shrimp (Litopenaeus vannamei). Bio-products of E. prolifera included E. prolifera meal, E. prolifera hydrolysate and E. prolifera polysaccharide, which was supplied using different processing procedures. The control diet was supplemented without any E. prolifera bio-products or dietary attractants. Experimental diets were formulated to contain 0.2% and 0.4% of E. prolifera hydrolysate (EPH0.2% and EPH0.4%), 0.03% of E. prolifera polysaccharide (EPP0.03%), 3% of E. prolifera meal (EPM3%), 0.1% of dimethyl-β-propiothetn (DMPT0.1%) and 1% of squid paste (SP1%). Shrimp (~8 g) were randomly distributed in 21 tanks and fed for 44 days. Feed intake showed that 3% of E. prolifera meal and 0.4% of E. prolifera hydrolysate in diets exhibited similar attractant effects as 0.1% of DMPT. Gross qualitative observation showed that the abundance of lipid droplets decreased in hepatopancreas of the EPH0.4% and EPM3% groups, which were supported by hepatopancreas triacylglycerol (TG), where significantly lower concentrations were observed in the EPH0.4% and EPM3% groups compared with the control group. Similarly, TG and low-density lipoprotein cholesterol in serum significantly decreased in the EPH0.4%, EPP0.03% and EPM3% groups compared to the control group. Supplemental E. prolifera bio-products resulted in significantly higher serum glutathione level of EPP0.03% or superoxide dismutase activities of EPH0.4% and EPM3%, but significantly lower serum malondialdehyde level of EPM3%. In addition, tnf-α expression in hepatopancreas was significantly down-regulated in shrimp fed the EPH0.2%, EPH0.4% and EPM3% diets. Based on survival analysis, E. prolifera bio-products improved the resistance of shrimp to hypoxic stresses. Thus, this study confirmed that bio-products of E. prolifera supplied using different processing procedures could be used to reduce the amount of E. prolifera in feed of shrimp without compromising their biological functions.

Observations on the embryonic development of the mud crab, Scylla paramamosain - Li-Kun Xu; Ke-Yi Ma; Feng-Ying Zhang; Wei Wang; Ling-Bo Ma; Zhong-Wen Jin; Ming Zhao; Wei Chen; Yin Fu; Chun-Yan Ma; Zhi-Qiang Liu (Frontiers in Marine Science, 2023)
To investigate the embryonic development of the mud crab Scylla paramamosain , we analyzed three critical parameters: egg color of, embryo morphology (through conventional and laser scanning confocal microscopy), and the distribution of cell divisions. During embryonic development, the egg color exhibited a progressive transition, shifting from orange to reddish-orange, then to brown, before ultimately darkening to black. Each embryo displayed a spherical shape, measuring approximately 280 μm in diameter, characterized by a smooth surface devoid of any depressions. The embryonic cell division was in the form of mixed oogenesis, comprised of complete division in the early stage, spiral oogenesis in the middle stage and surface division in the late stage. It is noteworthy that the blastopore appeared at the position where the transparent area and cell aggregation just appeared under the microscope, and the blastomere was a characteristic of the embryo entering the gastrulation stage. After entering the gastrulation stage, the cells aggregated towards the blastopore and formed two symmetrical cell clusters, which formed a V-shape with the void of the classic blastopore. When the transparent region occupied approximately 1/5 of the embryo ’ s volume, the embryo entered the nauplius stage, and the thoracic and abdominal armor, as well as the optic lobe and abdominal limb primordia, could be clearly distinguished. The appearance of the compound eye pigment band indicated the stage of compound eye pigment formation. At this time, the transparent area accounted for 1/4 of the embryo and a large number of ganglia appeared. The change of the compound eye pigment band from red to black was also one of the reasons for the blackening of the egg color of the crabs. The data obtained through this study have potential applications in the determination of embryonic development status and obtaining of high-quality seeds for S. paramamosain culture.

A lightweight deep learning model for ocean eddy detection - Haochen Sun; Hongping Li; Ming Xu; Fan Yang; Qiang Zhao; Cuishu Li (Frontiers in Marine Science, 2023)
Ocean eddies are typical oceanic mesoscale phenomena that are numerous, widely distributed and have high energy. Traditional eddy detection methods are mainly based on physical mechanisms with high accuracy. However, the large number of steps and complex parameter settings limit their applicability for most users. With the rapid development of deep learning techniques, object detection models have been broadly used in the field of ocean remote sensing. This paper proposes a lightweight eddy detection model, ghost eddy detection YOLO (GED-YOLO), based on sea level anomaly data and the “You Only Look Once” (YOLO) series models. The proposed model used ECA+GhostNet as the backbone network and an atrous spatial pyramid pooling network as the feature enhancement network. The ghost eddy detection path aggregation network was proposed for feature fusion, which reduced the number of model parameters and improved the detection performance. The experimental results showed that GED-YOLO achieved better detection precision and smaller parameter size. Its mAP was 95.11% and the parameter size was 22.56 MB. In addition, the test experiment results showed that GED-YOLO had similar eddy detection performance and faster detection speed compared to the traditional physical method.

Efficient rhodamine B dye degradation by red mud-grapefruit peel biochar catalysts activated persulfate in water - Shuman Deng; Maolin Yang; Qiang An; Zheng Li; Bin Zhao; Binbin Ran (Environmental Science and Pollution Research, 2023)

First principles insights into the interaction mechanism of iron doped thermally activated kaolinite with Cd and Pb pollutants in organic solid waste incineration flue gas - Yang-wen Wu; Rong Guo; Li-juan Sun; Xin-yue Zhou; Jia-le Zhou; Hai-yuan Zhao; Yi-fei Yu; Zhuang Hu; Bin Hu; Ji Liu; Bing Zhang; Li Zhao; et al. (Waste Management, 2023)

Under flooding conditions, controlled-release fertiliser coated microplastics affect the growth and accumulation of cadmium in rice by increasing the fluidity of cadmium and interfering with metabolic pathways - Meng Zhao; Congping Li; Cheng Zhang; Yujie Zhao; Xuexia Wang; Bing Cao; Li Xu; Jiajia Zhang; Jiachen Wang; Qiang Zuo; Yanhua Chen; Guoyuan Zou (Science of The Total Environment, 2023)

Dual roles of the Arabidopsis PEAT complex in histone H2A deubiquitination and H4K5 acetylation - Si-Yao Zheng; Bin-Bin Guan; Dan-Yang Yuan; Qiang-Qiang Zhao; Weiran Ge; Lian-Mei Tan; Shan-Shan Chen; Lin Li; She Chen; Rui-Ming Xu; Xin-Jian He (Molecular Plant, 2023)

Sustainable management of water, nitrogen and biochar resources for soybean growth considering economic, environmental and resource use efficiency aspects: An integrated modeling approach - Pingan Zhang; Lu Li; Qiang Fu; Zhonglili Zhang; Haiyan Li; Li Zhao; Wuyuan Liu; Yijia Wang; Mo Li; Aizheng Yang (Journal of Cleaner Production, 2023)

Integrating Cr doped FeOOH into FeSe2 nanoparticles for efficient water oxidation at large current densities - Jinwei Wang; Yiquan Xiang; Weiyi Zhang; Yijie Zhang; Qiang Zhao; Jinping Li; Guang Liu (Fuel, 2023)

Release of dissolved organic matter from wetland plants and its interaction with polycyclic aromatic hydrocarbons - Qian Wang; LuXing Liu; JingTao Xu; Yue Guo; Qiang Kong; WenYing Li; Zhen Hu; JiaTong Wang; HuanXin Zhang; Jian Zhang; CongCong Zhao (Environmental Research, 2023)

A state-of-the-art analysis of pharmacological delivery and artificial intelligence techniques for inner ear disease treatment - Wanqing Li; Nan Zheng; Qiang Zhou; Mohammed S. Alqahtani; Dalia H. Elkamchouchi; Huajun Zhao; Sen Lin (Environmental Research, 2023)

Harnessing the radical potential of calcium-activated biochar for non-peroxide catalytic degradation of bisphenol S - Fulin Shao; Jingtao Xu; Xingsheng Kang; Qiang Su; Xinsheng Luo; Congcong Zhao; Jian Zhang; Meng Li; Jin Wang (Chemical Engineering Journal, 2023)

H2S cracking to produce H2 through microwave discharge catalysis of graphitized petroleum coke - Zhiyang Zhao; Dongqiang Cai; Juan Liu; Guifu Zou; Qiang Zhang; Zhanlong Song; Cuiping Wang; Longzhi Li (Chemical Engineering Journal, 2023)

Recycling polycarbonate wastes to prepare hydrophobic and super mechanically robust aerogels with excellent oil–water and emulsion separation performance - Xin Li; Zhendong Huang; Bowen Dai; Qiang Liu; Wei Huang; Chunxia Zhao; Hongbing Chen (Chemical Engineering Journal, 2023)

The modification of meteorological factors on the relationship between air pollution and periodontal diseases: an exploration based on different interaction strategies - Kai Huang; Lin-Fei Feng; Zhe-Ye Liu; Zhen-Hua Li; Yi-Cheng Mao; Xin-Qiang Wang; Jia-Wen Zhao; Kang-Di Zhang; Ying-Qing Li; Jie Wang; Wen-Jie Yu; Xin Cheng; et al. (Environmental Geochemistry and Health, 2023)

Investigation of Campbell mode with automatic calibration operated in fission chamber-based neutron flux monitoring system on EAST - Li Yang; Li-Qun Hu; Guo-Qiang Zhong; Hong-Rui Cao; Jin-Long Zhao; Yong-Qiang Zhang; Wei-Kun Chen (Annals of Nuclear Energy, 2023)

Spatial patterns and recent temporal trends in global transpiration modelled using eco-evolutionary optimality - Shijie Li; Guojie Wang; Chenxia Zhu; Marco Hannemann; Rafael Poyatos; Jiao Lu; Ji Li; Waheed Ullah; Daniel Fiifi Tawia Hagan; Almudena García-García; Yi Liu; Qi Liu; et al. (Agricultural and Forest Meteorology, 2023)

Integrated transcriptomic and metabolomic analyses identify key factors in the vitellogenesis of juvenile Sichuan bream (Sinibrama taeniatus) - Zhe Zhao; Qiang Zhao; Haoyu Wang; Lan Wei; Siya Wang; Shilin Li; Dengyue Yuan; Zhijian Wang (Frontiers in Marine Science, 2023)
Vitellogenesis is the most important stage of ovarian maturation in fish, involving the synthesis and transport of essential yolk substances and their complex mechanisms and coordination process. The liver is the main tissue involved in the vitellogenesis of oviparous animals, but studies of vitellogenesis in fish rarely include the liver and ovary as a whole. The aim of this study was to explore the molecular mechanism and associated regulatory factors behind vitellogenesis in Sichuan bream ( Sinibrama taeniatus ). The different stages of oogenesis were first identified by successive histological observations. Then, ovary and liver tissues that developed to 115 days (stage II, previtellogenesis stage), 165 days (stage III, vitellogenesis stage) and 185 days (stage IV, late-vitellogenesis stage) were collected for transcriptomic and metabolomic analyses, and serum testosterone (T), 17β-estradiol (E 2 ), vitellogenin (Vtg), triiodothyronine (T 3 ), and thyroxine (T 4 ) levels were measured at the corresponding stages. We found that energy redistribution during vitellogenesis is mainly regulated through glycolysis, fatty acid biosynthesis and the citrate cycle pathway. In the liver, energy metabolism was promoted by activating glucolipid metabolic pathways to provide sufficient ATP, but at the same time, the ovary tends to retain nutrients rather than decompose them to produce energy. In addition, we have identified several key factors involved in the metabolism of neutral lipids, polar lipids, amino acids and vitamins, which are involved in the assembly and transport of important yolk nutrients. The initiation of vitellogenesis was found to be associated with a surge in serum E 2 levels, but the sustained increase in Vtg levels in the late stage may be due more to upregulation of the estrogen receptor. These results provide valuable information about the regulation of ovarian development in cultured fish.

Comprehensive competitiveness assessment of four typical municipal sludge treatment routes in China based on environmental and techno-economic analysis - Yanqin Huang; Yuhang Zhen; Lanling Liu; Xiaoyang Ning; Chenzhou Wang; Kai Li; Li Zhao; Qiang Lu (Science of The Total Environment, 2023)

Metal ion assistant transformation strategy to synthesize catechol-based metal–organic frameworks from Ti3C2T precursors - Weikang Wang; Yan Bai; Pin Yang; Shuai Yuan; Feiyang Li; Weiwei Zhao; Beibei Jin; Xuan Zhang; Shujuan Liu; Daqiang Yuan; Qiang Zhao (Science Bulletin, 2023)

Pb-Zn mineralization formed from coupled hydrocarbon-bearing and hydrothermal fluids in the Ediacaran strata in the central Sichuan Basin, China - Lianqiang Zhu; Zezhang Song; Guangdi Liu; Wenzhi Zhao; Long Wen; Xingwang Tian; Wenzhi Wang; Dailin Yang; Wei Yan; Qiang Li (Precambrian Research, 2023)

Long-chain propagation pathways from meteorological to hydrological, agricultural and groundwater drought and their dynamics in China - Zhiming Han; Shengzhi Huang; Jing Zhao; Guoyong Leng; Qiang Huang; Hongbo Zhang; Zhi Li (Journal of Hydrology, 2023)

Discovery of new strains for furfural degradation using adaptive laboratory evolution in Saccharomyces cerevisiae - Hanyu Wang; Qian Li; Zhengyue Zhang; Ellen Ayepa; Quanju Xiang; Xiumei Yu; Ke Zhao; Likou Zou; Yunfu Gu; Xi Li; Qiang Chen; Xiaoping Zhang; et al. (Journal of Hazardous Materials, 2023)

BK-SWMM flood simulation framework is being proposed for urban storm flood modeling based on uncertainty parameter crowdsourcing data from a single functional region - Chengshuai Liu; Wenzhong Li; Chenchen Zhao; Tianning Xie; Shengqi Jian; Qiang Wu; Yingying Xu; Caihong Hu (Journal of Environmental Management, 2023)

Study on photodissociation and photoconversion characteristics of CS2 in O2/O3 environment using real-time conversion products obtained by UV-DOAS - Jie Gao; Mu Li; Huan Zhao; Yongqi Wu; Qiang Gao; Xijun Wu; Yucun Zhang; Yungang Zhang (Journal of Environmental Chemical Engineering, 2023)

Removal of toluene using an integrative DBD/Absorption reactor: Feasibility and mechanism - Li-qiang Qi; Qi-hao Chen; Wei-yuan Zhao; Shuai Zhao; Jing-xin Li; Feng Liu (Journal of Environmental Chemical Engineering, 2023)

Optimization and validation of an oxidation and solid-phase extraction procedure for analysis of imidacloprid and its metabolites in cereals using ultra-performance liquid chromatography tandem mass spectrometry - Tan Wang; Yueliang Zhao; Songhan Zhang; Lin Ma; Qiang Sun; Li Zhao; Weimin Wang; Maofeng Dong (Food Control, 2023)

Influence of nitrogen sources on wastewater treatment performance by filamentous algae in constructed wetland system - Congcong Zhao; Wenying Li; Dawei Shang; Qilong Ma; Luxing Liu; Jingtao Xu; Jiashuo Meng; Tao Zhang; Qian Wang; Xiaofei Wang; Jian Zhang; Qiang Kong (Environmental Research, 2023)

An amphibolitic source for “adakitic” I-type plutons in continental collision zones - Qi-Wei Li; Oliver Nebel; Jun-Hong Zhao; Rui Wang; Yona Jacobsen; Marianne Richter; Qiang Wang; Peter A. Cawood (Earth and Planetary Science Letters, 2023)

A major QTL simultaneously increases the number of spikelets per spike and thousand-kernel weight in a wheat line - Conghao Zhao; Jieguang Zhou; Cong Li; Jianing You; Yanling Liu; Huaping Tang; Mei Deng; Qiang Xu; Yazhou Zhang; Qiantao Jiang; Guoyue Chen; Pengfei Qi; et al. (Theoretical and Applied Genetics, 2023)

Climatic controls on stable carbon and nitrogen isotope compositions of temperate grasslands in northern China - Yuntao Wu; Xiaodong Zhang; Zhaoliang Song; Changxun Yu; Man Liu; Yidong Wang; Qian Hao; Qiang Li; Xiangwei Zhao; Lele Wu; Xia Wang (Plant and Soil, 2023)

TAT-PEP Alleviated Cognitive Impairment by Alleviating Neuronal Mitochondria Damage and Apoptosis After Cerebral Ischemic Reperfusion Injury - Pin Zhao; Jiapo Zhang; JianKe Kuai; Liya Li; Xuying Li; Namin Feng; Hailiang Du; Chen Li; Qiang Wang; Bin Deng (Molecular Neurobiology, 2023)
Paired immunoglobulin-like receptor B (PirB) was identified as a myelin-associated inhibitory protein (MAIP) receptor that plays a critical role in axonal regeneration, synaptic plasticity and neuronal survival after stroke. In our previous study, a transactivator of transcription-PirB extracellular peptide (TAT-PEP) was generated that can block the interactions between MAIs and PirB. We found that TAT-PEP treatment improved axonal regeneration, CST projection and long-term neurobehavioural recovery after stroke through its effects on PirB-mediated downstream signalling. However, the effect of TAT-PEP on the recovery of cognitive function and the survival of neurons also needs to be investigated. In this study, we investigated whether pirb RNAi could alleviate neuronal injury by inhibiting the expression of PirB following exposure to oxygen–glucose deprivation (OGD) in vitro. In addition, TAT-PEP treatment attenuated the volume of the brain infarct and promoted the recovery of neurobehavioural function and cognitive function. This study also found that TAT-PEP exerts neuroprotection by reducing neuronal degeneration and apoptosis after ischemia–reperfusion injury. In addition, TAT-PEP improved neuron survival and reduced lactate dehydrogenase (LDH) release in vitro. Results also showed that TAT-PEP reduced malondialdehyde (MDA) levels, increased superoxide dismutase (SOD) activity and reduced reactive oxygen species (ROS) accumulation in OGD-injured neurons. The possible mechanism was that TAT-PEP could contribute to the damage of neuronal mitochondria and affect the expression of cleaved caspase 3, Bax and Bcl-2. Our results suggest that PirB overexpression in neurons after ischaemic-reperfusion injury induces neuronal mitochondrial damage, oxidative stress and apoptosis. This study also suggests that TAT-PEP may be a potent neuroprotectant with therapeutic potential for stroke by reducing neuronal oxidative stress, mitochondrial damage, degeneration and apoptosis in ischemic stroke.

Population pharmacokinetics of topiramate in Chinese children with epilepsy - Shifeng Wei; Xingmeng Li; Qiang Zhang; Han Wu; Yun Wu; Zhigang Zhao; Shenghui Mei; Weixing Feng (European Journal of Clinical Pharmacology, 2023)

Comparative transcriptome profiling reveals RNA splicing alterations and biological function in patients exposed to occupational noise - Jia-Wei Chen; Jun-Jie Shao; Shao-Fei Zhao; Pei-Heng Lu; Si-Yu Li; Hao Yuan; Peng-Wei Ma; Yu-Qiang Lun; Wei-Long Wang; Rui Liang; Wei Gao; Qian Yang; et al. (Environmental Science and Pollution Research, 2023)

Biodegradability enhancement of waste lubricating oil regeneration wastewater using electrocoagulation pretreatment - Li-li Shan; Zhao Tan; Yu Chen; Ruo-shan Wang; Meng Zhang; Chang-long Pang; Yu-Hong Cui; Zhi-min Liao; Hong-qiang Ma; Ze-bing Zhu (Environmental Science and Pollution Research, 2023)

Molecular interaction mechanisms and cellular response of superoxide dismutase and catalase to fluoranthene - Yan Song; Kailun Sun; Qiang Zhao; Yuze Li; Guiqing Liu; Rutao Liu (Environmental Science and Pollution Research, 2023)

Expression patterns of volatile compounds during ‘FL 47′ tomato ripening and their response to exogenous methyl salicylate (MeSA) fumigation - Luting Jia; Li Wang; Qiang Xia; Weiqi Luo; Elizabeth A. Baldwin; Xu Zhang; Li Jiang; Jian Li; Yadong Zhao; Xin Qiao; Zhaoxin Cao; Libin Wang; et al. (Postharvest Biology and Technology, 2023)

Analytical solutions of flow velocity profile based on the morphological response of flexible vegetation - Wei-Jie Wang; Yan-Fang Zhao; Shi Ren; Xiao-Bo Liu; Fei Dong; Jin-Jin Li; Jing-Jing Fan; Wen-Qiang Wu (Journal of Hydrology, 2023)

A novel bacterial combination for efficient degradation of polystyrene microplastics - Peng Xiang; Yunfeng Zhang; Ting Zhang; Qian Wu; Changsong Zhao; Qiang Li (Journal of Hazardous Materials, 2023)

Uncovering the virome and its interaction with antibiotic resistome during compost fertilization - Qingxia Zhang; Lei Zhou; Yilong Zhao; Shuhong Gao; Yanjun Yang; Qingyun Chen; Wenhui Li; Qi Qi; Qiang Dong; Jiesi Lei; Xue Guo; Qun Gao; et al. (Journal of Hazardous Materials, 2023)

A review of recent earthquake-induced landslides on the Tibetan Plateau - Bo Zhao; Lijun Su; Qiang Xu; Weile Li; Chong Xu; Yunsheng Wang (Earth-Science Reviews, 2023)

Treatment of Dyes Wastewater by the Catalytic Wet Persulfate Oxidation Process in Reactors Using Red Mud Combined with Biochar as Catalyst - Shuman Deng; Zheng Li; Qiang An; Meng Tang; Chenlu Liu; Zihao Yang; Bohan Xu; Bin Zhao (Water, Air, & Soil Pollution, 2023)

Neuroprotective effect of salidroside on hippocampal neurons in diabetic mice via PI3K/Akt/GSK-3β signaling pathway - Xue-Hua Wang; Zhong-Fu Zuo; Lu Meng; Qi Yang; Pan Lv; Li-Pan Zhao; Xiao-Bai Wang; Yu-Fei Wang; Ying Huang; Cong Fu; Wen-Qiang Liu; Xue-Zheng Liu; et al. (Psychopharmacology, 2023)

Retraction Note: MiR-519d-3p enhances the sensitivity of non-small-cell lung cancer to tyrosine kinase inhibitors - Qiang Zhen; Yaxiao Zhang; Lina Gao; Renfeng Wang; Weiwei Chu; Xiaojian Zhao; Zhe Li; Huixian Li; Bing Zhang; Baolei Lv; Jiabao Liu (Mammalian Genome, 2023)

Effect and Mechanism of Sodium Butyrate on Neuronal Recovery and Prognosis in Diabetic Stroke - Ting-ting Li; Deng-ming Zhao; Yu-ting Wei; Jing-bo Li; Xue-fei Li; Qiang Wan; Xin Zhang; Xiang-nan Liu; Wan-chao Yang; Wen-zhi Li (Journal of Neuroimmune Pharmacology, 2023)

Effect of gaseous pollutant and greenness exposure on mortality during treatment of newly treated tuberculosis patients: a provincial population-based cohort study - Jia-Wen Zhao; Xin-Qiang Wang; Zhen-Hua Li; Yi-Cheng Mao; Sun Zhang; Kai Huang; Cheng-Yang Hu; Xiu-Jun Zhang; Xiao-Hong Kan (Environmental Science and Pollution Research, 2023)

Dihydromyricetin attenuates cisplatin-induced acute kidney injury by reducing oxidative stress, inflammation and ferroptosis - Zheming Xu; Minjing Zhang; Wenwen Wang; Suhan Zhou; Minghua Yu; Xingyu Qiu; Shan Jiang; Xiaohua Wang; Chun Tang; Shuijie Li; Chih-Hong Wang; Runzhi Zhu; et al. (Toxicology and Applied Pharmacology, 2023)

A complete assembly of the rice Nipponbare reference genome - Lianguang Shang; Wenchuang He; Tianyi Wang; Yingxue Yang; Qiang Xu; Xianjia Zhao; Longbo Yang; Hong Zhang; Xiaoxia Li; Yang Lv; Wu Chen; Shuo Cao; et al. (Molecular Plant, 2023)

Excellent, steady and economical nitrogen removal in highly variable mining wastewater via three-stage partial-denitrification/partial-nitrification/anammox system: A pilot-scale demonstration - Hao Su; Yukun Deng; Jiejun Zhao; Chen Lai; Longwen Xiao; Shengliang Li; Jianwei Zhao; Qiang Luo; Dachao Zhang; Bingyan Dong (Journal of Water Process Engineering, 2023)

Coalescence of As(II) with •OH: The pivot for co-processing of As(III) and butyl xanthate - Zihan Shu; Rongliang Qiu; Yetao Tang; Nan Zhao; Qiang Chen; Hailan Yang; Hong Li; Yuanyuan Deng; Shaobo Liu; Yanling Gu; Xiaofei Tan (Journal of Hazardous Materials, 2023)

Physical and chemical evaluation of adhesion recovery property of aged high-viscosity asphalt based on specialized composite rejuvenators - Wenxuan Zhang; Qiang Li; Jiaqing Wang; Zili Zhao; Dongzhao Jin (Journal of Cleaner Production, 2023)

Breakup mechanism of the northern South China Sea: Evidence from the deep crustal structure across the continent-ocean transition - Qiang Wang; Minghui Zhao; Jiazheng Zhang; Haoyu Zhang; Jean-Claude Sibuet; Zizheng Li; Enyuan He; Xuelin Qiu; Wen Peng; Guizhong Chen (Gondwana Research, 2023)

Organic matter enrichment and palaeoenvironmental comparison of Alinian fine-grained sedimentary rocks in lake facies - Delu Li; Qianyang He; Haibin Li; Jianwen Gao; Xiaochen Zhao; Qiang Sun; Shaofei Wang; Tao Xue (Gas Science and Engineering, 2023)

Preparation and characterization of novel composite nanoparticles using zein and hyaluronic acid for efficient delivery of naringenin - Genyang Ye; Tianlong Wu; Zhaohua Li; Manlin Teng; Lixue Ma; Mengdi Qin; Peixu Zhao; Qiang Fu (Food Chemistry, 2023)

Role of dietary tea polyphenols on growth performance and gut health benefits in juvenile hybrid sturgeon () - Zhenxin Zhao; Fei Zhao; Zhuoma Cairang; Zhou Zhou; Qiang Du; Jinle Wang; Feng Zhao; Qifu Wang; Zhengyou Li; Xiaoping Zhang (Fish & Shellfish Immunology, 2023)

Remote sensing for landslide investigations: A progress report from China - Qiang Xu; Bo Zhao; Keren Dai; Xiujun Dong; Weile Li; Xing Zhu; Yinghui Yang; Xianxuan Xiao; Xin Wang; Jian Huang; Huiyan Lu; Bo Deng; et al. (Engineering Geology, 2023)

Adsorption behavior of antibiotics with different structures onto vivianite in the presence of dissolved organic matter during the phosphorus recovery process - Wang-Xiao Jia; Wen-Qiang Li; Zhi-Hui Xie; Pu-Can Guo; Zhi-Long Ye; Zhao-Kun Xiong; Chuan-Shu He; Bo Lai (Chemical Engineering Journal, 2023)

Understanding the restructuring and degradation of oxide-derived copper during electrochemical CO2 reduction - Dazhong Zhong; Dongfang Cheng; Qiang Fang; Yi Liu; Jinping Li; Qiang Zhao (Chemical Engineering Journal, 2023)

Impact of Stefan flow on the interphase scalar transfer in flow past random particle arrays - Xiao Chen; Yuxuan Zhao; Shaohua Du; Li Zhao; Qiang Zhou (Chemical Engineering Journal, 2023)

Liquid flow fuel cell with an electrodeposition-modified nickel foam anode for efficient oxidation of 5-hydroxymethylfurfural to produce 2, 5-furandicarboxylic acid with co-generation of electricity - Ye Qiang; Denghao Ouyang; Li You; Dehua Liu; Xuebing Zhao (Chemical Engineering Journal, 2023)

Rockfall feature investigation and kinematic simulation based on nap-of-the-object photogrammetry and GIS spatial modeling - Xude Li; Fu-zhen Liu; Li Zhao; Na Deng; Long Chen; Jing-shen Pan; Guo-qiang Tang (Natural Hazards, 2023)

Straw return counteracts the negative effects of warming on microbial community and soil multifunctionality - Gong Wu; Jun Ling; De-Qiang Zhao; Zi-Xi Liu; Yi-Ping Xu; Yakov Kuzyakov; Karina Marsden; Yuan Wen; Shun-Li Zhou (Agriculture, Ecosystems & Environment, 2023)

Effect of flue gas components on the removal of cadmium pollutants by transition metal-modified activated carbon: Density functional theory and thermodynamic study - Xin-Yue Zhou; Jia-Le Zhou; Rong Guo; Yin-jie Liu; Yi-fei Yu; Bing Zhang; Yang-Wen Wu; Li Zhao; Qiang Lu (Fuel, 2023)

Steam reforming of biomass gasification tar over Ni-based catalyst supported by TiO2-SiO2 composite - Ming-xin Xu; Zi-shu Liu; Xin-yu Zhang; Jin-yi Di; Xiang-xi Meng; Li Zhao; Qiang Lu (Fuel, 2023)

A series of bifunctional ReBaCo2O5+ perovskite catalysts towards intermediate-temperature oxygen reduction reaction and oxygen evolution reaction - Lin Li; Ziwei Dong; Tian Xia; Xiang Li; Qiang Li; Liping Sun; Hui Zhao; Lihua Huo (Chemical Engineering Journal, 2023)

Experimental and DEM simulations of the mechanical properties of rock under freeze–thaw cycles - Jun Yu; Qiang Zhang; Chaojun Jia; Mingfeng Lei; Chenyang Zhao; Ruifeng Pang; Zong Li; Tao Zeng (Cold Regions Science and Technology, 2023)

Panicle removal delays plant senescence and enhances vegetative growth improving biomass production in switchgrass - Chunqiao Zhao; Yuesen Yue; Juying Wu; John Scullion; Qiang Guo; Qinghai Wang; Cui Li; Xiuyun Wan; Xincun Hou; Xifeng Fan (Biomass and Bioenergy, 2023)

Network prediction of surgical complication clusters: a prospective multicenter cohort study - Xiaochu Yu; Peng Wu; Zixing Wang; Wei Han; Yuguang Huang; Shijie Xin; Qiang Zhang; Shengxiu Zhao; Hong Sun; Guanghua Lei; Taiping Zhang; Luwen Zhang; et al. (Science China Life Sciences, 2023)

Quantifying the effects of nonlinear trends of meteorological factors on drought dynamics - Wenwen Guo; Shengzhi Huang; Yong Zhao; Guoyong Leng; Xianggui Zhao; Pei Li; Mingqiu Nie; Qiang Huang (Natural Hazards, 2023)

Pollution characteristics and human health risks of PM2.5-bound heavy metals: a 3-year observation in Suzhou, China - Xiaolong Zhou; Mengmeng Xie; Minxian Zhao; Ying Wang; Jia Luo; Songwen Lu; Jie Li; Qiang Liu (Environmental Geochemistry and Health, 2023)

Fluorescence Properties and Chemical Composition of Fine Particles in the Background Atmosphere of North China - Ping Li; Siyao Yue; Xiaoyang Yang; Di Liu; Qiang Zhang; Wei Hu; Shengjie Hou; Wanyu Zhao; Hong Ren; Gang Li; Yuanguan Gao; Junjun Deng; et al. (Advances in Atmospheric Sciences, 2023)

Combining multi-isotope technology, hydrochemical information, and MixSIAR model to identify and quantify nitrate sources of groundwater and surface water in a multi-land use region - Wanning Zhao; Deqing Yang; Qiang Sun; Yandong Gan; Liyong Bai; Shuangshuang Li; Dongmei Liu; Jiulan Dai (Environmental Science and Pollution Research, 2023)

A posture-based measurement adjustment method for improving the accuracy of beef cattle body size measurement based on point cloud data - Jiawei Li; Weihong Ma; Qiang Bai; Dan Tulpan; Minglun Gong; Yi Sun; Xianglong Xue; Chunjiang Zhao; Qifeng Li (Biosystems Engineering, 2023)

Comparative in vitro and in silico study on the estrogenic effects of 2,2-bis(4-chlorophenyl)ethanol, 4,4′-dichlorobenzophenone and DDT analogs - Li Wang; Lantian Zhou; Longyu Liu; Yu Yang; Qiang Zhao (Science of The Total Environment, 2023)

Sulfur-induced electronic optimization of Mo5N6 for hydrogen evolution through topochemical substitution - Jianmei Chen; Xiaochun Liu; Hao Wang; Chao-Lung Chiang; Pengfei Hou; Jianmin Li; Huanyu Jin; Shujuan Liu; Xing Meng; Yan-Gu Lin; Jong-Min Lee; Qiang Zhao (Chemical Engineering Journal, 2023)

Coupling doping and localized surface plasmon resonance toward acidic pH-preferential catalase-like nanozyme for oxygen-dominated synergistic cancer therapy - Yuqing Rao; Guopeng Xu; Zhihua Zhang; Weijie Wang; Chengmei Zhang; Mingwen Zhao; Yuanyuan Qu; Weifeng Li; Min Ji; Yanguo Liu; Yong-Qiang Li (Chemical Engineering Journal, 2023)

Crystallographic oriented plating by using lithiophilic ionic additives in carbonate electrolyte for enabling high voltage lithium metal batteries - Qiwen Ran; Jintao Liu; Lei Li; Qiang Hu; Fuquan Nie; Hongyuan Zhao; Xingquan Liu (Chemical Engineering Journal, 2023)

Effects of adsorption characteristics of carbocatalysts on persulfate-based advanced oxidation processes: Organic removal mechanisms and optimization strategies - Xiang-Feng Huang; Jing-Xi Yuan; Xia Zhao; Shuang-Qiang Li; Li-Heng Yang; Wen-Yan Li; Kai-Ming Peng; Chen Cai; Jia Liu (Chemical Engineering Journal, 2023)

A Genome-Wide Association Study for Susceptibility to Axial Length in Highly Myopic Eyes - Qiang Lu; Yu Du; Ye Zhang; Yuxi Chen; Hao Li; Wenwen He; Yating Tang; Zhennan Zhao; Yinglei Zhang; Jihong Wu; Xiangjia Zhu; Yi Lu (Phenomics, 2023)

Constructing a region-specific rheological parameter database for probabilistic run-out analyses of loess flowslides - Peng Zeng; Lin Zhang; Tianbin Li; Xiaoping Sun; Liangfu Zhao; Xiujun Dong; Qiang Xu (Landslides, 2023)

Cropland abandonment alleviates soil carbon emissions in the North China Plain - Lingjie Lei; Ying Li; Zhenxing Zhou; Na Li; Cancan Zhao; Qiang Li (Environmental Monitoring and Assessment, 2023)

Bergamotane-type sesquiterpenes from the leaves and twigs of Illicium oligandrum and their anti-inflammatory activities - Wen-Rui Li; Jia-Ying Zhao; Mi Li; Xiao-Jing Wang; Guo-Zhu Su; Hai-Qiang Wang; Li Li; Guan-Hua Du; Ru-Bing Wang; Shuang-Gang Ma (Phytochemistry, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Insights into Regulating Mechanism of Mutagenesis Strains of Elizabethkingia meningoseptica sp. F2 by Omics Analysis - Qiang Yang; Zhiming Zheng; Peng Wang; Li Wang; Han Wang; Mengxue Zhang; Genhai Zhao (Current Microbiology, 2023)

Identification of DNA methylation and genetic alteration simultaneously from a single blood biopsy - Xiaomin Chen; Jiahui Liu; Jun Li; Yinpeng Xie; Zichen Yu; Lu Shen; Qingfeng Liu; Wei Wu; Qiang Zhao; Haoxiang Lin; Gaotong Liu; Qiuping Luo; et al. (Genes & Genomics, 2023)

Elastic wave velocity of marine sediments with free gas: Insights from CT-acoustic observation and theoretical analysis - Jie Chen; Gaowei Hu; Qingtao Bu; Nengyou Wu; Changling Liu; Qiang Chen; Chengfeng Li; Yizhao Wan; Zihao Wang; Wengao Zhao; Jiale Kang; Jiafang Xu (Marine and Petroleum Geology, 2023)

Pyridine N of N/Co-co-doped graphite gas diffusion electrode facilitating the efficient production of hydroxyl radicals in the electro-peroxone process - Qiang Bi; Sisi Jiang; Changfeng Hu; Li Zhang; Yilin Zhao; Bo Yang; Guoping Li; Juanqin Xue (Journal of Environmental Chemical Engineering, 2023)

Heavy metal contamination and risk assessment in winter jujube (Ziziphus jujuba Mill. cv. Dongzao) - Min Xu; Qiusheng Chen; Xiabing Kong; Lingxi Han; Qiang Zhang; Qingjun Li; Bianqing Hao; Xubo Zhao; Lu Liu; Haoliang Wan; Jiyun Nie (Food and Chemical Toxicology, 2023)

Green manure and maize intercropping with reduced chemical N enhances productivity and carbon mitigation of farmland in arid areas - Hanting Li; Zhilong Fan; Qiming Wang; Guocui Wang; Wen Yin; Cai Zhao; Aizhong Yu; Weidong Cao; Qiang Chai; Falong Hu (European Journal of Agronomy, 2023)

In situ rapid and deep self-reconstruction of Fe-doped hydrate NiMoO4 for stable water oxidation at high current densities - Yijie Zhang; Rui Yao; Yun Wu; Qiang Zhao; Jinping Li; Guang Liu (Chemical Engineering Journal, 2023)

Free-standing [0 0 1]-oriented one-dimensional crystal-structured antimony selenide films for self-powered flexible near-infrared photodetectors - Xixing Wen; Zonghuan Lu; Bingxiang Li; Gwo-Ching Wang; Morris A. Washington; Qiang Zhao; Toh-Ming Lu (Chemical Engineering Journal, 2023)

A 90-Day Prognostic Model Based on the Early Brain Injury Indicators after Aneurysmal Subarachnoid Hemorrhage: the TAPS Score - Runting Li; Fa Lin; Yu Chen; Junlin Lu; Heze Han; Li Ma; Yahui Zhao; Debin Yan; Ruinan Li; Jun Yang; Shihao He; Zhipeng Li; et al. (Translational Stroke Research, 2023)

Identification of a suppressor for the wheat stripe rust resistance gene Yr81 in Chinese wheat landrace Dahongpao - Huiling Jin; Haipeng Zhang; Xuyang Zhao; Li Long; Fangnian Guan; Yunpeng Wang; Linyu Huang; Xiaoyue Zhang; Yuqi Wang; Hao Li; Wei Li; Zhien Pu; et al. (Theoretical and Applied Genetics, 2023)

Beneficial effects of red and blue light on potato leaf antioxidant capacity and tuber bulking - Wei He; Qiang Chai; Dan Zhang; Wenli Li; Cai Zhao; Wen Yin; Hong Fan; Aizhong Yu; Falong Hu; Zhilong Fan (Physiology and Molecular Biology of Plants, 2023)

Anti-tumor effect of novel amino acid Schiff base nickel (II) complexes on oral squamous cell carcinoma cells (CAL-27) in vitro - Peng Zhao; Haiming Qiu; Qiang Wei; Yang Li; Lei Gao; Peiran Zhao (Molecular & Cellular Toxicology, 2023)

Mantle magmatism, metamorphism and anatexis: evidence from geochemistry and zircon U–Pb-Hf isotopes of Paleoproterozoic S-type granites, Khondalite Belt of the North China Craton - Qiang Shi; Zhong-Yuan Xu; M Santosh; Ding Ding; Zhong-Hai Zhao; Chen Li; Xin Gao; Wenjie Ma; Yan Xu; Hui-Xuan Li; Chengran Yue (International Geology Review, 2023)

Associations of blood metals with liver function: Analysis of NHANES from 2011 to 2018 - Wenjie Li; Xinyan Li; Jing Su; Han Chen; Ping Zhao; Haisheng Qian; Xin Gao; Qiang Ye; Guoxin Zhang; Xuan Li (Chemosphere, 2023)

Assessment of greenhouse gases emissions and intensity from Chinese marine aquaculture in the past three decades - Congjun Xu; Guohuan Su; Kangshun Zhao; Huan Wang; Xiaoqi Xu; Ziqi Li; Qiang Hu; Jun Xu (Journal of Environmental Management, 2023)

Fractal characteristics of rocks and mesoscopic fractures at different loading rates - Yanming Lai; Kang Zhao; Zhiwei He; Xiang Yu; Yajing Yan; Qiang Li; Hai Shao; Xiangwei Zhang; Yun Zhou (Geomechanics for Energy and the Environment, 2023)

Shaking table tests and seismic assessment of a full-scale precast concrete sandwich wall panel structure with bolt connections - Jia-Xuan He; Zhao-Dong Xu; Lian-Yu Zhang; Zhi-Hua Lin; Zhong-Wei Hu; Qiang-Qiang Li; Yao-Rong Dong (Engineering Structures, 2023)

A tris(hydroxymethyl)aminomethane-modified polyimide membrane with efficient organic solvent resistant performance and high separation selectivity for dye/salt separation - Zitian Liu; Xuesong Deng; Ligang Lin; Rongrong Qiang; Qiying Wang; Qi Cheng; Jing Yang; Xu Yang; Wensong Ma; Xinyang Li; Meina Xu; Chunhong Wang; et al. (Desalination, 2023)

Top-down control of macrofauna: Are waterbirds passengers or drivers in wetlands? - Jianshe Chen; Chunming Li; Changlu Wu; Xuena Sun; Xuesong Feng; Jiayuan Zhao; Zhijun Ma; Jihua Wu; Mark D. Bertness; Bo Li; Qiang He (Biological Conservation, 2023)

Risk assessment of floor water inrush based on TOPSIS combined weighting model: a case study in a coal mine, China - Qiang Li; Cunjin Lu; Hui Zhao (Earth Science Informatics, 2023)

Distribution patterns of landslides triggered by the 2022 Ms 6.8 Luding earthquake, Sichuan, China - Jian-qiang Zhang; Zong-ji Yang; Qing-kai Meng; Jiao Wang; Kai-heng Hu; Yong-gang Ge; Feng-huan Su; Bo Zhao; Bo Zhang; Ning Jiang; Yu Huang; Zai-yang Ming; et al. (Journal of Mountain Science, 2023)

Metal-organic frameworks for high performance desalination through thickness control and structural fine-tuning - Meili Yuan; Jingyuan Wang; Yixiang Li; Mingwen Zhao; Yong-Qiang Li; Weifeng Li; Yuanyuan Qu (Water Research, 2023)

Enhancements of dissociation of electrode materials in spent lithium-ion batteries by low-temperature heating pretreatment - Si-qi Jiang; Chun-chen Nie; Shun-xiang Shi; Yong-qiang Zhao; Xiang-guang Li; Chao-zhu Deng; Lu Yang; Ling Zhang; Xiang-nan Zhu (Process Safety and Environmental Protection, 2023)

2000 years of lake-level fluctuations and human adaptation around China's largest freshwater lake - Huanye Wang; Weiguo Liu; Qin Leng; Lin Yang; Hui Zhao; Jun Yang; Yuwei Chen; Shangbin Xiao; Yunning Cao; Jing Hu; Xiaoke Qiang; Peng Cheng; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Effect of phenol formaldehyde-associated microplastics on soil microbial community, assembly, and functioning - Hu Li; Qiu-Ping Luo; Sha Zhao; Yan-Yan Zhou; Fu-Yi Huang; Xiao-Ru Yang; Jian-Qiang Su (Journal of Hazardous Materials, 2023)

Effect of thermal treatment on the flavor quality of Chinese spicy cabbage - Xiru Zhang; Hui Guan; Qiang Zhao; Hansheng Gong; Dacheng Wang; Ping Wang; Huamin Li; Wenli Liu (Food Control, 2023)

A Review and Perspective of Environmental Disinfection Technology Based on Microwave Irradiation - Liming Liu; Na Wang; Azhar Ali Laghari; Hong Li; Can Wang; Zhenyu Zhao; Xin Gao; Qiang Zeng (Current Pollution Reports, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Effects of multi-resource addition on grassland plant productivity and biodiversity along a resource gradient - Xinxin Guo; Xiaoan Zuo; Eduardo Medina-Roldán; Aixia Guo; Ping Yue; Xueyong Zhao; Jingjuan Qiao; Xiangyun Li; Min Chen; Cunzheng Wei; Tian Yang; Yuguang Ke; et al. (Science of The Total Environment, 2023)

Analysis of iron in-use stocks: Evidence from the provincial and municipal levels in China - Qiang Yue; Xicui Chai; Feng Zhao; Junhao He; Yun Li; Heming Wang (Resources Policy, 2023)

Variations in Asian summer monsoon and hydroclimate during Heinrich stadials 4 revealed by stalagmite stable isotopes and trace elements - Yao Wu; Ting-Yong Li; Jun-Yun Li; Hai Cheng; You-Feng Ning; Chuan-Chou Shen; Yan Yang; Jing-Yao Zhao; Chao-Jun Chen; Ming-Qiang Liang; Si-Ya Xiao; Hai-Ying Qiu; et al. (Quaternary Science Reviews, 2023)

Catalytic pyrolysis of spent bleaching clay for its regeneration and simultaneously producing aromatic hydrocarbons - Kai Li; Zhu-yu Li; Cheng-Bo Zhang; Jia-qi Zhao; Li Zhao; Ji Liu; Shan-wei Ma; Qiang Lu (Journal of Cleaner Production, 2023)

Heterojunction engineering of Ni3S2/NiS nanowire for electrochemical hydrogen evolution - Meng Chen; Qing Su; Nutthaphak Kitiphatpiboon; Juan Zhang; Changrui Feng; Shasha Li; Qiang Zhao; Abuliti Abudula; Yufei Ma; Guoqing Guan (Fuel, 2023)

A new multi-dimensional framework considering environmental impacts to assess green development level of cultivated land during 1990 to 2018 in China - Chaoqing Chai; Bangbang Zhang; Yuanyuan Li; Wenhao Niu; Weiwei Zheng; Xiangbin Kong; Qiang Yu; Minjuan Zhao; Xianli Xia (Environmental Impact Assessment Review, 2023)

Auxiliary thermodynamic analysis support capturing the differences in nanostructured FeVO4·nH2O electrodes between lithium and sodium ions storage mechanism - Linyi Zhao; Tiansheng Wang; Fei Li; Yongshuai Liu; Fengkai Zuo; Li Yang; Yifei Xu; Cunliang Zhang; Huaizhi Wang; Jie Liu; Xiaotong Dong; Shikai Zhu; et al. (Chemical Engineering Journal, 2023)

L-cysteine boosted Fe(III)-activated peracetic acid system for sulfamethoxazole degradation: Role of L-cysteine and mechanism - Yinhao Dai; Hui Cao; Chengdu Qi; Yijie Zhao; Yanni Wen; Chenmin Xu; Qiang Zhong; Dunyu Sun; Shuohua Zhou; Bing Yang; Shaogui Yang; Huan He; et al. (Chemical Engineering Journal, 2023)

Nitrogen removal by Rhodococcus sp. SY24 under linear alkylbenzene sulphonate stress: Carbon source metabolism activity, kinetics, and optimum culture conditions - Peizhen Chen; Jingli Wang; Jie lv; Qiang Wang; Chunxue Zhang; Wenjie Zhao; Shaopeng Li (Bioresource Technology, 2023)

Microbial production of valuable chemicals by modular co-culture strategy - Shuo Zhao; Fangfang Li; Fan Yang; Qianqian Ma; Liwen Liu; Zhaosong Huang; Xiangyu Fan; Qiang Li; Xiaoli Liu; Pengfei Gu (World Journal of Microbiology and Biotechnology, 2023)

Shading reduced the compensation and enhancement effects of soil nutrition on the growth of cotyledon-damaged Quercus acutissima seedlings - Haonan Chen; Mingming Zhao; Luyu Qi; Xinke Sun; Qiang Li; Xiao Liu; Ning Wang; Janusz J. Zwiazek; Wenqing Zhang; Weihua Guo; Renqing Wang; Fengyu Zhang; et al. (Plant and Soil, 2023)

Elevated systemic immune inflammation level increases the risk of total and cause-specific mortality among patients with chronic kidney disease: a large multi-center longitudinal study - Wenguang Lai; Yun Xie; Xiaoli Zhao; Xiayan Xu; Sijia Yu; Hongyu Lu; Haozhang Huang; Qiang Li; Jun-Yan Xu; Jin Liu; Shiqun Chen; Yong Liu (Inflammation Research, 2023)

Brevibacillus daliensis sp. nov., Isolated From Soil in Machangqing Nature Reserve - Shi-Qiang Ye; Jiang-Yuan Zhao; Le-Le Li; Cheng Ling; Meng-Yu Zhang; Jing Tang; Song-Guo Liang; Jian-Yu Li; Pei-Wen Yang; Jiao Xiong; Lu-Yao Feng; Zhu-Feng Shi; et al. (Current Microbiology, 2023)

The landscape of aging - Yusheng Cai; Wei Song; Jiaming Li; Ying Jing; Chuqian Liang; Liyuan Zhang; Xia Zhang; Wenhui Zhang; Beibei Liu; Yongpan An; Jingyi Li; Baixue Tang; et al. (Science China Life Sciences, 2022)

Visualizing Seizure Propagation in Freely-moving Mice via Miniature Two-photon Microscopy - Zhuoran Zhang; Shihe Jiang; Kaibin Shi; Yan Li; Wei-Na Jin; Qiang Liu; Ting Zhao; Heping Cheng; Fu-Dong Shi (Neuroscience Bulletin, 2022)

Lipocalin-2-Mediated Insufficient Oligodendrocyte Progenitor Cell Remyelination for White Matter Injury After Subarachnoid Hemorrhage via SCL22A17 Receptor/Early Growth Response Protein 1 Signaling - Qiang Li; Xufang Ru; Yang Yang; Hengli Zhao; Jie Qu; Weixiang Chen; Pengyu Pan; Huaizhen Ruan; Chaojun Li; Yujie Chen; Hua Feng (Neuroscience Bulletin, 2022)
Insufficient remyelination due to impaired oligodendrocyte precursor cell (OPC) differentiation and maturation is strongly associated with irreversible white matter injury (WMI) and neurological deficits. We analyzed whole transcriptome expression to elucidate the potential role and underlying mechanism of action of lipocalin-2 (LCN2) in OPC differentiation and WMI and identified the receptor SCL22A17 and downstream transcription factor early growth response protein 1 (EGR1) as the key signals contributing to LCN2-mediated insufficient OPC remyelination. In LCN-knockdown and OPC EGR1 conditional-knockout mice, we discovered enhanced OPC differentiation in developing and injured white matter (WM); consistent with this, the specific inactivation of LCN2/SCl22A17/EGR1 signaling promoted remyelination and neurological recovery in both atypical, acute WMI due to subarachnoid hemorrhage and typical, chronic WMI due to multiple sclerosis. This potentially represents a novel strategy to enhance differentiation and remyelination in patients with white matter injury.

Genome-Wide Identification Reveals the Potential Functions of the bZIP Gene Family in Common Bean (Phaseolus vulgaris) in Response to Salt Stress During the Sprouting Stage - Qi Zhang; Wen-jing Zhang; Zhen-gong Yin; Wei-jia Li; Chun-Yang Xia; Hao-Yue Sun; Yi-Ming Yang; Hong-Bin Wu; Shuo Zhang; Hao-hao Zhao; Wen-Hui Zhang; Yong-xia Guo; et al. (Journal of Plant Growth Regulation, 2022)

Geomorphic and tectonic controls of landslides induced by the 2022 Luding earthquake - Bo Zhao; Kai-heng Hu; Zong-ji Yang; Qiao Liu; Qiang Zou; Hua-yong Chen; Bo Zhang; Wei-feng Zhang; Lei Zhu; Li-jun Su (Journal of Mountain Science, 2022)

Genome-Wide Identification, Expression, and Interaction Analysis of BEL-Like Homeodomain Gene Family in Peach - Hui-feng Li; Ya-ting Wu; Qiang Zhao; Qing-long Dong (Biochemical Genetics, 2022)

Anatexis of late Neoarchean-Early Paleoproterozoic and late Paleoproterozoic garnet-bearing leucogranite from the Khondalite Belt in the North China Craton - Qiang Shi; Zhong-Yuan Xu; Guo-Chun Zhao; Ding Ding; Guang-Wei Liu; Zhong-Hai Zhao; Jing-Yu Yu; Chen Li; Li-Qiang Bai; Yao Wang; Bing Guo; Kai Zhang; et al. (International Geology Review, 2022)

Anchor Chain Optimization Design of a Catenary Anchor Leg Mooring System Based on Adaptive Sampling - Qiang Sun; Wenbo Li; Rundong Li; Dongsheng Peng; Qiang Guo; Yan Zhao; Qianjin Yue; Wanxie Zhong (Journal of Marine Science and Engineering, 2022)
A catenary anchor leg mooring system (CALM) is one of the main kinds of offshore transport terminals. Its buoyancy is connected by multiple anchor chains fixed on the seabed. Because a large deformation characterizes the anchor chain, it is prone to fatigue failure under dynamic loads in marine environments. These factors lead to many challenges in the design optimization of anchor chains. This study aims to develop a rapid optimization design framework for a mooring anchor chain with cost minimization as the design objective. In this framework, an approximation model of the mooring analysis is built based on an adaptive sampling method, and a combination of a genetic algorithm and a sequential quadratic programming method is utilized to optimize the established approximation model. The results show that the framework significantly reduces the computation time, and the error of the final optimization result obtained by adaptive sampling is significantly reduced. We found that using a quadratic or elliptic function as an adaptive function is good enough to obtain the optimization result.

Extreme drought does not alter the stability of aboveground net primary productivity but decreases the stability of belowground net primary productivity in a desert steppe of northern China - Xiangyun Li; Xiaoan Zuo; Xueyong Zhao; Shaokun Wang; Ping Yue; Chong Xu; Qiang Yu; Eduardo Medina-Roldán (Environmental Science and Pollution Research, 2022)

Application of quorum sensing system in microbial synthesis of valuable chemicals: a mini-review - Pengfei Gu; Qianqian Ma; Shuo Zhao; Juan Gao; Changtao Li; Hao Zhou; Shuixing Jiang; Qiang Li (World Journal of Microbiology and Biotechnology, 2022)

Influence of organoboron cross-linker and reservoir characteristics on filtration and reservoir residual of guar gum fracturing fluid in low-permeability shale gas reservoirs - Qiang Li; Fuling Wang; Yanling Wang; Jinyan Zhang; Xiaoqiu Yu; Mi Zhao; Chang Zhou; Kobina Forson; Shuang Shi; Yu Zhao; Wusheng Li (Environmental Science and Pollution Research, 2022)

Saturated permeability of compacted loess based on low-field nuclear magnetic resonance (NMR) - Jialiang Liu; Qiang Xu; Pinliang Li; Pan He; Chuanhao Pu; Kuanyao Zhao; Dalei Peng; Zhuo Wang (Bulletin of Engineering Geology and the Environment, 2022)

A histological study of vascular wall resident stem cells in venous malformations - Hou-Fu Xia; Wen-Qiang Lai; Gao-Hong Chen; Ye Li; Qi-Hui Xie; Yu-Lin Jia; Gang Chen; Yi-Fang Zhao (Cell and Tissue Research, 2022)

Assessment of macrobenthic community function and ecological quality after reclamation in the Changjiang (Yangtze) River Estuary wetland - Yinying Huang; Yingying Huang; Xinglin Du; Yiming Li; Jiangtao Tian; Qiang Chen; Youhui Huang; Weiwei Lv; Ying Yang; Zhiquan Liu; Yunlong Zhao (Acta Oceanologica Sinica, 2022)

Preservation of soil organic carbon in coastal wetlands promoted by glomalin–iron–organic carbon ternary system - Bo Zhao; Yunlong Jia; Shengjie Wu; Lili Wei; Jian Li; Hualong Hong; Chongling Yan; Mark A. Williams; Qiang Wang (Limnology and Oceanography, 2022)
Iron‐bound soil organic carbon (Fe‐bound SOC) and microbial residues are vital for SOC preservation, a process crucial for drawdown of anthropogenic carbon. However, the relative importance of Fe‐bound SOC in coastal wetlands, and its interaction with microbial residues remain poorly understood. Here, we used glomalin as a proxy for microbial residues, with the goal of determining microbial residues binding to Fe and Fe‐bound SOC across a 1000 km coastline of China including seven typical mangrove wetlands. As hypothesized, it was found that the glomalin fraction was strongly associated with and likely bound to Fe‐bound SOC complexes, which accounted for 21.4% ± 1.6% of mangrove SOC. Mean level of Fe‐bound glomalin was 1.2 ± 0.1 mg cm −3 , accounting for 40.6% ± 1.5% of total glomalin and 35.4% ± 3.2% of Fe‐bound SOC in the top 10 cm mangrove soil layer at regional scale. Due to the growing realization that Fe may be a crucial factor of glomalin cycling, we performed multiple chemical characterization techniques to identify the association between Fe and glomalin. Our results suggested that association to Fe was a main stabilization mechanism of glomalin in soils, and glomalin served as organic ligands in the formation of Fe‐bound SOC. We also found that the bulk glomalin extracts were a glomalin–Fe–OC ternary complex, which constituted an important proportion of mangrove SOC. These findings highlight the important effect of glomalin bound to Fe as a major mechanism of SOC persistence in coastal wetlands.

Development and characterization of monoclonal antibodies specific for cyprinid herpesvirus 2 - Lupin Zhao; Wa Gao; Yihua zheng; Liqun Lu; Qiang Li; Yousheng Jiang (Journal of Fish Diseases, 2022)
Infections of Cyprinid herpesvirus 2 in goldfish and farmed crucian carp ( Carassius auratus gibelio ) are still an urgent problem worldwide. Detection and prevention are necessary for the control of haematopoietic necrosis disease caused by CyHV‐2. Although many sensitive molecular diagnostic methods have been developed, effective immunodiagnosis and neutralization approaches based on monoclonal antibodies (MAbs) against CyHV‐2 are still important to CyHV‐2 study. In this experiment, purified CyHV‐2 was used as antigens to produce monoclonal antibodies (Mabs). Six Mabs bound to different proteins were selected by Dot‐blot screening and Western‐blot analysis, and no one had cross‐reactivity with closely related koi herpesvirus. Among them, Mabs 2E1‐B10, 1F5‐A3 and 4C4‐A7 belonged to IgG 1 isotype, while other three Mabs 3G9‐B11, 3B4‐G5 and 4F4‐B7 belonged to IgM isotype. These six Mabs all could specifically detect CyHV‐2 in CyHV‐2 infected caudal fin of Carassius auratus gibelio (GiCF) cells by immunofluorescence assays. Then, the neutralization ability was tested in vitro, and the result showed that all six Mabs can attenuate CPE by CyHV‐2 in vitro among which 2E1‐B10 had the best neutralization ability. The virus proteins recognized by these six Mabs were identified by mass spectrometry identification, and the result showed they probably were ORF88, ORF55R, ORF115 and ORF151R. This study is the first to prepare Mabs by purifying CyHV‐2, which will provide a practical basis for the in‐depth study of CyHV‐2 virus.

Genesis of the Hermyingyi W–Sn deposit, Southern Myanmar, SE Asia: Constraints from fluid inclusion and multiple isotope (C, H, O, S, and Pb) studies - Hai Jiang; Shao-Yong Jiang; Wen-Qian Li; Kui-Dong Zhao; Wei Zhang; Qiang Zhang (Mineralium Deposita, 2022)

Starch, cellulose and plant extracts as green inhibitors of metal corrosion: a review - Li Huang; Wei-Qiang Chen; Shan-Shan Wang; Qing Zhao; Hui-Jing Li; Yan-Chao Wu (Environmental Chemistry Letters, 2022)

Circ-ATIC Serves as a Sponge of miR-326 to Accelerate Esophageal Squamous Cell Carcinoma Progression by Targeting ID1 - Bing Zhang; Weiwei Chu; Zhe Li; Yaxiao Zhang; Qiang Zhen; Baolei Lv; Jiabao Liu; Caiping Lu; Xiaojian Zhao (Biochemical Genetics, 2022)

Automatic identification of harmful algae based on multiple convolutional neural networks and transfer learning - Mengyu Yang; Wensi Wang; Qiang Gao; Chen Zhao; Caole Li; Xiangfei Yang; Jiaxi Li; Xiaoguang Li; Jianglong Cui; Liting Zhang; Yanping Ji; Shuqin Geng (Environmental Science and Pollution Research, 2022)

Development of 45 SNP markers in Triplophysa hsutschouensis based on RAD sequencing - Ya Liu; Jiansheng Lai; Zhongmeng Zhao; Hongyu Ke; Han Zhao; Yeyu Chen; Xiaoyun Wu; Qiang Li (Conservation Genetics Resources, 2022)

Feasibility analyses of virtual models and 3D printing for surgical simulation of the double-outlet right ventricle - Jixiang Liang; Bingheng Lu; Xin Zhao; Jiong Wang; Dianjiang Zhao; Gen Zhang; Bin Zhu; Qiang Ma; Guangyu Pan; Dianyuan Li (Medical & Biological Engineering & Computing, 2022)

Ser68 phosphoregulation is essential for CENP-A deposition, centromere function and viability in mice - Yuting Liu; Kehui Wang; Li Huang; Jicheng Zhao; Xinpeng Chen; Qiang Wu; Zhouliang Yu; Guohong Li (Science China Life Sciences, 2022)

mTOR-FABP4 signal is activated in brain arteriovenous malformations in humans - Debin Yan; Qiang Hao; Yu Chen; Zhipeng Li; Haibin Zhang; Kexin Yuan; Runting Li; Ruinan Li; Yahui Zhao; Ke Wang; Hao Peng; Dong Zhang; et al. (Journal of Molecular Medicine, 2022)

Effects of nylon mesh vitrification on the cytoskeleton, mitochondria, and aquaporins of mouse 2-cell embryos - Zhen Gao; Wei Li; Hui Zhang; Zhenshan Yang; Xiaoe Zhao; Qiang Wei; Baohua Ma (In Vitro Cellular & Developmental Biology - Animal, 2022)

Timing and tectonic setting of tin mineralization in southern Myanmar: constraints from cassiterite and wolframite U–Pb ages - Qiang Zhang; Kui-Dong Zhao; Wen-Qian Li; Martin R. Palmer; Shao-Yong Jiang; Hai Jiang; Wei Zhang; Di Zhang; Amjad Hussain (Mineralium Deposita, 2022)

Integrated analysis of the miRNA and mRNA expression profiles in Leiocassis longirostris at gonadal maturation - Han Zhao; Lu Zhang; Qiang Li; Zhongmeng Zhao; Yuanliang Duan; Zhipeng Huang; Hongyu Ke; Chao Liu; Huadong Li; Lu Liu; Jun Du; Zhen Wei; et al. (Functional & Integrative Genomics, 2022)

Effect of high temperatures on the magnetic susceptibility of loess - Yuyang Zhao; Qiang Sun; Weizhen Li; Shaofei Wang; Yue Meng; Xiaofei Wang (Environmental Science and Pollution Research, 2022)

Cohnella mopanensis sp. nov., a new Gram-negative bacterium isolated from soil in Xinping Mountain National Forest Park - Jing Tang; Jiang-Yuan Zhao; Le-Le Li; Zhang-Gui Ding; Shi-Qiang Ye; Cheng Ling; Meng-Yu Zhang; Song-Guo Liang; Jian-Yu Li; Pei-Wen Yang; Jiao Xiong; Lu-Yao Feng; et al. (Archives of Microbiology, 2022)

Diminished miR-374c-5p negatively regulates IL (interleukin)-6 in unexplained recurrent spontaneous abortion - Lin Zhao; Li Han; Guozhen Hei; Ran Wei; Zhen Zhang; Xiaoxiao Zhu; Qiang Guo; Chu Chu; Xiaoxiao Fu; Ke Xu; Xia Li (Journal of Molecular Medicine, 2022)

Experimental investigation on the high-pressure sand suspension and adsorption capacity of guar gum fracturing fluid in low-permeability shale reservoirs: factor analysis and mechanism disclosure - Qiang Li; Fuling Wang; Yanling Wang; Kobina Forson; Lili Cao; Chenglin Zhang; Chang Zhou; Bo Zhao; Jiashuo Chen (Environmental Science and Pollution Research, 2022)

Nitric oxide enhances resistance of Pleurotus eryngii to cadmium stress by alleviating oxidative damage and regulating of short-chain dehydrogenase/reductase family - Changsong Zhao; Zhijie Bao; Huiyu Feng; Lanchai Chen; Qiang Li (Environmental Science and Pollution Research, 2022)

Short-term effect of sulfur dioxide (SO2) change on the risk of tuberculosis outpatient visits in 16 cities of Anhui Province, China: the first multi-city study to explore differences in occupational patients - Xin-Qiang Wang; Jia-Wen Zhao; Kang-Di Zhang; Wen-Jie Yu; Jie Wang; Ying-Qing Li; Xin Cheng; Zhen-Hua Li; Yi-Cheng Mao; Cheng-Yang Hu; Kai Huang; Kun Ding; et al. (Environmental Science and Pollution Research, 2022)

Temporal Variation of Summer Hypoxia off Changjiang Estuary During 1997–2014 and Its Association With ENSO - Xiao Ma; Anqi Liu; Qiang Zhao; Bin Wang; Di Tian; Qicheng Meng; Dingyong Zeng; Jia Li; Daji Huang; Feng Zhou (Frontiers in Marine Science, 2022)
Temporal variation of summer hypoxia, along a repeated hydrographic section from the Changjiang River mouth to Cheju Island, is investigated using cruise data during 1997–2014. The climatological mean of dissolved oxygen (DO) presents a “dual-core structure” below the oxycline, associated with two hypoxic centers near the river mouth and offshore of the Changjiang Bank, respectively. The DO value is highly variable from year to year, with dramatic interannual variation but an insignificant linear trend during 1997–2014. Composite analysis indicates that the interannual variation of DO and associated hypoxia events are strongly affected by the El Niño–Southern Oscillation (ENSO) cycle. In the El Niño decaying summer, large river discharge and relatively strong stratification, combined with calm climatic and hydrographic conditions, enhance DO depletion off the Changjiang Estuary. It is likely that El Niño is not a prerequisite for hypoxia occurrences. However, El Niño did enhance bottom hypoxia probability off the Changjiang Estuary during 1997–2014.

Numerical Simulation of Inrush Water Spreading Through a Mine: A Case Study of the Beixinyao Mine, Shanxi Province, China - Qiang Wu; Xiaoyan Zhang; Yingwang Zhao; Peitao Li; Yi Yao; Zhili Du; Hua Xu; Xiao Wang (Mine Water and the Environment, 2022)

Isolation and characterization of 45 SNP markers in Triplophysa tenuis - Ya Liu; Yeyu Chen; Jiansheng Lai; Hongyu Ke; Zhongmeng Zhao; Han Zhao; Xiaoyun Wu; Jian Zhou; Qiang Li (Conservation Genetics Resources, 2022)

Re-evaluation of the identities of Glossadelphus borneensis and its associated synonyms, G. attenuatus and G. nitidus - Zhao-Qin Yi; Si He; Jun-Jie Wang; Li-Qiang Mu; Yu Jia (Brittonia, 2022)

The effect and attributable risk of daily temperature on category C infectious diarrhea in Guangdong Province, China - Qiang Hao; Qi Gao; Ran Zhao; Haitao Wang; Hao Li; Baofa Jiang (Environmental Science and Pollution Research, 2022)

Correction to: Role of HMGB1 in TNF-α Combined with Z-VAD-fmk-Induced L929 Cells Necroptosis - Zhao Lei; Can Yu; Xia Li; Li-Hua Huang; Zhi-Qiang Li; Hong-Wei Zhu; Duo Han; Hui Huang; Xiao Yu (Biochemical Genetics, 2022)

Role of HMGB1 in TNF-α Combined with Z-VAD-fmk-Induced L929 Cells Necroptosis - Can Yu; Zhao Lei; Xia Li; Li-Hua Huang; Zhi-Qiang Li; Hong-Wei Zhu; Duo Han; Hui Huang; Xiao Yu (Biochemical Genetics, 2022)

Two new sesquiterpenes from the rhizomes of Atractylodes macrocephala and their biological activities - Yi-Nan Zhao; Gai Gao; Jin-Lian Ma; Rui-Zhu Xu; Tao Guo; Li-Min Wu; Xin-Guang Liu; Zhi-Shen Xie; Jiang-Yan Xu; Zhen-Qiang Zhang; Pan Wang (Natural Product Research, 2022)

Biosynthesis of vanillin by different microorganisms: a review - Qianqian Ma; Liwen Liu; Shuo Zhao; Zhaosong Huang; Changtao Li; Shuixing Jiang; Qiang Li; Pengfei Gu (World Journal of Microbiology and Biotechnology, 2022)

Redescription of the Sanqiaspidae (Galeaspida) from the Lower Devonian of South China and its biostratigraphic significance - Zhi-Kun Gai; Wen-Yu Jiang; Wen-Jin Zhao; Qiang Li; Xiao-Dong Shi; Min Zhu (Palaeobiodiversity and Palaeoenvironments, 2022)

More frequent glacier-rock avalanches in Sedongpu gully are blocking the Yarlung Zangbo River in eastern Tibet - Weile Li; Bo Zhao; Qiang Xu; Gianvito Scaringi; Huiyan Lu; Runqiu Huang (Landslides, 2022)

Atorvastatin-Induced Absorption of Chronic Subdural Hematoma Is Partially Attributed to the Polarization of Macrophages - Liang Yang; Nan Li; Lijun Yang; Dong Wang; Shuke Qiang; Zongmao Zhao (Journal of Molecular Neuroscience, 2022)

A peptide encoding gene MdCLE8 regulates lateral root development in apple - Tian-en Zhang; Yan Shi; Xiu-ming Li; Qiang Zhao; Chun-xiang You (Plant Cell, Tissue and Organ Culture (PCTOC), 2022)

Formation mechanism and evolution process of the Chada rock avalanche in Southeast Tibet, China - Qiyi Lai; Jianjun Zhao; Runqiu Huang; Dujiang Wang; Nengpan Ju; Qingmiao Li; Yunsheng Wang; Qiang Xu; Weihua Zhao (Landslides, 2022)

Dissolving microneedle rollers for rapid transdermal drug delivery - Xiao Peng Zhang; Bao Li Zhang; Bo Zhi Chen; Ze Qiang Zhao; Wen Min Fei; Yong Cui; Xin Dong Guo (Drug Delivery and Translational Research, 2022)

Pore-Scale Investigation of the Electrical Property and Saturation Exponent of Archie’s Law in Hydrate-Bearing Sediments - Jinhuan Zhao; Changling Liu; Chengfeng Li; Yongchao Zhang; Qingtao Bu; Nengyou Wu; Yang Liu; Qiang Chen (Journal of Marine Science and Engineering, 2022)
Characterizing the electrical property of hydrate-bearing sediments is essential for hydrate reservoir identification and saturation evaluation. As the major contributor to electrical conductivity, pore water is a key factor in characterizing the electrical properties of hydrate-bearing sediments. The objective of this study is to clarify the effect of hydrates on pore water and the relationship between pore water characteristics and the saturation exponent of Archie’s law in hydrate-bearing sediments. A combination of X-ray computed tomography and resistivity measurement technology is used to derive the three-dimensional spatial structure and resistivity of hydrate-bearing sediments simultaneously, which is helpful to characterize pore water and investigate the saturation exponent of Archie’s law at the micro-scale. The results show that the resistivity of hydrate-bearing sediments is controlled by changes in pore water distribution and connectivity caused by hydrate formation. With the increase of hydrate saturation, pore water connectivity decreases, but the average coordination number and tortuosity increase due to much smaller and more tortuous throats of pore water divided by hydrate particles. It is also found that the saturation exponent of Archie’s law is controlled by the distribution and connectivity of pore water. As the parameters of connected pore water (e.g., porosity, water saturation) decrease, the saturation exponent decreases. At a low hydrate-saturation stage, the saturation exponent of Archie’s law changes obviously due to the complicated pore structure of hydrate-bearing sediments. A new logarithmic relationship between the saturation exponent of Archie’s law and the tortuosity of pore water is proposed which helps to calculate field hydrate saturation using resistivity logging data.

Paracoccus shandongensis sp. nov., Isolated from Activated Sludge - Xiao-Fan Gong; Fang Wang; Dong Meng; Yu-Ling Liu; Peng-Fei Gu; Xiang-Yu Fan; Zhao-Song Huang; Zong-Jun Du; Qiang Li (Current Microbiology, 2022)

Mesorhizobium xinjiangense sp. nov., isolated from rhizosphere soil of Alhagi sparsifolia - Dong Meng; Yu-Ling Liu; Jun-Jie Zhang; Peng-Fei Gu; Xiang-Yu Fan; Zhao-Song Huang; Yan Ji; Heng Meng; Zong-Jun Du; Wei-Min Li; Qiang Li (Archives of Microbiology, 2022)

Comparison of the Anthropogenic Emission Inventory for CMIP6 Models with a Country-Level Inventory over China and the Simulations of the Aerosol Properties - Tianyi Fan; Xiaohong Liu; Chenglai Wu; Qiang Zhang; Chuanfeng Zhao; Xin Yang; Yanglian Li (Advances in Atmospheric Sciences, 2022)

RETRACTED ARTICLE: MiR-519d-3p enhances the sensitivity of non-small-cell lung cancer to tyrosine kinase inhibitors - Qiang Zhen; Yaxiao Zhang; Lina Gao; Renfeng Wang; Weiwei Chu; Xiaojian Zhao; Zhe Li; Huixian Li; Bing Zhang; Baolei Lv; Jiabao Liu (Mammalian Genome, 2021)

Correction to: Enhanced adsorption of phosphorus in soil by lanthanum-modified biochar: improving phosphorus retention and storage capacity - Di Zhao; Yuan Luo; Yi-yang Feng; Qiu-ping He; Li-sheng Zhang; Ke-qiang Zhang; Feng Wang (Environmental Science and Pollution Research, 2021)

Enhanced adsorption of phosphorus in soil by lanthanum-modified biochar: improving phosphorus retention and storage capacity - Di Zhao; Yuan Luo; Yi-yang Feng; Qiu-ping He; Li-sheng Zhang; Ke-qiang Zhang; Feng Wang (Environmental Science and Pollution Research, 2021)

Pollution characteristics, spatial distribution, and source identification of heavy metals in road dust in a central eastern city in China: a comprehensive survey - Guoyong Zhao; Ronglei Zhang; Yan Han; Jianing Meng; Qiang Qiao; Hetan Li (Environmental Monitoring and Assessment, 2021)

Strategies of cadmium and copper uptake and translocation in different plant species growing near an E-waste dismantling site at Wenling, China - Jiao Jiao Li; Xue Qiang Zhao; Jia Lin Wang; Ren Fang Shen (Environmental Science and Pollution Research, 2021)

The characterization and candidate gene isolation for a novel male-sterile mutant ms40 in maize - Xiaowei Liu; Yujing Yue; Zicheng Gu; Qiang Huang; Zijin Pan; Zhuofan Zhao; Mingmin Zheng; Zhiming Zhang; Chuan Li; Hongyang Yi; Tao Yu; Moju Cao (Plant Cell Reports, 2021)

Community structure and abundance of comammox Nitrospira in Chongming eastern intertidal sediments - Dongyao Sun; Min Liu; Lijun Hou; Mengyue Zhao; Xiufeng Tang; Qiang Zhao; Jun Li; Ping Han (Journal of Soils and Sediments, 2021)

Sorption and transport of Mn2+ in soil amended with alkali-modified pomelo biochar - Qiang An; Sheng Zhu; Zheng Li; Shuman Deng; Bin Zhao; Fanyu Meng; Ningjie Jin; Xiaozhou Ren (Environmental Science and Pollution Research, 2021)

Experimental study on the influence of water on the failure properties of sandstone - Hongjian Wang; Jin Li; Qiang Guo; Ruiguo Shi; Zijiang Zhao; Yitong Zhang; Fei Zhao (Bulletin of Engineering Geology and the Environment, 2021)

Elevation change of the Urumqi Glacier No.1 derived from Sentinel-1A data - Jia-liang Liu; Jun Zhao; Zhong-qin Li; Yan-qiang Wang; Si-min Shen (Journal of Mountain Science, 2021)

Geohazard Recognition and Inventory Mapping Using Airborne LiDAR Data in Complex Mountainous Areas - Chen Guo; Qiang Xu; Xiujun Dong; Weile Li; Kuanyao Zhao; Huiyan Lu; Yuanzhen Ju (Journal of Earth Science, 2021)

High-resolution genome-wide association study and genomic prediction for disease resistance and cold tolerance in wheat - Yunlong Pang; Yuye Wu; Chunxia Liu; Wenhui Li; Paul St. Amand; Amy Bernardo; Danfeng Wang; Lei Dong; Xiufang Yuan; Huirui Zhang; Meng Zhao; Linzhi Li; et al. (Theoretical and Applied Genetics, 2021)

Effect of Immersion Duration on Shear Behavior of Granite Fractures - Zihao Dou; Tianyang Gao; Zhihong Zhao; Jinjin Li; Qiang Yang; Shuang Yi (Rock Mechanics and Rock Engineering, 2021)

Interaction between the cell walls of microalgal host and fungal carbohydrate‐activate enzymes is essential for the pathogenic parasitism process - Juan Lin; Hailong Yan; Liang Zhao; Yanhua Li; Bahareh Nahidian; Mianmian Zhu; Qiang Hu; Danxiang Han (Environmental Microbiology, 2021)
Summary Fungi can parasitize microalgae, exerting profound impacts on both the aquatic ecosystems and microalgal mass cultures. In this study, the unicellular green alga Haematococcus pluvialis and the blastocladialean fungus Paraphysoderma sedebokerense were used as a model system to address the mechanisms underlying the fungal parasitism on the algal host. High‐throughput metabolic assay indicated that P . sedebokerense can utilize several carbon sources with a preference for mannose, glucose and their oligosaccharides, which was compatible with the profile of the host algal cell walls enriched with glucan and mannan. The results of dual transcriptomics analysis suggested that P . sedebokerense can upregulate a large number of putative carbohydrate‐activate enzymes (CAZymes) encoding genes, including those coding for the endo‐1,4‐β‐glucanase and endo‐1,4‐β‐mannanase during the infection process. The cell walls of H . pluvialis can be decomposed by both P . sedebokerense and commercial CAZymes (e.g. cellulase and endo‐1,4‐β‐mannanase) to produce mannooligomers, while several putative parasitism‐related genes of P . sedebokerense can be in turn upregulated by mannooligomers. In addition, the parasitism can be blocked by interfering the selected CAZymes including glucanase, mannanase and lysozyme with the specific inhibitors, which provided a framework for screening suitable compounds for pathogen mitigation in algal mass culture.

Safety evaluation and ibuprofen removal via an Alternanthera philoxeroides-based biochar - Yuan-da Du; Xin-qian Zhang; Li Shu; Yu Feng; Cui Lv; Hong-qiang Liu; Fei Xu; Qian Wang; Cong-cong Zhao; Qiang Kong (Environmental Science and Pollution Research, 2021)

Abundance and mobility of metal(loid)s in reservoir sediments of Singe Tsangpo and Yarlung Tsangpo in Tibet, China: Implications for ecological risk - Zhenjie Zhao; Shehong Li; Lili Xue; Jie Liao; Jingjing Zhao; Mei Wu; Mingguo Wang; Qiang Yang; Jing Sun; Yan Zheng (Environmental Geochemistry and Health, 2021)

Paracoccus binzhouensis sp. nov., isolated from activated sludge - Fang Wang; Xiao-Fan Gong; Dong Meng; Yu-Ling Liu; Peng-Fei Gu; Xiang-Yu Fan; Zhao-Song Huang; Zong-Jun Du; Qiang Li (Archives of Microbiology, 2021)

Profiling of Serum Exosome MiRNA Reveals the Potential of a MiRNA Panel as Diagnostic Biomarker for Alzheimer’s Disease - Zhiwu Dong; Hongjun Gu; Qiang Guo; Shuang Liang; Jian Xue; Feng Yao; Xianglu Liu; Feifei Li; Huiling Liu; Li Sun; Kewen Zhao (Molecular Neurobiology, 2021)

Estimation of mountain block recharge on the northern Tianshan Mountains using numerical modeling - Jian-hua Ping; Ya-qiang Zhu; Xue-mei Mei; Wei Leng; Sheng Li; Ji-chang Zhao (Journal of Mountain Science, 2021)

Ambient fine particulate matter of diameter ≤ 2.5 μm and risk of hemorrhagic stroke: a systemic review and meta-analysis of cohort studies - Kai Zhao; Jing Li; Chaonan Du; Qiang Zhang; Yu Guo; Mingfei Yang (Environmental Science and Pollution Research, 2021)
Ambient fine particulate matter of 2.5 μm or less in diameter (PM 2.5 ) of environment contamination is deemed as a risk factor of cerebrovascular diseases. Yet there is still no explicit evidence strongly supporting that PM 2.5 with per unit increment can increase the risk of hemorrhagic stroke (HS). Literatures were searched from PubMed, Cochrane, and Embase. After the systemic review of relevant studies, random effects model was used to perform meta-analysis and to evaluate the association between PM 2.5 and risk of HS. Seven cohort studies were finally included, involving more than 6 million people and 37,667 endpoint events (incidence or mortality of HS). Total scores of quality assessment were 50. Pooled hazard ratio (HR) for crude HRs was 1.13 (95%CI: 1.09–1.17) (CI for confidence interval). Pooled HR of subgroup analysis for current smoking with exposure to growing PM 2.5 was 1.14 (95%CI: 0.92–2.15) and for never and former smoking was 1.04 (95%CI: 0.74–1.46). Ambient PM 2.5 level is significantly associated with the risk of HS, which might be a potential risk factor of HS. Smoking does not further increase the risk of HS under exposure of PM 2.5 .

TLR8 in the Trigeminal Ganglion Contributes to the Maintenance of Trigeminal Neuropathic Pain in Mice - Lin-Xia Zhao; Ming Jiang; Xue-Qiang Bai; De-Li Cao; Xiao-Bo Wu; Jing Zhang; Jian-Shuang Guo; Tong-Tong Chen; Juan Wang; Hao Wu; Yong-Jing Gao; Zhi-Jun Zhang (Neuroscience Bulletin, 2021)
Trigeminal neuropathic pain (TNP) is a significant health problem but the involved mechanism has not been completely elucidated. Toll-like receptors (TLRs) have recently been demonstrated to be expressed in the dorsal root ganglion and involved in chronic pain. Here, we show that TLR8 was persistently increased in the trigeminal ganglion (TG) neurons in model of TNP induced by partial infraorbital nerve ligation (pIONL). In addition, deletion or knockdown of Tlr8 in the TG attenuated pIONL-induced mechanical allodynia, reduced the activation of ERK and p38-MAPK, and decreased the expression of pro-inflammatory cytokines in the TG. Furthermore, intra-TG injection of the TLR8 agonist VTX-2337 induced pain hypersensitivity. VTX-2337 also increased the intracellular Ca 2+ concentration, induced the activation of ERK and p38, and increased the expression of pro-inflammatory cytokines in the TG. These data indicate that TLR8 contributes to the maintenance of TNP through increasing MAPK-mediated neuroinflammation. Targeting TLR8 signaling may be effective for the treatment of TNP.

EEG-Based Anxious States Classification Using Affective BCI-Based Closed Neurofeedback System - Chao Chen; Xuecong Yu; Abdelkader Nasreddine Belkacem; Lin Lu; Penghai Li; Zufeng Zhang; Xiaotian Wang; Wenjun Tan; Qiang Gao; Duk Shin; Changming Wang; Sha Sha; et al. (Journal of Medical and Biological Engineering, 2021)

The prevalence and risks of major comorbidities among inpatients with pulmonary tuberculosis in China from a gender and age perspective: a large-scale multicenter observational study - Wanli Kang; Jian Du; Song Yang; Jiajia Yu; Hongyan Chen; Jianxiong Liu; Jinshan Ma; Mingwu Li; Jingmin Qin; Wei Shu; Peilan Zong; Yi Zhang; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Chelativorans alearense sp. nov., A Novel Bacterial Species Isolated From Soil in Alear, China - Dong Meng; Yu-Ling Liu; Peng-Fei Gu; Xiang-Yu Fan; Zhao-Song Huang; Yan Ji; Wei-Min Li; Zong-Jun Du; Qiang Li (Current Microbiology, 2021)

Genome-Wide Identification of Copper Stress-Regulated and Novel MicroRNAs in Mulberry Leaf - Qiuxia Du; Peng Guo; Yisu Shi; Jian Zhang; Danyan Zheng; Yang Li; Adolf Acheampong; Ping Wu; Qiang Lin; Weiguo Zhao (Biochemical Genetics, 2021)

Quantitative spatial distribution model of site-specific loess landslides on the Heifangtai terrace, China - Qi Zhou; Qiang Xu; Dalei Peng; Xuanmei Fan; Chaojun Ouyang; Kuanyao Zhao; Huajin Li; Xing Zhu (Landslides, 2021)

Effects of iron and humic acid on competition between Microcystis aeruginosa and Scenedesmus obliquus revealed by HPLC analysis of pigments - Miaomiao Zhao; Qiang He; Chongtai Chen; Yaqi Tian; Jing Wei; Pengfei Duan; Haiming Wu; Ming Li (Journal of Oceanology and Limnology, 2021)

Efficient Editing of an Adenoviral Vector Genome with CRISPR/Cas9 - Qiang Li; Hui Wang; Chen-yu Gong; Zhao Chen; Jia-xing Yang; Hong-wei Shao; Wen-feng Zhang (Indian Journal of Microbiology, 2021)

Description of the reservoir along strike-slip fault zones in China T-Sh oilfield, Tarim Basin - Rui Zhao; Shang Deng; Lu Yun; Huixi Lin; Teng Zhao; Chen Yu; Qiangfu Kong; Qiang Wang; Huili Li (Carbonates and Evaporites, 2021)

Transcriptome profiling reveals candidate genes associated with cold stress in mulberry - Acheampong Adolf; Li Liu; Michael Ackah; Yang Li; Qiuxia Du; Danyan Zheng; Peng Guo; Yisu Shi; Qiang Lin; Changyu Qiu; Weiguo Zhao (Brazilian Journal of Botany, 2021)

Chelativorans xinjiangense sp. nov., a novel bacterial species isolated from soil in Xinjiang, China - Dong Meng; Yu-Ling Liu; Peng-Fei Gu; Xiang-Yu Fan; Zhao-Song Huang; Yan Ji; Wei-Min Li; Zong-Jun Du; Qiang Li (Archives of Microbiology, 2021)

Variance Component Decomposition for Growth Traits of the Bay Scallop (Argopecten irradians irradians) - Hengde Li; Yangfan Wang; Qiang Xing; Qifan Zeng; Liang Zhao; Yaqun Zhang; Xiaoli Hu; Zhenmin Bao (Frontiers in Marine Science, 2021)
The bay scallop ( Argopecten irradians irradians ) is one of the most important shellfish species in China. Since their introduction into China, only mass selection has been used in bay scallop breeding. With its gradual expansion and shortage of mate selection, population homozygosity increased, and fitness decreased. To investigate the effects of inbreeding and provide reference for improving breeding strategies and mating management, the variance components of the growth traits of the bay scallop were decomposed with genomic relationship matrices. The results indicated that the genetic variations in shell height and length were mainly accounted for by the additive effects. The genetic variation in shell width was mainly caused by dominance or dominance-by-dominance epistasis. The genetic variation in body weight was accounted for by dominance. No significant directional dominances were detected for all growth traits. Cross-validation for genomic prediction showed that including insignificant inbreeding in the genomic prediction model is not necessary, and we suggest that the genomic prediction model should be optimized with both likelihood ratio tests and cross-validation before utilization in practice.

Long-term remote sensing of total suspended matter using Landsat series sensors in Hulun Lake, China - Qiang Wang; Kaishan Song; Zhidan Wen; Yingxin Shang; Sijia Li; Chong Fang; Jia Du; Fangrui Zhao; Ge Liu (International Journal of Remote Sensing, 2021)

Injectable collagen scaffold promotes swine myocardial infarction recovery by long-term local retention of transplanted human umbilical cord mesenchymal stem cells - Qiang Wang; Xiaojun He; Bin Wang; Jun Pan; Chunying Shi; Jie Li; Liudi Wang; Yannan Zhao; Jianwu Dai; Dongjin Wang (Science China Life Sciences, 2021)

Distribution, failure risk and reinforcement necessity of check-dams on the Loess Plateau: a review - Wen-zhao Guo; Wen-Long Wang; Qiang Xu; Jian-jun Hu; Li-li Zhu (Journal of Mountain Science, 2021)

Retraction Note to: NPC-16, a novel naphthalimide–polyamine conjugate, induced apoptosis and autophagy in human hepatoma HepG2 cells and Bel-7402 cells - Song-qiang Xie; Qian Li; Ya-hong Zhang; Jian-hong Wang; Zi-hou Mei; Jin Zhao; Chao-jie Wang (Apoptosis, 2021)

Identification of the interactions and feedbacks among watershed water-energy balance dynamics, hydro-meteorological factors, and underlying surface characteristics - Xiaoting Wei; Shengzhi Huang; Qiang Huang; Guoyong Leng; Hao Wang; Li He; Jing Zhao; Dong Liu (Stochastic Environmental Research and Risk Assessment, 2021)

Modes of genetic adaptations underlying functional innovations in the rumen - Xiangyu Pan; Yudong Cai; Zongjun Li; Xianqing Chen; Rasmus Heller; Nini Wang; Yu Wang; Chen Zhao; Yong Wang; Han Xu; Songhai Li; Ming Li; et al. (Science China Life Sciences, 2021)

MiRNA-seq analysis of spleen and head kidney tissue from aquacultured largemouth bass (Micropterus salmoides) in response to Aeromonas hydrophila infection - Jian Zhou; Han Zhao; Lu Zhang; Qiang Li; Zhipeng Huang; Zhongmeng Zhao; Hongyu Ke; Yu Xiao; Xutao Su; Qiao Liu; Song Yang; Liulan Zhao (Functional & Integrative Genomics, 2021)

Isolation and complete genome sequencing of the virulent phage vB_EcoS_XY3 infecting multidrug-resistant Escherichia coli - Pan Fu; Qiang Zhao; Li Shi; Qin Xiong; Hongxia Xu; Senmao Cai; Qianqian Xu; Xiaodong Sun; Ming Sang (Archives of Virology, 2021)

Localization and characterization of Citrus centromeres by combining half-tetrad analysis and CenH3-associated sequence profiling - Qiang-Ming Xia; Lu-Ke Miao; Kai-Dong Xie; Zhao-Ping Yin; Xiao-Meng Wu; Chun-Li Chen; Jude W. Grosser; Wen-Wu Guo (Plant Cell Reports, 2020)

Toxicity Changes of Heavily Polluted River Sediments on Daphnia magna Before and After Dredging - Li-Ling Zhang; Zhou-Tao Pei; Ya-Ni Zhao; Jing Zhang; Rou-Rou Xu; Meng Zhang; Wen-Qiang Wang; Li-Wei Sun; Guang-Can Zhu (Bulletin of Environmental Contamination and Toxicology, 2020)

Prevalence, Molecular Characterization and Risk Factors of Blastocystis sp. from Farmed Pigs in Yunnan Province, Southwestern China - Jian Qiang Han; Zhao Li; Yang Zou; Li Hua Pu; Xin Quan Zhu; Feng Cai Zou; Cui-Qin Huang (Acta Parasitologica, 2020)

Analysis of genetic architecture and favorable allele usage of agronomic traits in a large collection of Chinese rice accessions - Xiuxiu Li; Zhuo Chen; Guomin Zhang; Hongwei Lu; Peng Qin; Ming Qi; Ying Yu; Bingke Jiao; Xianfeng Zhao; Qiang Gao; Hao Wang; Yunyu Wu; et al. (Science China Life Sciences, 2020)

LncRNA NFIA-AS2 promotes glioma progression through modulating the miR-655-3p/ZFX axis - Jun Xin; Yu-Hong Zhao; Xi-Yun Zhang; Li-Qiang Tian (Human Cell, 2020)

GalNAc-T3 and MUC1, a combined predictor of prognosis and recurrence in solitary pulmonary adenocarcinoma initially diagnosed as malignant solitary pulmonary nodule (≤ 3 cm) - Qiang Xie; Fengzhou Li; Shilei Zhao; Tao Guo; Zhuoshi Li; Lei Fang; Shiqing Wang; Wenzhi Liu; Chundong Gu (Human Cell, 2020)

Characterization of bimetallic Fe/Ni nanoparticles supported by amphiphilic block copolymer and its application in removal of 1,1,1-trichloroethane in water - Kai Huang; Hao Bian; Meng Zhang; Cong Zhan; Can Li; Wei Zhang; Changzheng Cui; Qiang Lu; Kuangfei Lin; Jianhua Zhao (Environmental Science and Pollution Research, 2020)

Comparative transcriptome analysis reveals a gene expression profile that contributes to rhizome swelling in Panax japonicus var. major - Jun Rong Tang; Ying Chun Lu; Zheng Jie Gao; Wan Ling Song; Kun Hua Wei; Yan Zhao; Qing Yan Tang; Xue Jiao Li; Jun Wen Chen; Guang Hui Zhang; Guang Qiang Long; Wei Fan; et al. (Plant Biosystems, 2020)

Shear Strength of Rock Fractures Under Dry, Surface Wet and Saturated Conditions - Bo Li; Xinna Ye; Zihao Dou; Zhihong Zhao; Yingchun Li; Qiang Yang (Rock Mechanics and Rock Engineering, 2020)

Deformation characteristics and failure mechanism of a reactivated landslide in Leidashi, Sichuan, China, on August 6, 2019: an emergency investigation report - Weile Li; Bo Zhao; Qiang Xu; Fan Yang; Hao Fu; Cong Dai; Xinxin Wu (Landslides, 2020)

Robust dictionary learning for erratic noise-corrupted seismic data reconstruction - Qiang Zhao; Qizhen Du; Qingqing Li; Liyun Fu (Acta Geophysica, 2020)

Coupling and Decoupling of High Biomass Phytoplankton Production and Hypoxia in a Highly Dynamic Coastal System: The Changjiang (Yangtze River) Estuary - Feng Zhou; Fei Chai; Daji Huang; Mark Wells; Xiao Ma; Qicheng Meng; Huijie Xue; Jiliang Xuan; Pengbin Wang; Xiaobo Ni; Qiang Zhao; Chenggang Liu; et al. (Frontiers in Marine Science, 2020)

Anti-phytopathogenic Bacterial Metabolites From the Seaweed-Derived Fungus Aspergillus sp. D40 - Rui-Huan Huang; Wei Lin; Peng Zhang; Jian-Yang Liu; Dan Wang; Yi-Qiang Li; Xiao-Qiang Wang; Cheng-Sheng Zhang; Wei Li; Dong-Lin Zhao (Frontiers in Marine Science, 2020)

Coumarin-pi, a new antioxidant coumarin derivative from Paxillus involutus - Jin-Xiu Zhang; Jian-Hua Lv; Li-Qiang Zhao; Xiao-Xi Shui; Jun Zhang; Li-An Wang (Natural Product Research, 2020)

Correction to: Transcriptomic Profiling Provides Insights into Inbreeding Depression in Yesso Scallop Patinopecten yessoensis - Liang Zhao; Yangping Li; Jiarun Lou; Zhihui Yang; Huan Liao; Qiang Fu; Zhenyi Guo; Shanshan Lian; Xiaoli Hu; Zhenmin Bao (Marine Biotechnology, 2020)

Next-generation sequencing technology as a powerful detection and semi-quantitative method for herpes simplex virus type 1 in pediatric encephalitis - Lin-lin Liu; Ling-yun Guo; Jie Dong; Wen-hua Huang; Li Zhao; Bing Liu; Xi-xi Zhang; Yong-qiang Jiang; Gang Liu (Journal of NeuroVirology, 2020)

Polymorphisms in arsenic (+ 3 oxidation state) methyltransferase (AS3MT) predict the occurrence of hyperleukocytosis and arsenic metabolism in APL patients treated with As2O3 - Wen-Sheng Liu; Xin-Yu Wang; Jing Lu; Ying-Mei Zhang; Xiang-Mei Ye; Jin-Mei Li; Qi-Lei Zhao; Zhi-Qiang Wu; Jin Zhou; Xin Hai (Archives of Toxicology, 2020)

Difference of planktonic ciliate communities of the tropical West Pacific, the Bering Sea and the Arctic Ocean - Chaofeng Wang; Haibo Li; Zhiqiang Xu; Shan Zheng; Qiang Hao; Yi Dong; Li Zhao; Wuchang Zhang; Yuan Zhao; Gérald Grégori; Tian Xiao (Acta Oceanologica Sinica, 2020)

Effects of Dietary Supplementation of Recombinant Plectasin on Growth Performance, Intestinal Health and Innate Immunity Response in Broilers - Jing Lin Ma; Li Hua Zhao; Dan Dan Sun; Jing Zhang; Yong Peng Guo; Zhi Qiang Zhang; Qiu Gang Ma; Cheng Ji; Li Hong Zhao (Probiotics and Antimicrobial Proteins, 2020)

Restricted nitrous oxide emissions by ammonia oxidizers in two agricultural soils following excessive urea fertilization - Zhaoming Chen; Qiang Wang; Jun Zhao; Yudong Chen; Huoyan Wang; Junwei Ma; Ping Zou; Li Bao (Journal of Soils and Sediments, 2020)

GABAergic Abnormalities Associated with Sensorimotor Cortico-striatal Community Structural Deficits in ErbB4 Knockout Mice and First-Episode Treatment-Naïve Patients with Schizophrenia - Chengcheng Zhang; Peiyan Ni; Yikang Liu; Yang Tian; Jinxue Wei; Bo Xiang; Liansheng Zhao; Xiaojing Li; Xiaohong Ma; Wei Deng; Wanjun Guo; Rongjun Ni; et al. (Neuroscience Bulletin, 2020)

Relative roles of formation and preservation on gold endowment along the Sanshandao gold belt in the Jiaodong gold province, China: importance for province- to district-scale gold exploration - Liang Zhang; David I. Groves; Li-Qiang Yang; Gong-Wen Wang; Xiang-Dong Liu; Da-Peng Li; Ying-Xin Song; Wei Shan; Si-Chen Sun; Zhao-Kun Wang (Mineralium Deposita, 2020)

One bis-indole alkaloid-voacamine from Voacanga africana Stapf: biological activity evaluation of PTP1B in vitro utilizing enzymology method based on SPRi expriment - Yan-Qiu Wang; Hong-Xiang Li; Xiao-Chun Liu; Jin-Shuang Zhao; Rong-Qiang Liu; Wen-ying Huai; Wei-Jun Ding; Tian-E Zhang; Yun Deng (Natural Product Research, 2019)

Interaction Between Variations in Dopamine D2 and Serotonin 2A Receptor is Associated with Short-Term Response to Antipsychotics in Schizophrenia - Liansheng Zhao; Huijuan Wang; Yamin Zhang; Jinxue Wei; Peiyan Ni; Hongyan Ren; Gang Li; Qiang Wang; Gavin P Reynolds; Weihua Yue; Wei Deng; Hao Yan; et al. (Neuroscience Bulletin, 2019)

Exosome-mediated transfer of CLIC1 contributes to the vincristine-resistance in gastric cancer - Kun Zhao; Zhen Wang; Xin Li; Jin-lu Liu; Lei Tian; Jun-qiang Chen (Molecular and Cellular Biochemistry, 2019)

Multi‐model analysis of climate impacts on plant photosynthesis in China during 2000–2015 - Hao Yan; Shao‐Qiang Wang; Jun‐Bang Wang; Yun Cao; Ling‐Ling Xu; Men‐Xin Wu; Lu Cheng; Liu‐Xi Mao; Feng‐Hua Zhao; Xian‐Zhou Zhang; Yun‐Fen Liu; Yan‐Fen Wang; et al. (International Journal of Climatology, 2019)
Differences, arising from differences in gross primary production (GPP) model structures and driving forces, have fuelled arguments concerning interannual changes of GPP in China since 2000. To better investigate the interannual variability of GPP and its covariance with climate factors in China, this study adopted a multi‐model analysis based on three GPP models (i.e., Terrestrial Ecosystem Carbon flux model [TEC], Breathing Earth System Simulator model [BESS], and MOD17 GPP model). The results show that annual GPP in China increased by 0.021–0.057 Pg C year −1 from 2000 to 2015 attributable to atmospheric‐CO 2 fertilization effects and favourable climate change, that is, increasing precipitation ( P r ) and temperature ( T a ). However, northern China and southern China had a large difference in the amplitude of these GPP changes; annual GPP increased by 0.017–0.039 Pg C year −1 in northern China but only 0.001–0.018 Pg C year −1 in southern China. Northern China and southern China occupy contrasting climate zones and this contrast produced different interannual variability of GPP through different mechanisms. Northern China has a dry climate with GPP changes sensitive to P r . As a result, more P r along with higher T a in northern China produced the strong uptrend of GPP from 2000 to 2015. In contrast, southern China has a wet climate with its GPP sensitive to solar radiation and T a . For the interval of 2000–2015, decreasing radiation plus drought exerted a negative influence on GPP in southern China. This study highlights the diverse mechanisms in which climate change affects GPP in dry and wet climate zones. A robust multi‐model analysis is preferred to reduce uncertainties arising from a single GPP model and its driving data.

Complete genome sequences of five prunus necrotic ringspot virus isolates from Inner Mongolia of China and comparison to other PNRSV isolates around the world - Shuang Song; Ping-ping Sun; Ya-han Chen; Qiang Ma; Xiao-yun Wang; Ming-min Zhao; Zheng-nan Li (Journal of Plant Pathology, 2019)

Transcriptomic Profiling Provides Insights into Inbreeding Depression in Yesso Scallop Patinopecten yessoensis - Liang Zhao; Yangping Li; Jiarun Lou; Zhihui Yang; Huan Liao; Qiang Fu; Zhenyi Guo; Shanshan Lian; Xiaoli Hu; Zhemin Bao (Marine Biotechnology, 2019)

Internal Tide Generation and Dissipation by Small Periodic Topography in Deep Ocean - Qiang Li; Xianzhong Mao; Guotong Deng; Ruixiang Zhao; Chuanzheng Zhang; Xiaohua Zhu (Journal of Ocean University of China, 2019)

The ABA receptor-like gene VyPYL9 from drought-resistance wild grapevine confers drought tolerance and ABA hypersensitivity in Arabidopsis - Jie Liu; Feng-Li Zhao; Ye Guo; Xiu-cai Fan; Yue-jin Wang; Ying-Qiang Wen (Plant Cell, Tissue and Organ Culture (PCTOC), 2019)

Integrated analysis of RNA-seq and microRNA-seq depicts miRNA–mRNA networks involved in stripe patterns of Botia superciliaris skin - Jian Zhou; Han Zhao; Lu Zhang; Can Liu; Siyuan Feng; Jideng Ma; Qiang Li; Hongyu Ke; Xinyu Wang; Lingyan Liu; Chao Liu; Xutao Su; et al. (Functional & Integrative Genomics, 2019)

The Mining-Induced Seepage Effect and Reconstruction of Key Aquiclude Strata During Backfill Mining - Jixiong Zhang; Qiang Sun; Meng Li; Xu Zhao (Mine Water and the Environment, 2019)

RNA-Seq-based transcriptomic profiling of primary interstitial cells of Cajal in response to bovine viral diarrhea virus infection - Shengnan Li; Xinyan Hu; Ruixin Tian; Yanting Guo; Junzhen Chen; Zhen Li; Xinyan Zhao; Ling Kuang; Duoliang Ran; Hongqiong Zhao; Xiaohong Zhang; Jinquan Wang; et al. (Veterinary Research Communications, 2019)

Genome-wide identification, expression, and interaction analysis for ovate family proteins in peach - Huifeng Li; Qinglong Dong; Xiaoping Zhu; Qiang Zhao; Kun Ran (Molecular Biology Reports, 2019)

Molecular detection and identification of phytoplasmas in a novel 16SrI subgroup in sunflowers and cocklebur weeds - Lei Zhang; Ping-ping Sun; Qiang Ma; Xiao-zhao Xu; Hong-you Zhou; Zheng-nan Li (Journal of Plant Pathology, 2019)

Proteomics analysis of HSV-1-induced alterations in mouse brain microvascular endothelial cells - Hui Liu; Chu-Xin Huang; Qiang He; Dong Li; Min-Hua Luo; Fei Zhao; Wei Lu (Journal of NeuroVirology, 2019)

Fermented cassava bioethanol waste as substitute of protein in diet for growth performance and carcass evaluation on meat ducks - Long Lei; Zhi Feng; Qiang Li; Xiaoqiang Xue; Dandan Zhang; Zhengya Liu; Yulan Liu; Ying Ren; Shengjun Zhao (Tropical Animal Health and Production, 2019)

Genome-wide identification, expression profiling, and protein-protein interaction properties of ovate family proteins in apple - Huifeng Li; Qinglong Dong; Qiang Zhao; Kun Ran (Tree Genetics & Genomes, 2019)

Cloning and Expression Analysis of SiCDPK4, a Gene Related to Heterosis in Foxtail Millet [(Setaria italica (L.) P. Beauv.)] - Dan Liu; Suying Li; Lina Wang; Qiang Li; Yanjiao Cui; Xiaodong Dai; Zilong Zhao; Chao Chen; Junxia Li; Zhengli Liu (Journal of Plant Growth Regulation, 2019)

Associations between the red blood cell distribution width and primary angle-closure glaucoma: a potential for disease prediction - Qiang Chen; Bin Zhao; Meng-ya Wang; Xue-yu Chen; Dong Li; Xin-quan Jiang; Jing-hui Tian; Yong-jun Liu (EPMA Journal, 2019)

Spatial variation and soil nitrogen potential hotspots in a mixed land cover catchment on the Chinese Loess Plateau - Yun-long Yu; Zhao Jin; Henry Lin; Yun-qiang Wang; Ya-li Zhao; Guang-chen Chu; Jing Zhang; Yi Song; Han Zheng (Journal of Mountain Science, 2019)

An Outbreak of Gastroenteritis Associated with GII.17 Norovirus-Contaminated Secondary Water Supply System in Wuhan, China, 2017 - Xuan Zhou; De-Guang Kong; Jing Li; Bei-Bei Pang; Ying Zhao; Jun-Bo Zhou; Ting Zhang; Jun-Qiang Xu; Nobumichi Kobayashi; Yuan-Hong Wang (Food and Environmental Virology, 2019)

The complete chloroplast genome of a rare and endangered elm (Ulmus chenmoui) endemic to East China - Hao Zhang; Qing Zhang; Weibing Fan; Xiaodan Chen; Jiao Wang; Qiang Li; Guifang Zhao (Conservation Genetics Resources, 2019)

Mitochondrial Gene Heterogeneity and Population Genetics of Haemaphysalis longicornis (Acari: Ixodidae) in China - Zhong-Bo Li; Yi-Tian Fu; Tian-Yin Cheng; Guo-Min Yao; Qiang-Hong Hou; Fen Li; Yu Zhao; Feng-Cai Zou; Guo-Hua Liu (Acta Parasitologica, 2019)

δ-Opioid Receptor Activation Attenuates the Oligomer Formation Induced by Hypoxia and/or α-Synuclein Overexpression/Mutation Through Dual Signaling Pathways - Tao Chen; Qinyu Wang; Dongman Chao; Terry C. Xia; Shiying Sheng; Zhuo-Ri Li; Jian-Nong Zhao; Guo-Qiang Wen; Guanghong Ding; Ying Xia (Molecular Neurobiology, 2019)

Testing the role of genetic variation of the MC4R gene in Chinese population in antipsychotic-induced metabolic disturbance - Yamin Zhang; Hongyan Ren; Qiang Wang; Wei Deng; Weihua Yue; Hao Yan; Liwen Tan; Qi Chen; Guigang Yang; Tianlan Lu; Lifang Wang; Fuquan Zhang; et al. (Science China Life Sciences, 2019)

Early identification and dynamic processes of ridge-top rockslides: implications from the Su Village landslide in Suichang County, Zhejiang Province, China - Chaojun Ouyang; Wei Zhao; Huicong An; Shu Zhou; Dongpo Wang; Qiang Xu; Weile Li; Dalei Peng (Landslides, 2019)

Dechlorination and conversion mechanism of trichlorobenzene as a model compound of chlorine-containing wastes by different base-catalyzed combinations - Shijin Dai; Yilin Zheng; Youcai Zhao; Qiang Li; Dongjie Niu (Environmental Science and Pollution Research, 2019)

The complete genome sequence of Escherichia phage SRT7, a novel T7-like phage - Kaili Zhao; Shukai Song; Zhipeng Zhao; Zichen Liu; Yan Ji; Pengfei Gu; Xiangyu Fan; Qiang Li (Archives of Virology, 2019)

Plant-derived phosphocholine facilitates cellular uptake of anti-pulmonary fibrotic HJT-sRNA-m7 - Jianchao Du; Zhu Liang; Jiantao Xu; Yan Zhao; Xiaoyun Li; Yanli Zhang; Dandan Zhao; Ruxuan Chen; Yang Liu; Trupti Joshi; Jiahui Chang; Zhiqing Wang; et al. (Science China Life Sciences, 2019)

Roles of mitochondrial fission inhibition in developmental fluoride neurotoxicity: mechanisms of action in vitro and associations with cognition in rats and children - Qian Zhao; Qiang Niu; Jingwen Chen; Tao Xia; Guoyu Zhou; Pei Li; Lixin Dong; Chunyan Xu; Zhiyuan Tian; Chen Luo; Luming Liu; Shun Zhang; et al. (Archives of Toxicology, 2019)

Antioxidant and α -glucosidase inhibitory ingredients identified from Jerusalem artichoke flowers - Yan-Ming Wang; Jian-Qiang Zhao; Jun-Li Yang; Pema Tsering Idong; Li-Juan Mei; Yan-Duo Tao; Yan-Ping Shi (Natural Product Research, 2019)

The influence of porcine epidemic diarrhea virus on pig small intestine mucosal epithelial cell function - Xing-Ye Wang; Tai-Qiang Zhao; De-Peng Xu; Xue Zhang; Cheng-Jie Ji; De-Li Zhang (Archives of Virology, 2019)

Late Paleocene–early Eocene granitoids in the Jiamusi Massif, NE China: Zircon U–Pb ages, geochemistry, and tectonic implications - Peng-Chuan Li; Zheng-Hong Liu; Shi-Chao Li; Qing-Ying Zhao; Qiang Shi; Chang-Hai Li; Xu-Hai Yang (International Geology Review, 2019)

Revegetation modifies patterns of temporal soil respiration responses to extreme-drying-and-rewetting in a semiarid ecosystem - Wenhao Sun; Xining Zhao; Qiang Ling; Hongchen Li; Xiaodong Gao (Plant and Soil, 2018)

Conditional and unconditional QTL analyses of seed hardness in vegetable soybean (Glycine max L. Merr.) - Yuanpeng Bu; Xing Zhang; Congcong Wang; Jingjie Guo; Xiaoli Zhang; Xiangnan Li; Qiang Yan; Jinming Zhao; Han Xing (Euphytica, 2018)

Effects of cadmium exposure on expression of glutathione synthetase system genes in Acidithiobacillus ferrooxidans - Chunli Zheng; Li Zhang; Minjie Chen; Xue Qiang Zhao; Yizhuo Duan; Ye Meng; Xuefeng Zhang; Ren Fang Shen (Extremophiles, 2018)

Antidepressant-like action of agmatine in the acute and sub-acute mouse models of depression: a receptor mechanism study - Zhao-Di Chen; Wen-Qiang Chen; Zhi-Yuan Wang; Dan-Ni Cao; Ning Wu; Jin Li (Metabolic Brain Disease, 2018)

Application on Floor Water Inrush Evaluation Based on AHP Variation Coefficient Method with GIS - Weitao Liu; Qiang Li; Jiyuan Zhao (Geotechnical and Geological Engineering, 2018)

Comparative analysis of molecular activity in dermal mesenchymal stem cells from different passages - Xinhua Li; Junqin Li; Xincheng Zhao; Qiang Wang; Xiaohong Yang; Yueai Cheng; Min Zhou; Gang Wang; Erle Dang; Xiaoli Yang; Ruixia Hou; Peng An; et al. (Cell and Tissue Banking, 2018)

A MHC–NF Coupling Model for Water Inrush from Collapse Columns and Its Numerical Simulation - Weitao Liu; Jiyuan Zhao; Qiang Li (Geotechnical and Geological Engineering, 2018)

Assessment of water inrush risk using the principal component logistic regression model in the Pandao coal mine, China - Weitao Liu; Qiang Li; Jiyuan Zhao; Biao Fu (Arabian Journal of Geosciences, 2018)

MiR-519d-3p suppresses breast cancer cell growth and motility via targeting LIM domain kinase 1 - Dengfeng Li; Hongming Song; Tianqi Wu; Dan Xie; Jiashu Hu; Junyong Zhao; Qiang Shen; Lin Fang (Molecular and Cellular Biochemistry, 2018)

Failure mechanisms and characteristics of the 2016 catastrophic rockslide at Su village, Lishui, China - Chaojun Ouyang; Wei Zhao; Qiang Xu; Dalei Peng; Weile Li; Dongpo Wang; Shu Zhou; Shunwei Hou (Landslides, 2018)

Nitrogen and phosphorus concentrations and allocation strategies among shrub organs: the effects of plant growth forms and nitrogen-fixation types - Qiang Zhang; Gaoming Xiong; Jiaxiang Li; Zhijun Lu; Yuelin Li; Wenting Xu; Yang Wang; Changming Zhao; Zhiyao Tang; Zongqiang Xie (Plant and Soil, 2018)

Analysis of the function of KIF3A and KIF3B in the spermatogenesis in Boleophthalmus pectinirostris - Yong-Qiang Zhao; Dan-Li Mu; Di Wang; Ying-Li Han; Cong-Cong Hou; Jun-Quan Zhu (Fish Physiology and Biochemistry, 2018)

Complete genome sequence of SRT8, a novel T1-like Escherichia coli bacteriophage - Kaili Zhao; Shukai Song; Zhipeng Zhao; Pengfei Gu; Xiangyu Fan; Qiang Li (Archives of Virology, 2018)

The ileal FGF15/19 to hepatic FGFR4 axis regulates liver regeneration after partial hepatectomy in mice - Qiang Li; Qiang Zhao; Chuanzhao Zhang; Peng Zhang; Anbin Hu; Longjuan Zhang; Paul M. Schroder; Yi Ma; Zhiyong Guo; Xiaofeng Zhu; Xiaoshun He (Journal of Physiology and Biochemistry, 2018)

Association of IL-28B, TBX21 gene polymorphisms and predictors of virological response for chronic hepatitis C - Dan Yan Zhu; Xiao Zhao Deng; Yu Meng Zhu; Guo Tao Li; Guo Qiang Zhang; Ling Ju Wang; Jing Hai Zhang; Wen Xiao; Zhen Xian Zhou; Wei Liang Ding (Archives of Virology, 2018)

Interaction network of core ABA signaling components in maize - Ying-Ge Wang; Feng-Ling Fu; Hao-Qiang Yu; Tao Hu; Yuan-Yuan Zhang; Yi Tao; Jian-Kang Zhu; Yang Zhao; Wan-Chen Li (Plant Molecular Biology, 2018)

Hydrogeochemistry and δ 13 C DIC and δ 18 O H2O composition of three Chinese Tibetan Plateau lakes - Xiaodan Wang; Shijie Li; Cong-Qiang Liu; Khan M. G. Mostofa; Zhiqi Zhao; Rongqin Luo (Isotopes in Environmental and Health Studies, 2018)

RETRACTED ARTICLE: TAT-PEP Enhanced Neurobehavioral Functional Recovery by Facilitating Axonal Regeneration and Corticospinal Tract Projection After Stroke - Bin Deng; Liya Li; Xingchun Gou; Hao Xu; Zhaohua Zhao; Qiang Wang; Lixian Xu (Molecular Neurobiology, 2018)

L1CAM drives oncogenicity in esophageal squamous cell carcinoma by stimulation of ezrin transcription - Jin-Cheng Guo; Yang-Min Xie; Li-Qiang Ran; Hui-Hui Cao; Chun Sun; Jian-Yi Wu; Zhi-Yong Wu; Lian-Di Liao; Wei-Jiang Zhao; Wang-Kai Fang; En-Min Li; Li-Yan Xu; et al. (Journal of Molecular Medicine, 2017)

Plasma and cerebrospinal fluid population pharmacokinetics of vancomycin in postoperative neurosurgical patients after combined intravenous and intraventricular administration - Xingang Li; Shusen Sun; Xi Ling; Kai Chen; Qiang Wang; Zhigang Zhao (European Journal of Clinical Pharmacology, 2017)

Complexity measure of regional seasonal precipitation series based on wavelet entropy - Dong Liu; Qiang Fu; Dan Zhao; Tianxiao Li (Hydrological Sciences Journal, 2017)

Interannual variability of PDSI from tree-ring widths for the past 278 years in Baotou, China - XinJia Zhang; Yu Liu; Huiming Song; Qiufang Cai; Qiang Li; Boyang Zhao; Han Liu; Ruochen Mei (Trees, 2017)

A New Imaging Approach for Dipole–Dipole Time-Domain Electromagnetic Data Based on the q-Transform - Hai Li; Guo-qiang Xue; Pan Zhao (Pure and Applied Geophysics, 2017)

Bioinformatic identification and expression analysis of the Malus domestica DREB2 transcription factors in different tissues and abiotic stress - Huifeng Li; Qiang Zhao; Xiaoli Sun; Houzhen Jia; Kun Ran (Journal of Plant Biochemistry and Biotechnology, 2017)

Characterization of mitochondrial prohibitin from Boleophthalmus pectinirostris and evaluation of its possible role in spermatogenesis - Di Wang; Yong-Qiang Zhao; Ying-Li Han; Cong-Cong Hou; Jun-Quan Zhu (Fish Physiology and Biochemistry, 2017)

Parental attendance of Chestnut Thrush reduces nest predation during the incubation period: compensation for low nest concealment? - Yun-Biao Hu; Qing-Shan Zhao; Ying-Qiang Lou; Li-Jun Chen; Manuel Antonio González; Yue-Hua Sun (Journal of Ornithology, 2017)

Hydroxy-Al and cell-surface negativity are responsible for the enhanced sensitivity of Rhodotorula taiwanensis to aluminum by increased medium pH - Xue Qiang Zhao; Xue Min Bao; Chao Wang; Zuo Yi Xiao; Zhen Min Hu; Chun Li Zheng; Ren Fang Shen (Archives of Microbiology, 2017)

Protein structure estimation from NMR data by matrix completion - Zhicheng Li; Yang Li; Qiang Lei; Qing Zhao (European Biophysics Journal, 2017)

Mechanism of Lycium barbarum polysaccharides on primary cultured rat hippocampal neurons - Peng Zhao; Ning-Tian Ma; Ren-Yuan Chang; Yu-Xiang Li; Yin-Ju Hao; Wen-Li Yang; Jie Zheng; Yang Niu; Tao Sun; Jian-Qiang Yu (Cell and Tissue Research, 2017)

A new sucrosephenylpropanoid ester from Polygonum pubescens Blume - Qiang Liu; Bin Li; Jianping Zhao; Shabana I. Khan; Wen-Bin Liu; Ting Zeng; Cai-Yun Peng; Xiong Cai; Qinghua Peng; Huiyong Huang; Ikhlas A. Khan; Wei Wang (Natural Product Research, 2017)

Identification of novel ATP7A mutations and prenatal diagnosis in Chinese patients with Menkes disease - Binbin Cao; Xiaoping Yang; Yinyin Chen; Qionghui Huang; Ye Wu; Qiang Gu; Jiangxi Xiao; Huixia Yang; Hong Pan; Junya Chen; Yu Sun; Li Ren; et al. (Metabolic Brain Disease, 2017)

Expression-based genotyping of the rice blast resistance genes in the elite maintainer line Yixiang1B - Li Wang; Xiao-Hong Hu; Gang Lin; De-Ming Zhao; Jun Shi; Zhi-Xue Zhao; Rui Zeng; Heng-Jing Li; De-Qiang Li; Jing Fan; Yan Li; Fu Huang; et al. (European Journal of Plant Pathology, 2017)

Environmental change and raw material selection strategies at Taoshan: a terminal Late Pleistocene to Holocene site in north‐eastern China - Shi‐Xia Yang; Yu‐Xiu Zhang; You‐Qian Li; Chao Zhao; Xiao‐Qiang Li; Jian‐Ping Yue; Ya‐Mei Hou; Cheng‐Long Deng; Ri‐Xiang Zhu; Michael D. Petraglia (Journal of Quaternary Science, 2017)
The Lesser Khingan Mountains of north‐eastern China are heavily forested, making archaeological site identification difficult owing to poor ground surface visibility. Nevertheless, several prehistoric archaeological site discoveries have been made in recent years and a limited number of excavations have been initiated. One of the most important sites to emerge is Taoshan, which has yielded stratified stone tool assemblages dating from the Last Glacial Maximum (LGM) to the mid‐Holocene. Pollen profiles indicate significant changes in vegetation, fluctuating from steppe conditions during the LGM to forested conditions in the Bølling–Allerød interstadial (B–A) and the mid‐Holocene. The stone tool assemblages from Taoshan were primarily produced from varieties of volcanic tuff, rhyolite, hornfels and agate. Geological prospecting and petrological analyses were performed to document procurement sources and changes in raw material exploitation strategies. During the LGM, the predominant raw material was vitric tuff, available from a source ca. 5–10 km from Taoshan. In the B–A and mid‐Holocene layers, emphasis was on the exploitation of raw materials in gravel bars, although stone tool reduction techniques and raw material preferences changed considerably during this time interval. Diachronic changes in raw materials and exploitation strategies correspond to changes in vegetation and human adaptations.

Separation of antioxidant and α -glucosidase inhibitory flavonoids from the aerial parts of Asterothamnus centrali - asiaticus - Yan-Ming Wang; Jian-Qiang Zhao; Jun-Li Yang; Yan-Duo Tao; Li-Juan Mei; Yan-Ping Shi (Natural Product Research, 2017)

Dietary exposure to aluminium in the popular Chinese fried bread youtiao - Ge Li; Xue Zhao; Shimin Wu; Hongying Hua; Qiang Wang; Zhiheng Zhang (Food Additives & Contaminants: Part A, 2017)

Genetic diagnosis of a Chinese multiple endocrine neoplasia type 2A family through whole genome sequencing - Zhen-Fang Du; Peng-Fei Li; Jian-Qiang Zhao; Zhi-Lie Cao; Feng Li; Ju-Ming Ma; Xiao-Ping Qi (Journal of Biosciences, 2017)

Evolutionary mechanism and biological functions of 8-mers containing CG dinucleotide in yeast - Yan Zheng; Hong Li; Yue Wang; Hu Meng; Qiang Zhang; Xiaoqing Zhao (Chromosome Research, 2017)

On the potential application of land surface models for drought monitoring in China - Liang Zhang; Huqiang Zhang; Qiang Zhang; Yaohui Li; Jianhua Zhao (Theoretical and Applied Climatology, 2017)

Simple-MSSM: a simple and efficient method for simultaneous multi-site saturation mutagenesis - Feng Cheng; Jian-Miao Xu; Chao Xiang; Zhi-Qiang Liu; Li-Qing Zhao; Yu-Guo Zheng (Biotechnology Letters, 2017)

Estrogen-like neuroprotection of isopsoralen against spinal cord injury through estrogen receptor ERα - Xiao-ming Li; Qi Yang; Xu-bo Li; Qiang Cheng; Kun Zhang; Jing Han; Jian-ning Zhao; Gang Liu; Ming-gao Zhao (Metabolic Brain Disease, 2017)

RNA-Seq Analysis of the Antioxidant Status and Immune Response of Portunus trituberculatus Following Aerial Exposure - Yuquan Li; Shoumin Lai; Renjie Wang; Yuchao Zhao; Hao Qin; Lingxu Jiang; Na Li; Qiang Fu; Chao Li (Marine Biotechnology, 2017)

Tree-ring-width-based PDSI reconstruction for central Inner Mongolia, China over the past 333 years - Yu Liu; Xinjia Zhang; Huiming Song; Qiufang Cai; Qiang Li; Boyang Zhao; Han Liu; Ruochen Mei (Climate Dynamics, 2017)

Chemical composition and antioxidant activities of essential oils from different parts of the oregano - Fei Han; Guang-qiang Ma; Ming Yang; Li Yan; Wei Xiong; Ji-cheng Shu; Zhi-dong Zhao; Han-lin Xu (Journal of Zhejiang University-SCIENCE B, 2017)

C-myc overexpression drives melanoma metastasis by promoting vasculogenic mimicry via c-myc/snail/Bax signaling - Xian Lin; Ran Sun; Xiulan Zhao; Dongwang Zhu; Xueming Zhao; Qiang Gu; Xueyi Dong; Danfang Zhang; Yanhui Zhang; Yanlei Li; Baocun Sun (Journal of Molecular Medicine, 2017)

Two new compounds from Trollius chinensis Bunge - Ya Jie-Shi; Lin Wei-Sang; Rui Yan; Qiang Zhao; Yang Zhang; Gui Yun-Zhao; Yun Cong-Li; Xue Chen; Chong Yu-Zhang; Hua Qiao; Guo Gang-Zhang (Journal of Natural Medicines, 2017)

Complexity measurement of regional groundwater resources system using improved Lempel-Ziv complexity algorithm - Dong Liu; Dan Zhao; Qiang Fu; Qiuchen Wu; Yongjia Zhang; Tianxiao Li; Khan M Imran; Faiz M Abrar (Arabian Journal of Geosciences, 2016)

Effect of cadmium exposure on antioxidant enzyme catalase in different tissues of Acrossocheilus fasciatus - Yong-Qiang Zhao; Guo-Di Liu; Cong-Cong Hou; Ying-Li Han; Jun-Quan Zhu (Molecular & Cellular Toxicology, 2016)

Selenoprotein X Gene Knockdown Aggravated H2O2-Induced Apoptosis in Liver LO2 Cells - Jiayong Tang; Lei Cao; Qiang Li; Longqiong Wang; Gang Jia; Guangmang Liu; Xiaoling Chen; Jingyi Cai; Haiying Shang; Hua Zhao (Biological Trace Element Research, 2016)

Analysis of the Appropriate Development Scale of Regional Paddy Field Under the Restriction of Water Resources - Dong Liu; Dan Zhao; Qiang Fu; Tianxiao Li; Muhammad Imran Khan; Wenting Liu; Faiz M. Abrar (Agricultural Research, 2016)

A new isocoumarin from the aerial parts of Aconitum gymnandrum - Jian-Qiang Zhao; Yan-Ming Wang; Shuo Wang; Jun Dang; Yan-Ping Shi; Li-Juan Mei; Yan-Duo Tao (Natural Product Research, 2016)

The Hilbert–Huang Transform-Based Denoising Method for the TEM Response of a PRBS Source Signal - Li Hai; Xue Guo-qiang; Zhao Pan; Zhong Hua-sen; Muhammad Younis Khan (Pure and Applied Geophysics, 2016)

Exendin-4 Enhances Motor Function Recovery via Promotion of Autophagy and Inhibition of Neuronal Apoptosis After Spinal Cord Injury in Rats - Hao-Tian Li; Xing-Zhang Zhao; Xin-Ran Zhang; Gang Li; Zhi-Qiang Jia; Ping Sun; Ji-Quan Wang; Zhong-Kai Fan; Gang Lv (Molecular Neurobiology, 2016)

Expression of Selenoprotein Genes Is Affected by Heat Stress in IPEC-J2 Cells - Lei Cao; Jiayong Tang; Qiang Li; Jingyang Xu; Gang Jia; Guangmang Liu; Xiaoling Chen; Haiying Shang; Jingyi Cai; Hua Zhao (Biological Trace Element Research, 2016)

Effects of experimental warming on soil microbial communities in two contrasting subalpine forest ecosystems, eastern Tibetan Plateau, China - Di-di Sun; Yue-jiao Li; Wen-qiang Zhao; Zi-liang Zhang; Dan-dan Li; Chun-zhang Zhao; Qing Liu (Journal of Mountain Science, 2016)

Two new compounds from the roots of Ilex pubescens and their cytotoxic activity - Huan Xiong; Fang Zhao; Jiayi Bi; Yang Zhang; Guiyun Zhao; Xue Chen; Yuncong Li; Rui Yan; Qiang Zhao; Hua Qiao; Guogang Zhang (Journal of Natural Medicines, 2016)

Finite element numerical simulation of 2.5D direct current method based on mesh refinement and recoarsement - Qian-Jiang Zhang; Shi-Kun Dai; Long-Wei Chen; Jian-Ke Qiang; Kun Li; Dong-Dong Zhao (Applied Geophysics, 2016)

The Application of a Water Rights Trading Model Based on two-Stage Interval-Parameter Stochastic Programming - Qiang Fu; Ke Zhao; Dong Liu; Qiuxiang Jiang; Tianxiao Li; Changhong Zhu (Water Resources Management, 2016)

Bacillus nitroreducens sp. nov., a humus-reducing bacterium isolated from a compost - Junhui Guo; Yue qiang Wang; Guiqin Yang; Yunqi Chen; Shungui Zhou; Yong Zhao; Li Zhuang (Archives of Microbiology, 2016)

Unravelling the relationship between macroautophagy and mitochondrial ROS in cancer therapy - Yuqian Zhao; Tiange Qu; Peiqi Wang; Xinyi Li; Jiayu Qiang; Zhaokun Xia; Hangwu Duan; Jian Huang; Lingjuan Zhu (Apoptosis, 2016)

Two-Stage Interval-Parameter Stochastic Programming Model Based on Adaptive Water Resource Management - Qiang Fu; Ke Zhao; Dong Liu; Qiuxiang Jiang; Tianxiao Li; Changhong Zhu (Water Resources Management, 2016)

Isolation, identification and genomic characterization of the Asian lineage Zika virus imported to China - Yong-Qiang Deng; Hui Zhao; Xiao-Feng Li; Na-Na Zhang; Zhong-Yu Liu; Tao Jiang; Da-Yong Gu; Lei Shi; Jian-An He; Hong-Jiang Wang; Zhao-Zeng Sun; Qing Ye; et al. (Science China Life Sciences, 2016)

A highly efficient grapevine mesophyll protoplast system for transient gene expression and the study of disease resistance proteins - Feng-Li Zhao; Ya-Juan Li; Yang Hu; Yu-Rong Gao; Xue-Wen Zang; Qin Ding; Yue-Jin Wang; Ying-Qiang Wen (Plant Cell, Tissue and Organ Culture (PCTOC), 2016)

De novo assembly and characterization of the leaf, bud, and fruit transcriptome from the vulnerable tree Juglans mandshurica for the development of 20 new microsatellite markers using Illumina sequencing - Zhuang Hu; Tian Zhang; Xiao-Xiao Gao; Yang Wang; Qiang Zhang; Hui-Juan Zhou; Gui-Fang Zhao; Ma-Li Wang; Keith E. Woeste; Peng Zhao (Molecular Genetics and Genomics, 2016)

Heterologous biosynthesis of triterpenoid dammarenediol-II in engineered Escherichia coli - Dashuai Li; Qiang Zhang; Zhijiang Zhou; Fanglong Zhao; Wenyu Lu (Biotechnology Letters, 2016)

CXCL16 upregulates RANKL expression in rheumatoid arthritis synovial fibroblasts through the JAK2/STAT3 and p38/MAPK signaling pathway - Chang-hong Li; Lin-lin Xu; Jin-xia Zhao; Lin Sun; Zhong-qiang Yao; Xiao-li Deng; Rui Liu; Lin Yang; Rui Xing; Xiang-yuan Liu (Inflammation Research, 2016)

The Protective Effects of Melatonin Against Oxidative Stress and Inflammation Induced by Acute Cadmium Exposure in Mice Testis - Renyan Li; Xue Luo; Lianbing Li; Qiang Peng; Yuyou Yang; Letian Zhao; Mingfu Ma; Zhiwei Hou (Biological Trace Element Research, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

New cytotoxic lignan glycosides from Phyllanthus glaucus - Shan Yu; Jun-Jiang Lv; Jian-Qiang Zhao; Yan Li; Dong Wang; Chong-Ren Yang; Min Xu; Ying-Jun Zhang (Natural Product Research, 2016)

Re–Os and U–Pb geochronology of the Laochang Pb–Zn–Ag and concealed porphyry Mo mineralization along the Changning–Menglian suture, SW China: implications for ore genesis and porphyry Cu–Mo exploration - Xiao-Dong Deng; Jian-Wei Li; Xin-Fu Zhao; Hong-Qiang Wang; Liang Qi (Mineralium Deposita, 2016)

The effect of different feeding rates on growth, feed efficiency and immunity of juvenile Penaeus monodon - Jin Niu; Xu Chen; Yun-Qiang Zhang; Li-Xia Tian; Hei-Zhao Lin; Jun Wang; Yun Wang; Yong-Jian Liu (Aquaculture International, 2016)

Differential distribution patterns of ammonia-oxidizing archaea and bacteria in acidic soils of Nanling National Nature Reserve forests in subtropical China - Xian-Hua Gan; Fang-Qiu Zhang; Ji-Dong Gu; Yue-Dong Guo; Zhao-Qing Li; Wei-Qiang Zhang; Xiu-Yu Xu; Yi Zhou; Xiao-Ying Wen; Guo-Guang Xie; Yong-Feng Wang (Antonie van Leeuwenhoek, 2016)

Precipitation Complexity Measurement Using Multifractal Spectra Empirical Mode Decomposition Detrended Fluctuation Analysis - Dong Liu; Mingjie Luo; Qiang Fu; Yongjia Zhang; Khan M. Imran; Dan Zhao; Tianxiao Li; Faiz M. Abrar (Water Resources Management, 2016)

Serum Levels of Thioredoxin Are Associated with Stroke Risk, Severity, and Lesion Volumes - Meng-Hai Wu; Fang-Yu Song; Li-Ping Wei; Zhao-Yun Meng; Zhi-Qiang Zhang; Qin-De Qi (Molecular Neurobiology, 2016)

Responses of soil fungal community to the sandy grassland restoration in Horqin Sandy Land, northern China - Shao-Kun Wang; Xiao-An Zuo; Xue-Yong Zhao; Yu-Qiang Li; Xin Zhou; Peng Lv; Yong-Qing Luo; Jian-Ying Yun (Environmental Monitoring and Assessment, 2016)

The Prevention Effect of Selenium on Prevalence of Children Kaschin-Beck Disease in Active Endemic Areas in Qinghai Plateau - Qiang Li; Zhi-jun Zhao; Pei-zhen Yang; Xiao-qing Xu; Yu-fang Liu; Hui-zhen Yu; Xiao Ma; Rui Du; Lei Zhu (Biological Trace Element Research, 2016)

IL-17A enhances ADAMTS-7 expression through regulation of TNF-α in human nucleus pulposus cells - Shuai-Shuai Wang; Wei Zhang; Yuan-Qiang Zhang; Yunpeng Zhao; Yi Liu; Jing-kun Li; Hao-xuan Zhang; Lei Cheng; Lin Nie (Journal of Molecular Histology, 2015)

Forty-nine SNP markers developed from the genome dataset of Pacific abalone (Haliotis discus hannai) and their application in population genetic analysis - Qian Yu; Yangping Li; Qiang Xing; Xue Li; Liang Zhao; Yangfan Wang; Xiaoli Hu; Zhenmin Bao (Conservation Genetics Resources, 2015)

Adaptive Allocation Modeling for a Complex System of Regional Water and Land Resources Based on Information Entropy and its Application - Kun Cheng; Qiang Fu; Xi Chen; Tianxiao Li; Qiuxiang Jiang; Xiaosong Ma; Ke Zhao (Water Resources Management, 2015)

Protective effects of aloperine on neonatal rat primary cultured hippocampal neurons injured by oxygen–glucose deprivation and reperfusion - Ning-Tian Ma; Ru Zhou; Ren-Yuan Chang; Yin-Ju Hao; Lin Ma; Shao-Ju Jin; Juan Du; Jie Zheng; Cheng-Jun Zhao; Yang Niu; Tao Sun; Wei Li; et al. (Journal of Natural Medicines, 2015)

Evaluation of Water Inrush Vulnerability from Aquifers Overlying Coal Seams in the Menkeqing Coal Mine, China - Qiang Wu; Yuanzhang Liu; Wanfang Zhou; Baoyu Li; Bin Zhao; Shouqiang Liu; Wenjie Sun; Yifan Zeng (Mine Water and the Environment, 2015)

Potential dental pulp revascularization and odonto-/osteogenic capacity of a novel transplant combined with dental pulp stem cells and platelet-rich fibrin - Yong-Jin Chen; Yin-Hua Zhao; Ya-Juan Zhao; Nan-Xia Liu; Xin Lv; Qiang Li; Fa-Ming Chen; Min Zhang (Cell and Tissue Research, 2015)

Therapeutic potential of human umbilical cord blood mesenchymal stem cells on erectile function in rats with cavernous nerve injury - Jian-Qiang Zhu; Hong-Kai Lu; Zhi-Qiang Cui; Yong-Chuan Wang; Yong-Hui Li; Weixin Zhao; Qiang Fu; Yue-Min Xu; Yong Xu; Lu-Jie Song (Biotechnology Letters, 2015)

Soil organic matter fractions under different vegetation types in permafrost regions along the Qinghai-Tibet Highway, north of Kunlun Mountains, China - Wen Shang; Lin Zhao; Xiao-dong Wu; Yu-qiang Li; Guang-yang Yue; Yong-hua Zhao; Yong-ping Qiao (Journal of Mountain Science, 2015)

Apolipoprotein E gene polymorphisms associated with processing speed and executive functions in healthy Han Chinese - Cheng-Cheng Zhang; Hong-Yan Ren; Ming-Li Li; Qiang Wang; Wei Deng; Wan-Jun Guo; Wei Lei; Bo Xiang; Lian-Sheng Zhao; Xiao-Hong Ma; Yong-Gang Yao; Tao Li (Neuroscience Bulletin, 2015)

Bacterial community composition at anodes of microbial fuel cells for paddy soils: the effects of soil properties - Ning Wang; Zheng Chen; Hong-Bo Li; Jian-Qiang Su; Feng Zhao; Yong-Guan Zhu (Journal of Soils and Sediments, 2015)

Characteristics of Na+ uptake in sugar beet (Beta vulgaris L.) seedlings under mild salt conditions - Guo-Qiang Wu; Qing-Zhao Shui; Chun-Mei Wang; Jin-Lin Zhang; Hui-Jun Yuan; Shan-Jia Li; Zuo-Jun Liu (Acta Physiologiae Plantarum, 2015)

In vivo construction of tissue-engineered cartilage using adipose-derived stem cells and bioreactor technology - Hongjun Kang; Shibi Lu; Jiang Peng; Qiang Yang; Shuyun Liu; Li Zhang; Jingxiang Huang; Xiang Sui; Bin Zhao; Aiyuan Wang; Wenjing Xu; Quanyi Guo; et al. (Cell and Tissue Banking, 2015)

Morphological changes in gray matter volume correlate with catechol-O-methyl transferase gene Val158Met polymorphism in first-episode treatment-naïve patients with schizophrenia - Ming-Li Li; Bo Xiang; Yin-Fei Li; Xun Hu; Qiang Wang; Wan-Jun Guo; Wei Lei; Chao-Hua Huang; Lian-Sheng Zhao; Na Li; Hong-Yan Ren; Hui-Yao Wang; et al. (Neuroscience Bulletin, 2015)

Rapid evaluation of reference evapotranspiration in Northern China - Shao-hua Zhao; Yong-hui Yang; Feng Zhang; Xin-xin Sui; Yun-jun Yao; Na Zhao; Qiuxiao Zhao; Chun-qiang Li (Arabian Journal of Geosciences, 2015)

Genome-wide identification and characterization of R2R3MYB family in Solanum lycopersicum - Panpan Zhao; Qiang Li; Jing Li; Lina Wang; Zhonghai Ren (Molecular Genetics and Genomics, 2014)

Isolation and characterization of polymorphic microsatellites in the perennial herb Euphorbia kansui using paired-end Illumina shotgun sequencing - Xiao-Hao Yan; Min-Feng Fang; Zeng-Qiang Qian; Zhan-Lin Liu; Ma-Li Wang; Cai-Ping Tian; Meng-Han Du; Yin-Jun Li; Zhong-Hu Li; Gui-Fang Zhao (Conservation Genetics Resources, 2014)

Pro-Apoptotic Effects of the Novel Tangeretin Derivate 5-Acetyl-6,7,8,4′-Tetramethylnortangeretin on MCF-7 Breast Cancer Cells - Jinhan Wang; Yitao Duan; Dexian Zhi; Guangqiang Li; Liwen Wang; Hongmei Zhang; Lichao Gu; Haihua Ruan; Kunsheng Zhang; Qiang Liu; Shiming Li; Chi-Tang Ho; et al. (Cell Biochemistry and Biophysics, 2014)

Variation in copper and zinc tolerance and accumulation in 12 willow clones: implications for phytoextraction - Wei-dong Yang; Yu-yan Wang; Feng-liang Zhao; Zhe-li Ding; Xin-cheng Zhang; Zhi-qiang Zhu; Xiao-e Yang (Journal of Zhejiang University-SCIENCE B, 2014)

Diffusion Source Detection of Volcanic Ash Cloud Using MODIS Satellite Data - Cheng-Fan Li; Yang-Yang Dai; Jun-Juan Zhao; Jing-Yuan Yin; Dan Xue; Shi-Qiang Zhou (Journal of the Indian Society of Remote Sensing, 2014)

Establishment of Rat Model of Central Venous Catheter (CVC): Associated Infection and Evaluation of the Virulence of Bacterial Biofilms - Lian-Hua Ye; Yun-Chao Huang; Feng-Li Guo; Xin Liu; Guang-Qiang Zhao; Lin-Can Duan; Cong-Guo Jin (Cell Biochemistry and Biophysics, 2014)

Application of aircraft observations over Beijing in cloud microphysical property retrievals from CloudSat - Lei Wang; Chengcai Li; Zhigang Yao; Zengliang Zhao; Zhigang Han; Qiang Wei (Advances in Atmospheric Sciences, 2014)

Identification of a putative cognate sensor kinase for the two‐component response regulator HrpG , a key regulator controlling the expression of the hrp genes in X anthomonas campestris pv. campestris - Rui‐Fang Li; Guang‐Tao Lu; Lei Li; Hui‐Zhao Su; Guo‐fang Feng; Ya Chen; Yong‐Qiang He; Bo‐Le Jiang; Dong‐Jie Tang; Ji‐Liang Tang (Environmental Microbiology, 2014)
Summary The bacterial phytopathogen X anthomonas campestris pv. campestris ( Xcc ) relies on the hrp (hypersensitive response and pathogenicity) genes to cause disease and induce hypersensitive response ( HR ). The hrp genes of bacterial phytopathogens are divided into two groups. Xcc hrp genes belong to group II . It has long been known that the group II hrp genes are activated by an AraC ‐type transcriptional regulator whose expression is controlled by a two‐component system ( TCS ) response regulator (named HrpG in Xcc ). However, no cognate sensor kinase has yet been identified. Here, we present evidence showing that the Xcc open‐reading frame XC _3670 encodes a TCS sensor kinase (named HpaS ). Mutation of hpaS almost completely abolished the HR induction and virulence. Bacterial two‐hybrid and protein pull‐down assays revealed that HpaS physically interacted with HrpG . Phos‐tag™ SDS‐PAGE analysis showed that mutation in hpaS reduced markedly the phosphorylation of HrpG in vivo . These data suggest that HpaS and HrpG are most likely to form a TCS . We also showed that XC _3669 (named hpaR2 ), which is adjacent to hpaS and encodes a putative TCS response regulator, is required for full virulence but not HR induction. HpaR2 also physically interacted with HpaS , suggesting that HpaS may also form another TCS with HpaR2 .

An automatic seismic signal detection method based on fourth-order statistics and applications - Xi-Qiang Liu; Yin Cai; Rui Zhao; Yin-Gang Zhao; Bao-An Qu; Zhi-Jun Feng; Hong Li (Applied Geophysics, 2014)

Genetic analysis and fine mapping of RpsJS, a novel resistance gene to Phytophthora sojae in soybean [Glycine max (L.) Merr.] - Jutao Sun; Lihong Li; Jinming Zhao; Jing Huang; Qiang Yan; Han Xing; Na Guo (Theoretical and Applied Genetics, 2014)

Development and characterization of EST-derived microsatellite makers for Manila clam (Ruditapes philippinarum) - Hong-Tao Nie; De-Peng Zhu; Feng Yang; Li-Qiang Zhao; Xi-Wu Yan (Conservation Genetics Resources, 2014)

Pharmacokinetics of sulfamonomethoxine in tongue sole (Cynoglossus semilaevis) after intravenous and oral administration - Zhi-Qiang Chang; Zhao-Xin Li; Jing-Bao Li; Ying-Zi Wang; Jian Li (Fish Physiology and Biochemistry, 2014)

Genes in the serotonin pathway are associated with bipolar affective disorder in a Han Chinese population - Bo Xiang; Zhenxing Yang; Yin Lin; Lijie Guan; Xuan Li; Wei Deng; Zeyu Jiang; Guohui Lao; Qiang Wang; Xiaoyu Hao; Xiang Liu; Yingcheng Wang; et al. (Neuroscience Bulletin, 2014)

Genome-wide analysis of the WD-repeat protein family in cucumber and Arabidopsis - Qiang Li; Panpan Zhao; Jing Li; Cunjia Zhang; Lina Wang; Zhonghai Ren (Molecular Genetics and Genomics, 2014)

A comparison of forest fire indices for predicting fire risk in contrasting climates in China - Xiaowei Li; Gang Zhao; Xiubo Yu; Qiang Yu (Natural Hazards, 2014)

Y chromosome diversity and paternal origin of Chinese cattle - Ran Li; Wen-Mei Xie; Zhen-Hua Chang; Shao-Qiang Wang; Rui-Hua Dang; Xian-Yong Lan; Hong Chen; Chu-Zhao Lei (Molecular Biology Reports, 2013)

Sorption of ammonium and phosphate from aqueous solution by biochar derived from phytoremediation plants - Zheng Zeng; Song-da Zhang; Ting-qiang Li; Feng-liang Zhao; Zhen-li He; He-ping Zhao; Xiao-e Yang; Hai-long Wang; Jing Zhao; Muhammad Tariq Rafiq (Journal of Zhejiang University-SCIENCE B, 2013)

Correlation Between Cerebral Infarction and ALOX5AP Gene Expression - Chen Xu; Li Qiang; Cao Limei; Zhang Yan; Zheng Jia; Dong Zhiqiang; Zhongxin Zhao (Cell Biochemistry and Biophysics, 2013)

MK-2206 induces cell cycle arrest and apoptosis in HepG2 cells and sensitizes TRAIL-mediated cell death - Peng Jiao; Yun-Sheng Zhou; Juan-Xia Yang; Ya-Li Zhao; Qiang-Qiang Liu; Chuang Yuan; Feng-Ze Wang (Molecular and Cellular Biochemistry, 2013)

Dietary capsaicin prevents nonalcoholic fatty liver disease through transient receptor potential vanilloid 1-mediated peroxisome proliferator-activated receptor δ activation - Qiang Li; Li Li; Fei Wang; Jian Chen; Yu Zhao; Peijian Wang; Bernd Nilius; Daoyan Liu; Zhiming Zhu (Pflügers Archiv - European Journal of Physiology, 2013)

The Antitumor Effect of a New Docetaxel-Loaded Microbubble Combined with Low-Frequency Ultrasound In Vitro: Preparation and Parameter Analysis - Shu-Ting Ren; Yi-Ran Liao; Xiao-Ning Kang; Yi-Ping Li; Hui Zhang; Hong Ai; Qiang Sun; Jing Jing; Xing-Hua Zhao; Li-Fang Tan; Xin-Liang Shen; Bing Wang (Pharmaceutical Research, 2013)

Anxiolytic Actions of Motilin in the Basolateral Amygdala - Bin Feng; Jin-cheng Liu; Jun Zhang; Ken-ichi Ozaki; Yan-yan Guo; Ding-hua Yi; Xiao-qiang Li; Ming-gao Zhao (Molecular Neurobiology, 2013)

Selenium: A Protective Factor for Kaschin–Beck Disease in Qing-Tibet Plateau - Zhi-Jun Zhao; Qiang Li; Pei-zhen Yang; Hu Wang; Ling-chuan Kong; Li-hua Wang; Li-yan Sun (Biological Trace Element Research, 2013)

Strategy for pH control and pH feedback-controlled substrate feeding for high-level production of l-tryptophan by Escherichia coli - Li-Kun Cheng; Jian Wang; Qing-Yang Xu; Chun-Guang Zhao; Zhi-Qiang Shen; Xi-Xian Xie; Ning Chen (World Journal of Microbiology and Biotechnology, 2013)

Optimization of Cultivating Conditions for Triterpenoids Production from Antrodia cinnmomea - Yuan-Chuan He; Kai-Ze He; Qiang Pu; Jing Li; Zong-Jie Zhao (Indian Journal of Microbiology, 2012)

T-2 Toxin Contamination in Grains and Selenium Concentration in Drinking Water and Grains in Kaschin–Beck Disease Endemic Areas of Qinghai Province - Li-Yan Sun; Qiang Li; Fan-Gang Meng; Ying Fu; Zhi-Jun Zhao; Li-Hua Wang (Biological Trace Element Research, 2012)

Synthesis, crystal structure and biological activity of novel anthranilic diamide insecticide containing alkyl ether group - Yu Zhao; Li-ping Xu; Jun Tong; Yong-qiang Li; Li-xia Xiong; Fang Li; Li-na Peng; Zheng-ming Li (Molecular Diversity, 2012)

Molecular cloning and expression analysis of common carp Cyprinus carpio tumor necrosis factor-α - Xiao Zhao; Duo Duan; Xiangru Feng; Yilong Chen; Zhen Sun; Shengmei Jia; Jiangshuai He; Bin Wang; Wei Li; Junhui Zhang; Wendong Wang; Zhenguo Yang; et al. (Fisheries Science, 2012)

Benfotiamine prevents increased β-amyloid production in HEK cells induced by high glucose - Xiao-Jing Sun; Lei Zhao; Na Zhao; Xiao-Li Pan; Guo-Qiang Fei; Li-Rong Jin; Chun-Jiu Zhong (Neuroscience Bulletin, 2012)

Association study of ACE polymorphisms and systemic lupus erythematosus in Northern Chinese Han population - Ai-min Gong; Xin-yuan Li; Yi-qin Wang; Hai-xia Yan; Zhao-xia Xu; Zhao Feng; Yi-qiang Xie; De-hui Yin; Shi-zhong Yang (Molecular Biology Reports, 2012)

Ultrasound-promoted synthesis and immunosuppressive activity of novel quinazoline derivatives - Lei Zhang; Zhe Gao; Chen Peng; Zheng-Yang Bin; Dan Zhao; Jing Wu; Qiang Xu; Jian-Xin Li (Molecular Diversity, 2012)

Effects of 1,1,1-trichloroethane on enzymatic activity and bacterial community in anaerobic microcosm form sequencing batch reactors - Hui Li; Wei Zhang; Lu Li; Yong-Di Liu; Kuang-Fei Lin; Shu-Guang Lu; Bo-Zhong Mu; Xiao-Ming Du; Qiang Lu; Qian Zhang; Ting-Ting Shen; Bing-Zhi Li; et al. (Ecotoxicology, 2012)

3-Nitro-naphthalimide and nitrogen mustard conjugate NNM-25 induces hepatocellular carcinoma apoptosis via PARP-1/p53 pathway - Song-qiang Xie; Ya-hong Zhang; Qian Li; Feng-hua Xu; Jiu-wang Miao; Jin Zhao; Chao-jie Wang (Apoptosis, 2012)

Improving the discrimination capability of bioaerosols using a dual-channel ultraviolet aerodynamic particle sizer spectrometer - Xiao-Ling Ma; Wei-Xiong Zhao; Jia-Qiang Zhao; Na Li; Hai-Yang Zheng; Li Fang; Fei-Hu Chen; Wei-Jun Zhang (Aerobiologia, 2012)

Seismic geomorphology and main controls of deep-water gravity flow sedimentary process on the slope of the northern South China Sea - Lei Li; YingMin Wang; Qiang Xu; JingZhou Zhao; Dong Li (Science China Earth Sciences, 2012)

Salicylic acid-altering Arabidopsis mutants response to salt stress - Lin Hao; Yan Zhao; Dandan Jin; Ling Zhang; Xiaohua Bi; Hongxing Chen; Qiang Xu; Chunyan Ma; Guangzhe Li (Plant and Soil, 2012)

Molecular cloning and functional characterization of a novel apple MdCIPK6L gene reveals its involvement in multiple abiotic stress tolerance in transgenic plants - Rong-Kai Wang; Ling-Li Li; Zhong-Hui Cao; Qiang Zhao; Ming Li; Ling-Yun Zhang; Yu-Jin Hao (Plant Molecular Biology, 2012)

Neuroprotective Effects of Salidroside and its Analogue Tyrosol Galactoside Against Focal Cerebral Ischemia In Vivo and H2O2-Induced Neurotoxicity In Vitro - Tian-yao Shi; Shu-fang Feng; Jiang-hao Xing; Yu-mei Wu; Xiao-qiang Li; Nan Zhang; Zhen Tian; Shui-bing Liu; Ming-gao Zhao (Neurotoxicity Research, 2012)

Physiological variations in chloroplasts of Rhodiola coccinea along an altitudinal gradient in Tianshan Mountain - Tuo Chen; Zhiguang Zhao; Youfu Zhang; Weiya Qiang; Huyuan Feng; Lizhe An; Zhongqin Li (Acta Physiologiae Plantarum, 2012)

Modification of the land surface energy balance relationship by introducing vertical sensible heat advection and soil heat storage over the Loess Plateau - Qiang Zhang; HongYu Li; JianHua Zhao (Science China Earth Sciences, 2012)

Cutaneous Protothecosis in Patient with Diabetes Mellitus and Review of Published Case Reports - Qiang-Qiang Zhang; Li Li; Li-Ping Zhu; Ying Zhao; Yun-Ru Wang; Jun-hao Zhu; Min Zhu (Mycopathologia, 2012)

SNIP1: a new activator of HSE signaling pathway - Qiang Li; Jian An; Xianghua Liu; Mingjun Zhang; Yichen Ling; Chenji Wang; Jing Zhao; Long Yu (Molecular and Cellular Biochemistry, 2012)

Molecular Cloning, Sequence Analysis, and Expression of the Polygalacturonase-inhibiting Protein (PGIP) Gene in Mulberry - Dongqing Hu; Ruiqiang Dai; Yuhua Wang; Yinghua Zhang; Zhaoyue Liu; Rongjun Fang; Weiguo Zhao; Long Li; Qiang Lin; Liu Li (Plant Molecular Biology Reporter, 2012)

Paleomagnetic results of Late Paleozoic rocks from northern Qiangtang Block in Qinghai-Tibet Plateau, China - Xin Cheng; HanNing Wu; Qiang Guo; BaoNing Hou; LingYan Xia; HaiJun Wang; ZongBao Diao; FeiFei Huo; WenHua Ji; RongShe Li; ShouJian Chen; ZhenMing Zhao; et al. (Science China Earth Sciences, 2012)

In Vitro Model of Bacterial Biofilm Formation on Polyvinyl Chloride Biomaterial - Guang-qiang Zhao; Lian-hua Ye; Yun-chao Huang; Da-kuan Yang; Li Li; Geng Xu; Yu-jie Lei (Cell Biochemistry and Biophysics, 2011)

Effect of Atorvastatin (Lipitor) on Myocardial Apoptosis and Caspase-8 Activation Following Coronary Microembolization - Lang Li; Qiang Su; Yan Wang; Rixin Dai; Yongguang Lu; Bo Su; Yongxiang Zhao (Cell Biochemistry and Biophysics, 2011)

Effects of exogenous hydrogen sulfide on the ascorbate and glutathione metabolism in wheat seedlings leaves under water stress - Chang-juan Shan; Sheng-li Zhang; Dong-fang Li; Yuan-zeng Zhao; Xue-liang Tian; Xin-liang Zhao; Ying-xia Wu; Xiu-ying Wei; Run-qiang Liu (Acta Physiologiae Plantarum, 2011)

Investigation on Heat and Mass Transfer in a Evaporator of a Capillary-Pumped Loop with the Lattice Boltzmann Method: Pore Scale Simulation - Yimin Xuan; Kai Zhao; Qiang Li (Transport in Porous Media, 2011)

Estimation of cancer cases and deaths attributable to infection in China - Wang Xiang; Ju-Fang Shi; Ping Li; Jian-Bing Wang; Li-Na Xu; Wen-Qiang Wei; Fang-Hui Zhao; You-Lin Qiao; Paolo Boffetta (Cancer Causes & Control, 2011)

Vascular Endothelial Growth Factor Increases Permeability of the Blood–Tumor Barrier via Caveolae-Mediated Transcellular Pathway - Li-ni Zhao; Zhi-hang Yang; Yun-hui Liu; Hao-qiang Ying; Hua Zhang; Yi-xue Xue (Journal of Molecular Neuroscience, 2011)

Expansin-regulated cell elongation is involved in the drought tolerance in wheat - Mei-rong Zhao; Feng Li; Ying Fang; Qiang Gao; Wei Wang (Protoplasma, 2011)

A novel human derived cell-penetrating peptide in drug delivery - Jian Zhao; Peng Gao; Wei Xiao; Li-Qiang Fan; Fu-Jun Wang; Su-Xia Li; Jian-Wen Liu (Molecular Biology Reports, 2011)

Artesunate inhibits growth and induces apoptosis in human osteosarcoma HOS cell line in vitro and in vivo - Qiang Xu; Zhao-xu Li; Hui-qin Peng; Zheng-wang Sun; Rui-lin Cheng; Zhao-ming Ye; Wei-xu Li (Journal of Zhejiang University-SCIENCE B, 2011)

Comparison of Non-covalent Interactions Between a Series of N-Phosphoryl Dipeptide or Methyl Esters and Protein by Electrospray Ionization Mass Spectrometry - Li-ming Qiang; Ming-xiu Lü; Xu-ru Dong; Shu-xia Cao; Kui Lu; Yu-fen Zhao (International Journal of Peptide Research and Therapeutics, 2011)

Weight-reducing effect of Acer truncatum Bunge may be related to the inhibition of fatty acid synthase - Wen-Hua Zhao; Li-Fang Gao; Wen Gao; Yong-Sheng Yuan; Chun-Chun Gao; Li-Ge Cao; Zi-Zheng Hu; Jian-Qiang Guo; Ying-Xia Zhang (Natural Product Research, 2011)

RETRACTED ARTICLE: NPC-16, a novel naphthalimide–polyamine conjugate, induced apoptosis and autophagy in human hepatoma HepG2 cells and Bel-7402 cells - Song-qiang Xie; Qian Li; Ya-hong Zhang; Jian-hong Wang; Zi-hou Mei; Jin Zhao; Chao-jie Wang (Apoptosis, 2011)

The pentapeptide PLNPK inhibits systemic lupus erythematosus-associated renal damage - Jun-qiang Lv; Wen Zhang; Song Wang; Lin Zhao; Rui Ma; Jin-wei Hu; Li-juan Wang; Jie Meng; Chun-lei Zhou; Gang Lin; Rong Lu; Zhi Yao (Inflammation Research, 2010)

MicroRNA-200b regulates cyclin D1 expression and promotes S-phase entry by targeting RND3 in HeLa cells - Wei Xia; Jie Li; Liucun Chen; Baochun Huang; Shaohua Li; Guang Yang; Hongmei Ding; Fang Wang; Nongle Liu; Qiang Zhao; Tao Fang; Tao Song; et al. (Molecular and Cellular Biochemistry, 2010)

PI3K-dependent host cell actin rearrangements are required for Cronobacter sakazakii invasion of human brain microvascular endothelial cells - Qiang Li; Wei-Dong Zhao; Ke Zhang; Wen-Gang Fang; Ying Hu; Shao-Hui Wu; Yu-Hua Chen (Medical Microbiology and Immunology, 2010)

Genetic evolution of equine influenza viruses isolated in China - Ting Qi; Wei Guo; Wen-Qiang Huang; Hong-Mei Li; Li-Ping Zhao; Ling-Li Dai; Na He; Xiao-Fang Hao; Wen-Hua Xiang (Archives of Virology, 2010)

Spontaneous Rhythmic Inward Currents Recorded in Interstitial Cells of Rabbit Portal Vein - Xu Huang; Dan Zhao; Zuo-Yu Wang; Ming-Liang Zhang; Zhi-Qiang Yan; Yan-Fei Han; Hong-Li Lu; Wen-Xie Xu; Zong-Lai Jiang (Cell Biochemistry and Biophysics, 2010)

Potential water sources for Late Quaternary Megalake Jilantai-Hetao, China, inferred from mollusk shell 87Sr/86Sr ratios - Yu-Xin Fan; Fa-Hu Chen; Guo-Xiao Wei; David B. Madsen; Charles G. Oviatt; Hui Zhao; Xi Chun; Li-Ping Yang; Tian-Lai Fan; Guo-Qiang Li (Journal of Paleolimnology, 2010)

Simvastatin attenuates TNF-α-induced growth inhibition and apoptosis in murine osteoblastic MC3T3-E1 cells - Yun-mei Yang; Wei-dong Huang; Qiang-min Xie; Zhe-rong Xu; Qi-jiang Zhao; Xi-mei Wu; Fen-fen Li; Xin-wei Dong (Inflammation Research, 2010)

Sex ratio deviation of offspring in the area where exposure to the processing of electronic wastes - Qiang Liu; Ke Qiu Li; Jia Cao; Hui Zhao; Guang Li; Fei Yue Fan (Environmental Science and Pollution Research, 2010)

Acute respiratory distress syndrome induced by H9N2 virus in mice - Guangcun Deng; Jianmin Bi; Fuli Kong; Xuezhu Li; Qiang Xu; Jun Dong; Miaojie Zhang; Lihong Zhao; Zhihua Luan; Nana Lv; Jian Qiao (Archives of Virology, 2010)

Responses of two rice cultivars differing in seedling-stage nitrogen use efficiency to growth under low-nitrogen conditions - Wei Ming Shi; Wei Feng Xu; Su Mei Li; Xue Qiang Zhao; Gang Qiang Dong (Plant and Soil, 2010)

A novel polymorphism of GDF5 gene and its association with body measurement traits in Bos taurus and Bos indicus breeds - Yong Feng Liu; Lin Sen Zan; Kui Li; Shuan Ping Zhao; Ya Ping Xin; Qing Lin; Wan Qiang Tian; Zhi Wei Wang (Molecular Biology Reports, 2010)

Association of LT-α Ala252Gly gene polymorphism and the genetic predisposition of coronary heart disease in Chinese - Hanxiang Gao; Zheng Zhang; Jin Zhang; Nan Zhao; Qiang Li; Ming Bai (Molecular Biology Reports, 2010)

Nasal cavity-maxillary sinus-pterygopalatine fossa-Meckel’s cave: a preliminary anatomic study of an endoscopy-based operative approach - Zhi-Qiang Bai; En-Yuan Cai; Shi-Qiang Wang; Zhao-Jian Li; Shou-Biao Wang (Neuroscience Bulletin, 2009)

Isolation and characterization of 14 dinucleotide microsatellite loci in the endangered herb Saruma henryi Oliv. (Aristolochiaceae) - Shan-Shan Dong; Xuan Huang; Zeng-Qiang Qian; Tian-Hua Zhou; Shan Li; Gui-Fang Zhao (Conservation Genetics Resources, 2009)

Characterization of EST-derived microsatellite loci in Saruma henryi Oliv., an endangered Chinese endemic herb - Tian-Hua Zhou; Gui-Fang Zhao; Shan Li; Zeng-Qiang Qian (Conservation Genetics Resources, 2009)

Tentative identification of glycerol dehydrogenase as Escherichia coli K1 virulence factor cglD and its involvement in the pathogenesis of experimental neonatal meningitis - Ke Zhang; Wei-Dong Zhao; Qiang Li; Wen-Gang Fang; Li Zhu; De-Shu Shang; Yu-Hua Chen (Medical Microbiology and Immunology, 2009)

Differential expression of N-Myc downstream regulated gene 2 (NDRG2) in the rat testis during postnatal development - Wu-Gang Hou; Yong Zhao; Lan Shen; Jie Zhao; Xue-Wu Liu; Zhen Li; Xin-Ping Liu; Li-Bo Yao; Yuan-Qiang Zhang (Cell and Tissue Research, 2009)

Genetic diversity and differentiation in Chinese sour cherry Prunus pseudocerasus Lindl., and its implications for conservation - Miao-Miao Li; Yu-Liang Cai; Zeng-Qiang Qian; Gui-Fang Zhao (Genetic Resources and Crop Evolution, 2009)

Seismic damage of highway bridges during the 2008 Wenchuan earthquake - Qiang Han; Xiuli Du; Jingbo Liu; Zhongxian Li; Liyun Li; Jianfeng Zhao (Earthquake Engineering and Engineering Vibration, 2009)

Functional characterization of rice OsDof12 - Dejun Li; Chunhua Yang; Xiaobing Li; Qiang Gan; Xianfeng Zhao; Lihuang Zhu (Planta, 2009)

The global challenge of electronic waste management - Qiang Liu; Ke Qiu Li; Hui Zhao; Guang Li; Fei Yue Fan (Environmental Science and Pollution Research, 2009)

Chromosomal aberrations and DNA damage in human populations exposed to the processing of electronics waste - Qiang Liu; Jia Cao; Ke Qiu Li; Xu Hong Miao; Guang Li; Fei Yue Fan; Yong Cheng Zhao (Environmental Science and Pollution Research, 2009)

MicroRNA-128 inhibits glioma cells proliferation by targeting transcription factor E2F3a - Yu Zhang; Tengfei Chao; Ran Li; Wei Liu; Yang Chen; Xingqi Yan; Yanhua Gong; Bin Yin; Wei Liu; Boqing Qiang; Jizhong Zhao; Jiangang Yuan; et al. (Journal of Molecular Medicine, 2009)

Increased pathogenesis and inflammation of airways from respiratory syncytial virus infection in T cell deficient nude mice - Juan Zhou; Xi-Qiang Yang; Zhou Fu; Xiao-Dong Zhao; Li-Ping Jiang; Li-Jia Wang; Yu-Xia Cui (Medical Microbiology and Immunology, 2008)

Involvement of ERK and AKT signaling in the growth effect of arginine vasopressin on adult rat cardiac fibroblast and the modulation by simvastatin - Yan-Ping He; Lian-You Zhao; Qiang-Sun Zheng; Shao-Wei Liu; Xiao-Yan Zhao; Xiao-Long Lu; Xiao-Lin Niu; Xia Li (Molecular and Cellular Biochemistry, 2008)

Expansins and coleoptile elongation in wheat - Qiang Gao; Meirong Zhao; Feng Li; Qifang Guo; Shichao Xing; Wei Wang (Protoplasma, 2008)

Triassic Nb-enriched basalts, magnesian andesites, and adakites of the Qiangtang terrane (Central Tibet): evidence for metasomatism by slab-derived melts in the mantle wedge - Qiang Wang; Derek A. Wyman; Jifeng Xu; Yusheng Wan; Chaofeng Li; Feng Zi; Ziqi Jiang; Huaning Qiu; Zhuyin Chu; Zhenhua Zhao; Yanhui Dong (Contributions to Mineralogy and Petrology, 2008)

A novel thioredoxin reductase inhibitor inhibits cell growth and induces apoptosis in HL-60 and K562 cells - Zuo-fu Peng; Lin-xiang Lan; Fang Zhao; Jing Li; Qiang Tan; Han-wei Yin; Hui-hui Zeng (Journal of Zhejiang University-SCIENCE B, 2008)

Localization of a novel gene for congenital nonsyndromic simple microphthalmia to chromosome 2q11-14 - Hui Li; Jia-Xin Wang; Cheng-Ye Wang; Ping Yu; Qiang Zhou; Yong-Gang Chen; Lu-Hang Zhao; Ya-Ping Zhang (Human Genetics, 2008)

A collection of 10,096 indica rice full-length cDNAs reveals highly expressed sequence divergence between Oryza sativa indica and japonica subspecies - Xiaohui Liu; Tingting Lu; Shuliang Yu; Ying Li; Yuchen Huang; Tao Huang; Lei Zhang; Jingjie Zhu; Qiang Zhao; Danlin Fan; Jie Mu; Yingying Shangguan; et al. (Plant Molecular Biology, 2007)

Renalase gene is a novel susceptibility gene for essential hypertension: a two-stage association study in northern Han Chinese population - Qi Zhao; Zhongjie Fan; Jiang He; Shufeng Chen; Hongfan Li; Penghua Zhang; Laiyuan Wang; Dongsheng Hu; Jianfeng Huang; Boqin Qiang; Dongfeng Gu (Journal of Molecular Medicine, 2007)

Analysis of Genetic Diversity and Population Differentiation of Larix potaninii var. chinensis Using Microsatellite DNA - Xiao-Min Yu; Qing Zhou; Zeng-Qiang Qian; Shan Li; Gui-Fang Zhao (Biochemical Genetics, 2006)

Increase in extracellular cross-linking by tissue transglutaminase and reduction in expression of MMP-9 contribute differentially to focal segmental glomerulosclerosis in rats - Senyan Liu; Yuehong Li; Huiying Zhao; Dong Chen; Qiang Huang; Suxia Wang; Wanzhong Zou; Youkang Zhang; Xiaomei Li; Haichang Huang (Molecular and Cellular Biochemistry, 2006)

Decreased cardiac sarcoplasmic reticulum Ca2+-ATPase activity contributes to cardiac dysfunction in streptozotocin-induced diabetic rats - Xiao-Yan Zhao; Shen-Jiang Hu; Jiang Li; Yun Mou; Bao-Ping Chen; Qiang Xia (Journal of Physiology and Biochemistry, 2006)

A novel technique of three-dimensional reconstruction segmentation and analysis for sliced images of biological tissues - Jing Li; Hai-yan Zhao; Xing-yun Ruan; Yong-qing Xu; Wei-zheng Meng; Kun-peng Li; Jing-qiang Zhang (Journal of Zhejiang University-SCIENCE B, 2005)

Climatic features of summer temperature in northeast china under warming background - Ji Li; Qiang Gong; Lian-wei Zhao (Chinese Geographical Science, 2005)

An autosomal genomic scan for loci linked to type 2 diabetes in northern Han Chinese - J. Y. Zhao; M. M. Xiong; W. Huang; H. Wang; J. Zuo; G. D. Wu; Z. Chen; B. Q. Qiang; M. L. Zhang; J. L. Chen; W. Ding; W. T. Yuan; et al. (Journal of Molecular Medicine, 2005)

Fed-batch fermentation of Lactobacillus lactis for hyper-production of l-lactic acid - Dong-Mei Bai; Qiang Wei; Zhi-Hui Yan; Xue-Ming Zhao; Xin-Gang Li; Shi-Min Xu (Biotechnology Letters, 2003)

An improved equation and assay for determining the CO2/O2 specificity for Rubisco - Guofu Li; Haibin Mao; Xiang Ruan; Qiang Xu; Yandao Gong; Xiufang Zhang; Nanming Zhao (Photosynthesis Research, 2003)